Selective separation of smithsonite from calcite through fluidization roasting-induced sulfidation transformation - Yuangan Chen; Yongsheng Sun; Xiaotong Wei; Peng Gao; Yanjun Li (Minerals Engineering, 2026)

Hydrogen-assisted suspension roasting for pre-reducing lateritic nickel ore: Comparison with CO reduction - Zhe Bai; Jiahao He; Mingxing Wang; Shaokai Cheng; Shuai Yuan; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Amino-functionalized hydrogel immobilized microbial consortia to reduce the dissemination risks of antibiotic resistance genes in soil - Yongxin Guo; Jiaoyang Ji; Xianfeng Lin; Yanjun Li; Gang Wang; Yong Yu (Bioresource Technology, 2026)

Single-cell profiling reveals IFI44L as a central regulator of immune dysregulation in high HIV viral load - Jiamin Gao; Yanjun Li; Jinping Huang; Xianzhen Huang; Qingdong Zhu; Cailing Wei; Jieling Chen; Shunda Luo; Zhouhua Xie (Medical Microbiology and Immunology, 2026)

Enzyme-immobilized hydrophilic metal-organic framework with in situ coenzyme regeneration and its application in the continuous synthesis of chiral hydroxycarboxylic acid - Danyang Zhao; Quan Yuan; Yongqi Pan; Zhao Li; Qiangqiang Xue; Yanjun Jiang; Yujun Wang; Guangsheng Luo (Chemical Engineering Journal, 2026)

Highly fluorescent Cucurbit[7]uril covalent organic frameworks for fluorescence sensor array - Nurimangul Muntiza; Qun Wang; Yanan Liu; Jiayi Wang; Xuejia Chang; Meifang Xiao; Boyu Yuan; Qinran Li; Haijie Li; Yanjun Yu; Qiliang Deng (Analytica Chimica Acta, 2026)

Suspension oxidative roasting for enhanced gold leaching from a quartz-rich refractory gold ore: Process optimization and microstructural evolution - Yan Song; Jianping Jin; Yanjun Li; Bing Zhao; Min Sun; Yuexin Han (Minerals Engineering, 2026)

Surface property evolution and floatability response of dolomite to hydrogen-based mineral phase transformation - Daolai Tian; Zhidong Tang; Peng Gao; Pengcheng Tian; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Study on the selective crushing behavior and mechanism of Dahongliutan spodumene ore under high-pressure grinding roll (HPGR) - Tianyou Yu; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Oxygen-controlled arsenic volatilization during preheating and preoxidation roasting of carbon–arsenic refractory gold ore - Hua Dong; Jianping Jin; Xinran Zhu; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Oxidation patterns and stability mechanisms of marine oils revealed by oxidized triglyceride and phospholipid analysis using RPLC–Q-TOF - Nan Meng; Yaru Li; Peixu Cong; Yu Song; Yanjun Liu; Jie Xu; Changhu Xue (Food Research International, 2026)

Enhanced peroxymonosulfate activation for antibiotic removal using Ni1Mn1Fe1-LDO/g-C3N4: Metallic electronic synergy and oxygen vacancy effects - Wenqi Bu; Zhan Wang; Tao Zhu; Zhaocai Wu; Siqi Liu; Jiang Li; Qianwen Wang; Shuaishuai Xin; Xiaozhe Song; Yanjun Xin; Qinghua Yan; Guocheng Liu (Environmental Research, 2026)

Unveiling TWC replacement benefits in in-use vehicles from a concentration-reactivity-toxicity perspective - Jie Yao; Xinping Yang; Yongdong Wang; Jian Wang; Yanjun Wang; Chao Peng; Hongfei Chen; Xin Li; Yunjing Wang; Yan Ding (Environmental Pollution, 2026)

A dual-functional heterosalt additive enables synergistic interphase-bulk engineering for advanced nickel-rich cathodes - Dongni Zhao; Jing Luo; Zixiang Su; Hongzeng Dou; Jingzuo He; Junwei Zhang; Yanjun Zhao; Xinfang Xu; Peng Wang; Ningshuang Zhang; Xiaoling Cui; Shiyou Li (Chemical Engineering Journal, 2026)

High-precision extraction and dynamics of thermokarst lakes in the Three Rivers Source Region using the SVM coupled edge-OTSU based on Sentinel-1 data - Wangping Li; Rongqi Wan; Xiaodong Wu; Xiaoqiang Cheng; Yadong Liu; Yanjun Bian; Heng Du; Niu Wang; Wenbo Wei; Zhaoye Zhou; Xiuxia Zhang; Defu Zou (CATENA, 2026)

Emerging advanced technologies: Modulation of sensory properties in milk and whey systems – A review - Waris Aziz; Khawaja Muhammad Ali Tayyab; Tahir Mahmood Qureshi; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Trends in Food Science & Technology, 2026)

Model-based inference of monsoonal moisture from stalagmite and tree-ring δ18O - Qiang Li; Yifan Wu; Jiachuan Wang; Yu Liu; Yanjun Cai; Haiwei Zhang; Liangcheng Tan; Jingyao Zhao; Changfeng Sun; Huiming Song; Yang Xu; Yueer Li; et al. (Quaternary Science Reviews, 2026)

A review on the modified clay minerals for remediation of lead contaminated soil: mechanism analysis, modification methods, challenges and future prospects - Pengcheng Tian; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Fluidized oxidative roasting of carbon-bearing gold ores for gold recovery: process and mechanism - Chuanlin Sun; Jianping Jin; Shoude Guo; Yanjun Li; Xinran Zhu (Minerals Engineering, 2026)

Efficient self-magnetization roasting of siderite via CO2 introduction - Tingbo Zhou; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

The mediator subunit PagMED20 is associated with enhanced vegetative growth and photosynthetic performance in poplar - Xiao Wang; Changwen Xu; Ce Zhang; Xuandong Liu; Binghe Wang; Yanjun Li; Jinxing Lin; Yaning Cui (Journal of Plant Physiology, 2026)

Selective adsorption of an eco-friendly depressant poly(acrylic acid-co-maleic acid) in columbite-dolomite flotation separation - Daolai Tian; Zhidong Tang; Peng Gao; Yanjun Li; Yuexin Han (Journal of Environmental Chemical Engineering, 2026)

Long-term petroleum pollution alters soil microbial communities via electron transfer capacity: Evidence from a 35-year chronosequence - Chengze Yu; Mingxiao Li; Jun Cui; Yanjun Xin; Ran Song; Wangmi Chen; Jiaqi Hou; Jianbing Li; Huibin Du; Beidou Xi (Journal of Environmental Sciences, 2026)

Mathematical model and experimental investigation on the effect of TiO2 on the electrodialysis separation process of the NH3-H2O-LiBr solution - Shenghao Huang; Zhenghao Jin; Mengkai Xu; Yunfeng Qiu; Chuang Pan; Kai Du; Weixue Jiang; Yanjun Li; Shuhong Li (International Journal of Refrigeration, 2026)

Optimization of zeotropic series cycle for improved temperature matching and energy efficiency in compact household refrigerators - Bingqi Li; Yanjun Du; Xudong Ma; Yuting Wu; Che Wang; Jie Lin; Haiqing Guan; Lubing Wang (International Journal of Refrigeration, 2026)

Hydrolyzed konjac glucomannan retards egg white protein digestion via glycosylation -driven gastric texture and rheology modulation - Lulu Guo; Yicheng Guo; Yating Wu; Shende Hu; Xiaosan Wang; Luping Gu; Cuihua Chang; Junhua Li; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2026)

Experimental and numerical investigation of shear buckling behaviour of friction stir welded 6013-T6 aluminium H-shaped beams - Beibei Li; Yanjun Tong; Boshan Chen; Jingfeng Wang; Hongzhuang Yang; Yihe Guo; Bingbing Sun (Engineering Structures, 2026)

Development characteristics and hazard mode of loess sinkhole-landslide-mudflow hazard chain: A typical case study of loess tableland - Kai Liu; Xingang Wang; Sheng Hu; Baoqin Lian; Yanjun Li; Daozheng Wang; Haoyu Wang; Chuyi Xu (Engineering Geology, 2026)

Gradient ultra-soft and self-adhesive hydrogels via an integrated multilevel design for wearable electronic patches - Sen Liu; Shanhua Qian; Jianhao Li; Yunpeng Dong; Da Bian; Yanjun Liu (Chemical Engineering Journal, 2026)

Balancing active hydrogen species flux via spillover enables efficient dilute-nitrate electroreduction to ammonia in a neutral medium - Chenghao Yang; Chang Shen; Yanjun Chen; Xin Xiao; Xiaoping Gao; Wanglai Cen; Mengyang Fan; Jianjun Li; Jinyu Liu; Jing Li (Chemical Engineering Journal, 2026)

Engineering Cupriavidus necator for L-threonine production - Shuang Sha; Yanjun Li; Xiaowei Peng (Biotechnology Letters, 2026)

Stage-specific estimation of rice leaf area index and above-ground biomass from UAV LiDAR-derived structural features - Zhongyu Jin; Yanjun Wang; Juchi Bai; Zhonghui Guo; Shilong Li; Fenghua Yu; Tongyu Xu (Computers and Electronics in Agriculture, 2026)

Progressive Failure Mechanism and Prediction Model of Geogrid‑Reinforced Embankments under Long‑Term Service Conditions in Xinjiang, China - Weijia Sun; Caijin Wang; Xuejun Liu; Liangfu Xie; Yanjun Li; Yan Wang; Yuelong Ha; Chuanhong Qiang; Weilin Ma; Annan Zhou; Songyu Liu (Transportation Geotechnics, 2026)

Corrigendum to “Toward climate-adaptive rural morphology: a grid-based micro-mesh framework for quantifying microclimate drivers” [Sustainable Cities and Society 148 (2026) 107617] - Zhixing Li; Yanjun Su; Tsung-Hsien Wang; Mimi Tian (Sustainable Cities and Society, 2026)

Toward climate-adaptive rural morphology: a grid-based micro-mesh framework for quantifying microclimate drivers - Zhixing Li; Yanjun Su; Tsung-Hsien Wang; Mimi Tian (Sustainable Cities and Society, 2026)

Contrasting cold season temperature trends between eastern and western mid-latitude Eurasia over the past millennium - Yuan Yao; Yongsong Huang; Lu Wang; Yurui Zhang; Nan Dai; Liang Ning; Hanying Li; Jie Liang; Xiangzhong Li; Yanjun Cai; Hai Cheng (Quaternary Science Reviews, 2026)

Selective breakage mechanism of ore under high-voltage pulse and development of discharge channel - Bo Zhang; Yanjun Li; Peng Gao; Shuai Yuan; Honghao Zhang (Minerals Engineering, 2026)

Sparse hierarchical recurrent modeling for real-time grade prediction in hydrogen-based hematite transformation: modeling and industrial validation - Tianyou Yu; Anh Nguyen; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Molecular mechanisms and environmental implications of thallium complexation with butyl xanthate - Ling Ma; Yanjun Wang; Yao Jin; Mengqiang Fan; Mengke Li; Yuehui Chen; Cao Liu; Yun Liu; Zhimin You (Journal of Hazardous Materials, 2026)

Research progress on regulation strategies and mechanisms of graphitic carbon nitride (g-C3N4)-based materials for photocatalytic CO2 reduction - Yanjun Li; Mingxia Tian; Yuan Zhang; Jianhui Jiang (Journal of Environmental Sciences, 2026)

pH-Shifting combined with heat treatment regulates the aggregate structure and interfacial functional properties of egg white protein microparticles powder - Yating Wu; Yicheng Guo; Junhua Li; Luping Gu; Yanjun Yang; Cuihua Chang; Yujie Su (Food Research International, 2026)

High internal phase Pickering emulsions stabilized by submicron composite particles via ultrasound-assisted binding of lysine to whey protein isolate: Interfacial behavior, microstructural evolution and stabilization enhancement - Yanjun Li; Yingying Sui; Luodi Xu; Olayemi Eyituoyo Dudu; Xuenan Gao; Yan Li; Jinju Cheng; Xiaodong Li (Food Chemistry, 2026)

Heavy metal pollution in complex polymetallic ore processing: migration mechanism, treatment technologies, and future perspectives - Pengcheng Tian; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Environmental Research, 2026)

Bioactive orientin-loaded Janus adhesive hydrogel promotes macrophage polarization and gastric injury repair - Yanqi Li; Yang Su; Huawu Yang; Maoyuan Zhao; Wangshuo Yang; Zhenxing Wang; TongTong Zhang; Jie Chen; Yanjun Liu; Lu Liu; Jinhao Zeng (Chemical Engineering Journal, 2026)

A comprehensive LMUPO research framework: Integrating outdoor urban microclimates into building performance analysis and optimization - Zhixing Li; Yi Yang; Rong Xia; Yanjun Su; Zhuoyang Sun (Building and Environment, 2026)

Soil reinforcement by Robinia pseudoacacia roots and its stabilization mechanism for shallow root-soil composite slopes - Xing Chen; Yanjun Shen; Ping Ni; Zijian Li; Jinyu Zhu; Yibing Ning; Haitao Wang (Bulletin of Engineering Geology and the Environment, 2026)

A multi-pronged strategy towards one-stage partial nitritation/anammox in a lab-scale MABR - Yimeng Li; Dongdong Xu; Yan Lu; Chenkai Niu; Yanjun Shao; Jianhua Guo (Water Research, 2026)

Retraction notice to “Biochar for urban agriculture: Impacts on soil chemical characteristics and on Brassica rapa growth, nutrient content and metabolism over multiple growth cycles” [Sci. Total Environ. 727 (2020) 138742] - Shuang Song; Srishti Arora; Anna Karen C. Laserna; Ye Shen; Brian W.Y. Thian; Jia Chin Cheong; Jonathan K.N. Tan; Zhongyu Chiam; Siew Lee Fong; Subhadip Ghosh; Yong Sik Ok; Sam F.Y. Li; et al. (Science of The Total Environment, 2026)

Mechanical evaluation of high-performance fiber ropes: creep test, tensile response and joint behavior - Beibei Li; Yanjun Tong; Yuanqing Wang; Shaomin Chen; Zongyi Wang; Jingfeng Wang; Zhe Wang; Quanxi Ye (Ocean Engineering, 2026)

Semi-industrial-scale detoxification of cyanide tailings by suspension oxidation roasting and feasibility evaluation for underground backfilling - Bing Zhao; Yan Song; Shuai Yuan; Peng Gao; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Recovery of smithsonite via suspension sulfidation roasting: Evaluation of surface properties and flotation behavior - Yuangan Chen; Yongsheng Sun; Peng Gao; Yanjun Li (Minerals Engineering, 2026)

Kinetic mechanism and structural evolution during blank roasting of vanadium-bearing shale - Xiaolong Yu; Jianping Jin; Xinran Zhu; Zhe Bai; Shuaihou Yang; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Activated carbon-quartz sand dual-layer filter material accelerates the start-up of filter: Performance and mechanism - Sen Yang; Dong Li; Hongpeng Li; Jifang Zheng; Yanjun Zhu; Sibo Fu; Huiping Zeng; Jie Zhang (Journal of Water Process Engineering, 2026)

Chronic heat exposure induces brain atrophy in mice: Molecular signatures and AI-driven intervention strategy - Wenxin Xiang; Bo Yin; Qi Huang; Shisu Li; Miaohui Ding; Guoqing Feng; Ruoran Li; Dizhi Wang; Leizi Min; Xingyuan Hu; Limei Ke; Linfeng Liu; et al. (Journal of Environmental Sciences, 2026)

Seasonal-Spatial Hydrochemical Variations and Salinity Control Mechanisms of Shallow Groundwater: Insights from the Northern Piedmont of the Qinling Mountains, China - Yixin Liu; Hui Qian; Panpan Xu; Xiaoxin Shi; Siqi Li; Yanyan Gao; Weijie Zhao; Shuhan Yang; Zhiming Cao; Jie Chen; Yanjun Shen (Journal of Environmental Sciences, 2026)

A review of lithium extraction from primary and secondary lithium resources using supercritical CO2 - Hongquan Wei; Jie Liu; Ruichen Wang; Yanjun Li; Yuexin Han; Chengxiu Li (Hydrometallurgy, 2026)

Morphodynamic adjustments of the Lower Yangtze River during 1988–2023: Integrated effects of sediment reduction and rocky outcrops - Lei Zhang; He Qing Huang; Hui Li; Zhongwu Jin; Chao Guo; Peng Yang; Yanjun Wang; Tianwei Qian (Geomorphology, 2026)

Impacts of coal particle size and secondary air ratio on NO and N2O emissions in a 10 kW circulating fluidized bed: Experimental and numerical simulation - Yingchuan Zhou; Yanjun Zuo; Haiyang Li; Zhaoxin Wan; Rui Jin; Xiaojia Wang; Yufeng Duan (Fuel, 2026)

Elucidating the oxidation mechanism of phospholipid-based marine oils during storage: A new insight based on the analysis of oxidized phospholipids - Nan Meng; Peixu Cong; Xincen Wang; Yu Song; Yanjun Liu; Yaru Li; Jie Xu; Changhu Xue (Food Research International, 2026)

Egg yolk phospholipid peptides as dual-functional nanocarriers for curcumin: Enhanced hypolipidemic effects and mechanism - Ruyi Zhang; Wenhui Feng; Lili Jiang; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Yi Wang; Junhua Li (Food Research International, 2026)

Structural characterization, functional properties and formation mechanism of alkali-thermal induced egg white gel: from macroscopic gel properties to molecular conformation and interactions - Shende Hu; Xiaochen Liu; Luping Gu; Cuihua Chang; Junhua Li; Xiaosan Wang; Jun Sun; Shijian Dong; Han Jiao; Yanjun Yang; Yujie Su (Food Research International, 2026)

Investigating the molecular mechanism of plasmalogen and quality changes in Pacific oyster (Crassostrea gigas) depurated under salinity stress - Yu Song; Lili Hao; Xincen Wang; Peixu Cong; Yanjun Liu; Xiaoxu Wang; Zhaojie Li; Changhu Xue; Jie Xu (Food Research International, 2026)

Association study on the regulation of muscle development-related genes, proteins, and metabolites in different tissues by gastrointestinal flora during various developmental stages of Liaoning cashmere goats - Yinggang Sun; Xingtang Dou; Qingyu Yuan; Ran Duan; Qiying Zhan; Taiyu Hui; Yanjun Qiao; Jiaqi Li; Wangshu Li; Yunlong Guo; Dakun Lyu; Jiaqi Ge; et al. (Food Chemistry, 2026)

Corrigendum to “Layered Bayesian model comparison and uncertainty quantification for CPTU dissipation test inversion” [Comput. Geotech. 201 (2027) 108489] - Jingtong He; Liangfu Xie; Caijin Wang; Xuejun Liu; Jun Wang; Zhiming Liu; Xianming Hou; Yanjun Li; Tao Zhang; Annan Zhou; Songyu Liu; Guojun Cai (Computers and Geotechnics, 2026)

Magnetic droplet carrier robot integrated with AI-fueled on-site detection - Long Jiao; Wentao Yan; Yanjun Hu; Dongliang Li; Zhenting Xie; Zibing Pan; Qianqian Guo; Xiao Yan; Xiang Wu; Qi Wu (Chemical Engineering Journal, 2026)

A synergistic metal ion–silane strategy enables fire-safe, water-repellent, and mold-resistant flattened bamboo board - Longchao Ma; Genmiao Wan; Yan Wang; Chenkai Dou; Danhe Liu; Yue Jiao; Hao Sun; Xinzhou Wang; Yi Chen; Qiliang Fu; Yanjun Li (Chemical Engineering Journal, 2026)

A near-infrared fluorescent probe lights up protective carbon monoxide during inflammation in live systems - Sihang Lv; Longyang Yang; Changjian Wu; Yangtian Liu; Yanjun He; Yuyao Cao; Pengfu Li; Zhongchang Wang; Hai-Liang Zhu (Analytica Chimica Acta, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

When defence mechanisms fail: Multi-omics evidence of antioxidant system collapse in Thymallus grubii liver under acute temperature stress - Xinchi Shang; Xinghua Che; Kai Ma; Huaifa Chen; Lanlan Zhang; Huizhi Sun; Yanjun Li; Meiqi Xing; Wei Xu; Wenhua Wu; Yongquan Zhang (Marine Pollution Bulletin, 2026)

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

Spectral and structural analysis of a new lactone metabolite isolated from a mangrove endophytic fungus - Meijing Tan; Shichao Ju; Fan He; Wenjun Li; Youquan Wei; Rui Pi; Xishan Huang; Yanjun Zhang (Natural Product Research, 2026)

Ephedplics E-I: three lignans and two benzofuran-type compounds from the roots of Ephedra sinica Stapf and their neuroprotective activity - Yunlong Dou; Bowen Zhang; Meng Li; Xiaolan Wang; Shuyan Liu; Yanjun Sun; Xiaoke Zheng; Weisheng Feng (Journal of Natural Medicines, 2026)

A high-strength interpenetrating-network cotton-derived biochar aerogel: Coupling uranium(VI) removal and interfacial solar desalination - Yang Wang; Yun Wang; Yang Li; Yanjun Du; Hao Jiang; Ruiyang Chang; Xingnong Wu; Yan Liu; Dingzhong Yuan; Xiaoyan Li (Process Safety and Environmental Protection, 2026)

Environmental and process performance implications of conversion-controlled kinetics and structure–reactivity coupling in fluidized-bed calcination of coarse limestone - Tong Chen; Xinran Zhu; Yanjun Li; Yuexin Han (Process Safety and Environmental Protection, 2026)

Hydrogen-based fluidized bed reduction of limonitic laterite nickel ore: towards co-recovery of iron and nickel and metallization enhancement - Jiaqi Wang; Yanjun Li; Jianwen Yu; Yuexin Han; Jianping Jin (Minerals Engineering, 2026)

Hydrogen fluidization roasting process to treat zinc-bearing dust: kinetics, mineral phase transformation, and magnetism - Xinran Zhu; Tong Chen; Lijie Hao; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

The effect of environmental concern on consumers’ preferences for carbon-neutral-labeled dairy: Evidence from China - Qi Liu; Shaoting Li; Yanjun Ren; Jens-Peter Loy (Journal of Environmental Management, 2026)

Belowground reorganization complements canopy regulation in stabilizing yield formation of dual-planting cotton - Jingyuan Zhou; Lijie Zhan; Dongmei Zhang; Shizhen Xu; Zhenhuai Li; Yanjun Zhang; Jianlong Dai; Zhengpeng Cui; Xiaoli Tian; Hezhong Dong (Field Crops Research, 2026)

Restoration effects of China’s Shan-Shui Initiative: Quantitative assessment based on the improved Remote Sensing Ecological Index (kRSEI) - Yanjun Shen; Shengwei Zhang; Yanzhao Yuan; Bo Wang; Tieming Liu; Yajun Li; Jianbing Peng (Science China Earth Sciences, 2026)

Intensifying ocean stratification reduces vertical phosphate supply and carbon sink magnitude - Rui Wang; Xuegang Li; Jinming Song; Zhibo Wang; Shanshan Liu; Guorong Zhong; Yanjun Wang; Jun Ma; Huamao Yuan; Liqin Duan (Limnology and Oceanography, 2026)
In recent decades, global warming‐driven ocean stratification has profoundly affected nutrient cycling. As the largest marginal sea in the northwestern Pacific, the South China Sea (SCS) provides a representative setting to examine these responses. Based on two decades of temperature, salinity, and nutrient datasets, we quantified the evolution of stratification in the SCS, its impacts on the upward transport of deep‐water phosphate (PO 4 3− ), and the resulting changes in carbon sink. Results show an increasing intensification of stratification, with an upward shift of the thermocline's upper boundary, a downward shift of its lower boundary, increased thickness, and weakened vertical mixing. Despite enhanced external inputs from rivers and atmospheric deposition and reduced phytoplankton consumption of PO 4 3− in the mixed layer, PO 4 3− concentrations have declined persistently, indicating a substantial reduction in nutrient flux from the deep water across the thermocline into the surface layer. The minimum net reduction of PO 4 3− in the upper water column (mixed layer plus thermocline) was −0.047 Gmol·yr −1 . This decline in PO 4 3− supply constrained primary production and reduced CO 2 uptake, leading to an estimated carbon sink reduction of 2.21 × 10 5 t CO 2 ·yr −1 in the SCS.

Potential mechanism of Lactiflorin in treating ulcerative colitis via modulation of the PI3K/AKT pathway: a study integrating network analysis, bioinformatics analysis, and experimental evidence - Mengjia Zhang; Haotian Li; Ningjuan Yan; Man Meng; Xiaolan Su; Yanjun Liu; Runhua Chen; Jianqin Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Process design and optimization for resource-efficient recovery of Fe, P, and Ti from a low-grade complex iron ore - Shiteng Qin; Xiaokun Li; Bing Zhao; Peng Gao; Yanjun Li; Zhidong Tang (Minerals Engineering, 2026)

Hydrogen-based suspension roasting for efficient utilization of high-phosphorus oolitic hematite: Selective reduction mechanism and metallization behavior - Xuesong Sun; Yanjun Li; Zhidong Tang; Jianwen Yu; Yize Guo; Jianping Jin; Yuexin Han (Minerals Engineering, 2026)

Feasibility of using tap water instead of deionized water in the high-voltage pulse breakage process of magnetite quartzite - Bo Zhang; Peng Gao; Shuai Yuan; Yanjun Li; Honghao Zhang (Minerals Engineering, 2026)

The interplay of carbon, nitrogen, and phosphorus in plants: From independent effects to synergistic regulation - Yanjun Li; Chunmei Luo; Jikai Li; Jemaa Essemine; Mingnan Qu (Journal of Plant Physiology, 2026)

Hydrochemical model of a fault-controlled playa (Jiahu) in the piedmont of Altun Mountain, Qaidam Basin, China: Insights from Sr, B, H, O isotopes, and chemical compositions - Lijian Shen; Yanjun Zhao; Wei Li; Bing Pan (Journal of Hydrology, 2026)

SIRT1 protects against UVA-induced photoaging by suppressing oxidative stress and FOXO3a acetylation in human dermal fibroblasts - Wenjuan Ma; Min Jiang; Jingtao Zhang; Wenjie Liu; Yanjun Dan; Wenjia Sun; Li Ma; Leihong Xiang; Jie Ren (Journal of Photochemistry and Photobiology B: Biology, 2026)

High internal phase emulsions stabilized by milk protein-arabinoxylan-quercetin ternary complex: Enhanced environmental stability and fat digestive property (Milk protein-AX-Q complex-stabilized HIPEs: Stability and digestion) - Xuenan Gao; Peizhu Liu; Sirong Li; Olayemi Eyituoyo Dudu; Yanjun Li; Yan Li; Hongfang Yang; Jinju Cheng; Tingsheng Yan (Journal of Food Engineering, 2026)

Rendering regenerated cellulose films superhydrophobic via modulated silanization in regeneration process - Xinhua Dong; Ya Li; Junming Wang; Chunjie Ye; Huining Xiao; Yanjun Tang (Journal of Environmental Chemical Engineering, 2026)

Synergistic effect of cocatalyst engineering and radical regulation toward high selectivity in one-step methane conversion - Chuan Yu; Mingli Fu; Keke Tang; Yanjun Li; Lei Liu; Chen Yang; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Improving functional and interfacial performance of whey protein by pH shift combined with enzymatic glycosylation modification and its effect on high internal phase emulsions - Luodi Xu; Peizhu Liu; Yanjun Li; Olayemi Eyituoyo Dudu; Yiping Luo; Jinju Cheng; Yujun Jiang (Innovative Food Science & Emerging Technologies, 2026)

Trianglamine-based polyurea nanofiltration membranes with exceptional acid stability and high dye/salt selectivity - Langyu Chen; Dibao Zhu; Qisheng Miao; Sisi Li; Yixuan Luo; Shiyu Liu; Weihang Jiang; Yanjun Ding; Tiefan Huang (Chemical Engineering Journal, 2026)

Failure mechanism and damage assessment of talus slopes with varied gradation under seismic loading - Xing Wei; Shitao Cheng; Rui Chen; Xinle Zhai; Jun Feng; Zijian Wang; Yanjun Li; Le Cheng (Landslides, 2026)

Biochar reshapes phosphorus distribution in soil aggregates and improves rice phosphorus uptake - Jiajun Wu; Bin Zhou; Zhehao Huang; Zichuan Li; Jingyuan Pan; Kaihao Zhang; Cheng Liu; Yanjun Chai; Yan Li; Muhammad Azeem; Nicholas Clarke; Shengdao Shan (Soil Ecology Letters, 2026)

Performance analysis and experimental study of flexible opening-closing single garlic seed metering device based on DEM-MBD coupling - Zhengzhong Li; Hua Zhou; Yinping Zhang; Fangyuan Lu; Xian Wang; Jiaye Li; Yanjun Li; Yangting Hu; Rui Yu (Computers and Electronics in Agriculture, 2026)

Simultaneous cyanide detoxification and sulfur immobilization in low-sulfur cyanide tailings via sustainable oxidation roasting: process optimization and mechanistic insights - Bing Zhao; Yan Song; Shuai Yuan; Peng Gao; Yuexin Han; Yanjun Li (Waste Management, 2026)

Nanoplastics induce SH-SY5Y cell damage through oxidative stress and disruption of amino acid metabolism - Tianyi Ma; Yuyang Liu; Jingran Sun; Yanjun Fang; Yonghui Wang; Xiaoli Li; Nan Su; Mingzhu Liu; Zunquan Zhao; Jin Wu; Jialei Bai (Toxicology, 2026)

Weyl points enabling significant enhancement of thermoelectric performance in an antiferromagnetic van der Waals metal GdTe3 - Zhigang Gui; Panshuo Wang; Wenxiang Wang; Yuqing Zhang; Yanjun Li; Yikang Li; Qingyuan Liu; Xikai Wen; Qihang Liu; Jianjun Ying; Xianhui Chen (Science Bulletin, 2026)

Research on single-phase thermal-hydraulic behavior of the piping system under the influence of mechanical vibration - Xu Chen; Jianxin Shi; Yuanshao Sun; Qingpeng Zeng; Wanze Wu; Xin Zhang; Xichao Liang; Yanjun Li; Jie Yang; Xinrong Wang; Yuanwei Cao (Ocean Engineering, 2026)

Comparison of dephosphorization processes for high-phosphorus oolitic hematite based on MLA mineralogical characteristic analysis - Yusen Yu; Wenbo Li; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Mechanistic insights into the hydrogen-based phase transformation processes of iron-bearing manganese ores - Ruofeng Wang; Shuai Yuan; Jiangang Ku; Qinglong Fan; Yanjun Li (Minerals Engineering, 2026)

Operational threshold and associated mechanisms in composting remediation of diesel-contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Environmental Management, 2026)

A novel biogas liquefaction process adopting dual nitrogen expansion cycle with carbon dioxide pre-cooling - Yanjun Huang; Qingfeng Jiang; Xiaofei Lu; Xiao Song; Jiangchao Wang; Huaibin Li (International Journal of Refrigeration, 2026)

Harnessing Lactiplantibacillus plantarum LW11: A promising bio-preservative for extending cake shelf life through antifungal metabolites - Xuechun Wang; Zhishuo Zhang; Cuihua Chang; Yujie Su; Luping Gu; Yanjun Yang; Hong Sun; Junhua Li (Food Control, 2026)

Multi-level metabolic engineering for efficient ergothioneine production in yeast using a Pleurotus ostreatus-derived pathway - Zhongjuan Di; Yanjun Huo; Yuejun Fu; Bo Li; Yingping Zhuang (Chemical Engineering Journal, 2026)

Accumulation pattern, source apportionment and risk assessment of soil heavy metals across diverse land use types: Insights from the northern foothills of Qinling mountains, China - Bingyao Huo; Yanjun Shen; Yibing Ning; Wei Shen; Penghui Ma; Zhijie Jia; Luqing Zhao; Junyan Zhao; Xing Chen; Tao Ding; Sirui Li; Jianbing Peng (CATENA, 2026)

Dauricine ameliorates intestinal inflammation and oxidative stress in DSS-induced colitis through TLR4/NLRP3/GSDMD-mediated pyroptosis and Nrf2 pathway - Lin Wang; Jingyuan Liu; Jiayi Wang; Yuxin Xie; Yanan Gao; Daili Xu; Jing Li; Jing Dong; Bingyao Li; Yanjun Cao; Yang Li; Jiao He (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Correction to: Evaluating carbon footprint calculators: a comprehensive assessment framework - Ziqian Xia; Kuang Liu; Jiangnan Li; Yanjun Gu; Bo Hu; Yun Zhong; Jinquan Ye; Ka Leung Lam (Clean Technologies and Environmental Policy, 2026)

Phosphorus Speciation and Mobility in the Dredged Sediment of an Urban Lake: The Role of Coupled Fe-S-P Dynamics and Microbial Succession - Baoquan Li; Min Zhang; Jicheng Zhong; Jiayu Qin; Haiyuan Cai; Chuanzhe Sun; Fanyan Yang; Yanjun Wu; Shanshan Liu; Hui Yang; Fen Huang (Water Research, 2026)

Decoupling environmental drivers of bioaerosol emissions during food waste degradation - Yanjun Liu; Haiwen Ning; Qiange Tang; Yanfeng Zhang; Zhuowen Chen; Qingfei Li; Jianbing Wang; Zhanhong Yang (Waste Management, 2026)

Strong tri-genic epistasis among natural alleles of the OsMYB2–OsGH18–OsCAD3 module enhances drought tolerance in rice - Mingyue Huo; Shanwen Wang; Fan Zhang; Min Li; Ming Yin; Yuxin Lei; Yanfang Wang; Yanjun Chen; Dapu Liu; Xiuqin Zhao; Binying Fu; Fengyi Hu; et al. (Molecular Plant, 2026)

Redox-active co-pyrolytic carbon enhances electron transfer and mitigates petroleum hydrocarbon hazards in contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Hazardous Materials, 2026)

Electro-trapping uranium(VI) by ternary phosphate-functionalized polymer / molybdenum disulfide / pod shell-derived biochar composite electrode - Dongqing Huang; Yun Wang; Yang Wang; Qidong Ye; Yang Li; Hao Jiang; Yanjun Du; Yan Liu; Dingzhong Yuan; Xianping Luo (Journal of Environmental Management, 2026)

Construction of CuO-ZnO interface electron channels accelerates the methane partial oxidation for high formaldehyde production - Yanjun Li; Chuan Yu; Chen Yang; Keke Tang; Xueyun Zhong; Sijia Weng; Chuying Qiu; Mingli Fu; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Unconventional seasonal variation and mechanisms of sediment phosphorus release in an Urban lake - Baoquan Li; Suisui Zhang; Yanjun Wu; Ying Li; Min Zhang; Chuanzhe Sun; Fanyan Yang; Yuyi Wang; Shanshan Liu; Hui Yang; Fen Huang; Jicheng Zhong (Journal of Environmental Sciences, 2026)

Spatiotemporal distribution of legacy and alternative per- and Polyfluoroalkyl substances (PFASs) in major rivers of the Pearl river delta - Ting Wu; Yonglong Lu; Pei Wang; Cong Wang; Haojie Lei; Yanjun Liu; Kongming Li; Zhenjun Zhang (Journal of Environmental Sciences, 2026)

Sustainable hierarchical carbon architectures from bamboo for enhanced electromagnetic wave dissipation - Jiateng Chen; Minzhen Bao; Yu Wang; Weigang Zhang; Tiancheng Yuan; Yanjun Li (Environmental Research, 2026)

Occurrence and distribution of phthalate esters in stormwater runoff and coastal water receiving bodies, Macao, South China - Yutang Luo; Tianyi Zhang; Yaru Cao; Qiying Jian; Aolei Du; Jun Yan; Yanjun Li; Youxiang Xu; Guoyuan Zhu; Xiong Xiong; Chenxi Wu; Kai Zhang (Environmental Pollution, 2026)

Low-temperature anammox efficiency is governed by matrix-mediated modulation of quorum sensing - Yanjun Zhu; Dong Li; Sen Yang; Sibo Fu; Hongpeng Li; Songyue Li; Huiping Zeng; Jie Zhang (Bioresource Technology, 2026)

Occurrence, persistence and vertical distribution of high-risk antibiotic resistance genes in biogas slurry-amended soils across China - Liting Zhang; Hao Li; Jiwei Li; Yi Lu; Yanjun Chai; Zichuan Li; Lifeng Ping; Ming Hung Wong; Shengdao Shan (Bioresource Technology, 2026)

Non-Invasive functional assessment of severity in cerebral arterial stenosis using cerebral flow fraction: A hemodynamic study - Hao Sun; Bao Li; Zijie Wang; Liyuan Zhang; Jun Zhao; Yanping Zhang; Guangfei Li; Jinli Ding; Yanjun Gong; Hwa Liang Leo; Youjun Liu (Medical & Biological Engineering & Computing, 2026)

Metabolomic profiling reveals activity-correlated chemotypes and strain-specific metabolites in mangrove-derived actinomycetes - Bonan Yan; Ming Chen; Ling Li; Peixi Zhang; Ki Shi; Li Guo; Yixin Tang; Chunlan Li; Yanjun Di; Chen Zhu; Yuting Wu; Chenlei Lian; et al. (Natural Product Research, 2026)

Prediction Method and Application of Dynamic Surface Subsidence in Deep-Buried Thick Alluvium Considering Aquifer Consolidation - Shenyi Zhang; Shanxi Wu; Han Zhang; Weijie Wei; Boyuan Cheng; Yanjun Song; Xiujuan Li; Yaochen Wang (Rock Mechanics and Rock Engineering, 2026)

Climate and vegetation-driven variations, ecological thresholds and mechanisms of ecosystem services in China’s drylands - Baolong Ma; Linlin Gao; Yanjun Xu; Xinyue Li; Yang Deng; Haijiang Yang (Environment, Development and Sustainability, 2026)

Rap1b is a critical regulator of germinal vesicle breakdown in porcine oocytes - Mingyue Sui; Zhihao Wang; Jianqiang Sun; Ruohan Mei; Mingju Sun; Yichen Liu; Xiang Gao; Youwei Li; Yanjun Huan (Theriogenology, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Sustainable ironmaking via Hydrogen-based suspension pre-reduction of hematite: reduction mechanisms, bonding behavior, and comparison with carbon routes - Xuesong Sun; Yanjun Li; Jianwen Yu; Yize Guo; Yuexin Han (Minerals Engineering, 2026)

A new type of absorber based on ultrasonic atomization enhanced in-tube falling film absorption process - Chuang Pan; Shenghao Huang; Yunfeng Qiu; Shuhong Li; Teng Jia; Yanjun Li; Jun Wu; Gui Li (International Journal of Refrigeration, 2026)

Holocene climate optimum moisture variability in the monsoon marginal zone of northern China revealed by multi-proxy stalagmite records - Shouyi Huang; Yanjun Cai; Gang Xue; Xinhui Zhang; Mei He; Ruoxin Li; Yingying Wei; Le Ma; Xing Cheng; Haiwei Zhang; Hai Cheng (Global and Planetary Change, 2026)

New insights into source of long chain n-alkanes in cave stalagmites - Yinan Zhao; Yuan Yao; Lu Wang; Yunning Cao; Haiwei Zhang; Tingyong Li; Yanjun Cai; Hai Cheng (Geochimica et Cosmochimica Acta, 2026)

Revealing the impact of short side-chain migration on the digestive kinetics and multiscale structure of ultrasound-treated nano-scale amylopectin endogenous ternary complexes - Bo Li; Mingyang Gao; Chongxing Huang; Xin Yang; Weihong Lu; Yanjun Zhang (Food Hydrocolloids, 2026)

Early cotton topping increases peanut yield without sacrificing cotton yield through reducing interspecific competition under intercropping - Junjun Nie; Yanan Li; Zhenhuai Li; Shizhen Xu; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Lin Sun; Jianlong Dai; Yanjun Zhang; Hezhong Dong (Field Crops Research, 2026)

Microplastics affect the quality of Cucumis melo. L by regulating the jasmonic acid signaling pathway - Tianyu Liu; Jinpeng Zhang; Mao Xu; Zhengkun Zhang; Yanjun Li; Xuedong Tang; Ling Liu; Yong Yu (Environmental Pollution, 2026)

Domain adaptation-enhanced transfer learning framework for cross-building cooling load forecasting: Case studies in metro stations - Panlong Liu; Yinghuai Liang; Shuhong Li; Yanjun Li; Wei Sheng (Energy and Buildings, 2026)

Covalently bonded ZnO-reinforced waterborne polyurethane incorporating carboxymethyl chitosan with synergistic antibacterial and antifouling functions - Yanjun Liu; Shurun Li; Jian Bin Zhen; Henghui Zhang; Ruifei Hao; Wenying Liu; Yayue He; Lina Dong (Chemical Engineering Journal, 2026)

Corrigendum to “Ultrafast improvement of cellulose accessibility via non-dissolving pretreatment with LiBr·3H2O under room temperature” [Carbohydrate Polymers 284 (2022) 119180] - Zhonglei Huang; Guang Yu; Chao Liu; Meiyan Wu; Yanjun Tang; Bin Li; Hui Peng (Carbohydrate Polymers, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

Formation mechanisms of dense biological flocs in a full-scale wastewater treatment plant employing hydrocyclone and chemical phosphorus removal - Yanjun Shao; Dongdong Xu; Xiang Tao; Zhizhang Shen; Sisi Chen; Tao Liu; Shuo Wang; Jianhua Guo; Ji Li (Water Research, 2026)

Achieving efficient separation of iron and manganese from iron-bearing manganese ore: A hydrogen-based mineral phase transformation magnetic separation strategy - Ruofeng Wang; Shuai Yuan; Jiangang Ku; Qinglong Fan; Zijian Wu; Yanjun Li (Minerals Engineering, 2026)

Earthworm activity and its gut microbiota drive the valorization of municipal sewage sludge by enhancing aggregate stability and phytohormone content - Yunxiang Xu; Jin Wang; Guoxun Su; Yizhao Wu; Jiayi Li; Huaixiang Zhou; Xiaoying Yi; Li Tang; Yanjun Shen; Yinsheng Li; Qi Zhao (Journal of Environmental Chemical Engineering, 2026)

Research on the motion characteristics of sliding vane in rolling piston compressor under low-speed condition - Yanjun Du; Shunan Li; Jianhua Wu; Qingwen Liu; Zibo Zhao (International Journal of Refrigeration, 2026)

Theoretical analysis of the enhancement effect of the combination of ultrasonic oscillation and atomization on the falling film absorption process of ammonia water and optimization of the combined parameters - Chuang Pan; Jinlei Li; Runfa Zhou; Shuhong Li; Yanjun Li; Jun Wu; Gui Li (International Journal of Refrigeration, 2026)

High-dispersion CeO2-promoted Ca-Ni composites for coupled CO2 capture and methane dry reforming: Improved cycle stability and reforming efficiency - Yanyuan Bai; Li Zou; Jian Jiao; Yutong Gao; Cong Wang; Yanjun Dai; Yungang Wang (Fuel, 2026)

Recent advances of techniques for mycotoxins analysis based on nanomaterials in food and herbal medicine: From design to applications - Ziyue Ni; Jingyu Zhao; Yanjun Nie; Zhibo Gai; Zhenhua Tian; Yunlun Li; Junhong Xin (Food Control, 2026)

Renewable, self-supporting bamboo-based composites for electromagnetic absorption and electrothermal management - Jiateng Chen; Yu Wang; Yanjun Li; Tiancheng Yuan (Environmental Research, 2026)

Viscosity-tunable polyvinyl alcohol/tannic acid supramolecular adhesive with ethanol as an intermolecular physical interaction modulator - Ninglu Zhang; Liangxian Liu; Yuyan Jiang; Haiyu Li; Na Wang; Ming Wei; Dexiu Min; Zhenqian Pang; Yanjun Xie; Jian Li; Shaoliang Xiao (Chemical Engineering Journal, 2026)

An eco-friendly Pickering emulsion gel loading white mustard essential oil for attract-and-kill control of Plutella xylostella larvae - Meng Xiao; Xirui Chen; Xiaoqin Zhao; Qiuxia Li; Chaoyi Peng; Xiaozhuo Chen; Yanjun Lin; Jingjing Li; Jinming Zhang (Chemical Engineering Journal, 2026)

Engineering Ni(0)/Ni(II) interfaces in LDH-Derived Ni–Al catalysts for mild lignin depolymerization - Yanjun Wen; Wenxuan Li; Dmitry I. Sharapa; Thomas A. Zevaco; Dieter Schild; Felix Studt; Klaus Raffelt; Nicolaus Dahmen (Bioresource Technology, 2026)

CSSL-based GWAS identifies SNPs and candidate genes associated with Verticillium wilt resistance in cotton - Youzhong Li; Xiaohui Jiang; Hongyu Cao; Xinyu Zhang; Zhongxu Lin; Qian-Hao Zhu; Yanjun Li; Fei Xue; Shuaishuai Cheng; Feng Liu; Jie Sun (Theoretical and Applied Genetics, 2026)

Microwave assisted alkali activated porous carbon from phenolic resin waste for high capacity methylene blue removal - Yanjun Yin; Mengjie Bai; Wenxu Wang; Xiaotian Zhao; Weide Yuan; Yongwei Li; Yuying Yan; Yujie Feng; Wenjie Zhu; Xinyu Wang; Zhihao Fang; Wei Zhang (Environmental Geochemistry and Health, 2026)

Unraveling shallow landslides in the Qinling Mountains: Novel insights into vegetation-hydrology driven mechanisms - Xing Chen; Yanjun Shen; Yibing Ning; Bailei Shi; Jinyu Zhu; Sirui Li; Zijian Li; You Lyu; Jianbing Peng (Journal of Mountain Science, 2026)

Upland Methane Sinks Under Climate Change: Global Patterns, Drivers and Trends - Li Cheng; Wensheng Xiao; Josep Peñuelas; Fei Li; Yanjun Liu; Philippe Ciais; Xiaoqi Zhou (Global Change Biology, 2026)
Well‐aerated upland soils serve as a crucial biological sink for atmospheric methane (CH 4 ), playing a key role in mitigating climate change. However, current understanding of how this CH 4 sink responds to global climate change remains limited. To address this, we integrated 1092 observational data points to construct a dataset covering multiple global change factors and used meta‐analysis to quantify the response mechanisms of the upland CH 4 sink. Results show that warming, reduced precipitation, and elevated carbon dioxide concentrations significantly strengthened the CH 4 sink, while increased precipitation and nitrogen addition weakened it. Interactive effects were also observed: low‐level nitrogen deposition acted antagonistically with increased precipitation, but synergistically with warming. We subsequently optimized a CH 4 oxidation model to explore the global distribution patterns and future trends under different climate scenarios. The current global upland soil CH 4 sink is estimated at approximately 37 Tg year −1 and generally shows an increasing temporal trend. Spatially, the sink exhibits heterogeneity: a greater extent of desert areas in the Northern Hemisphere leads to a lower CH 4 sink per unit area compared to the Southern Hemisphere. Future spatiotemporal trends of the soil CH 4 sink will depend on the climate pathway. Under the Shared Socioeconomic Pathway (SSP) 1–2.6 scenario, the CH 4 sink declines over time, whereas under SSP5‐8.5, it follows a unimodal trajectory. Variations in the soil CH 4 sink also differ across regions. These changes are primarily associated with atmospheric CH 4 concentrations under different climate pathways, as well as alterations in soil temperature and moisture resulting from various climate change drivers. These findings underscore the importance of the upland CH 4 sink in the global CH 4 cycle and significantly advance our understanding of its response mechanisms to climate change.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

A new method for efficient recovery of boron from boron-bearing iron concentrate: low-temperature fluidized selective reduction and magnetic separation - Jianwen Yu; Xuanxiong Kang; Peiyu Li; Xuesong Sun; Yanjun Li; Yuexin Han; Zhongxu Qi; Dayon Sun (Minerals Engineering, 2026)

Comprehensive utilization of Bayan Obo polymetallic ore: A review - Qiang Zhang; Yongsheng Sun; Yuexin Han; Yanjun Li; Peng Gao (Minerals Engineering, 2026)

Intermittent blue light-dark cycles: A new strategy for enhancing triterpenoid production in medicinal Sanghuangporus vaninii - Yanjun Ma; Rong Li; Jiahui Li; Zilu Song; Fawen She; Xiaoyan Ma; Xuetai Zhu (Journal of Photochemistry and Photobiology B: Biology, 2026)

Freeze-thaw differentially modulates the impact of agricultural film-derived microplastics on soil-crop system: Microbiome and metabolome responses - Yanjun Li; Jiayang Hu; Zhaojiang Liu; Yong Yu (Journal of Hazardous Materials, 2026)

Elucidating microplastic adsorption mechanisms in biomass composite materials through interpretable machine learning - Huiling Li; Yimin Shi; Junhao Liu; Zhichen Ba; Shengkai Liu; Birong Yan; Daxin Liang; Yanjun Xie (Journal of Hazardous Materials, 2026)

N2O and NO formation influenced by metal elements during coal pyrolysis and char combustion - Yanjun Zuo; Zhaoxin Wan; Haiyang Li; Ping Liu; Xiaoshuo Liu; Yingchuan Zhou; Zhi Han; Yufeng Duan (Fuel, 2026)

Enzyme and thermal induced transition of egg white proteins from dense-globular to random coil triggering uniform microparticle formation - Zhishuo Zhang; Yi Wang; Ruyi Zhang; Xuechun Wang; Junhua Li; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang (Food Research International, 2026)

Persistent luminescent nanoparticle-based immunochromatographic assay integrated with a smartphone device for simultaneous detection of aflatoxin B1 and T-2 toxin - Aimei Zhang; Mingzhu Liu; Jingran Sun; Zunquan Zhao; Yonghui Wang; Xiaoli Li; Jin Wu; Yanjun Fang; Pingping Zhang; Jialei Bai (Food Chemistry, 2026)

Novel composite essential oil nanoemulsion stabilized via a dual strategy of covalent chemical bonding and compositional synergy: Application to hairtail (Trichiurus lepturus) preservation - Meng Wang; Keming Zhang; Yanjun Wen; Yujin Li; Changhu Xue; Zihao Wei (Food Chemistry, 2026)

Facile synthesis of Fe3O4@wood-derived porous carbon with optimized impedance matching for enhanced microwave absorption performance - Jiateng Chen; Kaiwen Chen; Xinzhou Wang; Yu Wang; Yanjun Li; Tiancheng Yuan (Environmental Research, 2026)

Novel α-glucan phosphorylase coupled with thermotolerant yeast facilitated a high conversion rate from corn stover to artificial starch and microbial protein - Yanjun Li; Guoshun Xu; Jian Tian; Wangli Ji; Bo Liu; Tao Tu; Yuan Wang; Huoqing Huang; Huiying Luo; Bin Yao; Feifei Guan; Wei Zhang; et al. (Chemical Engineering Journal, 2026)

IL-4 in Alzheimer’s Disease—Mechanisms and Therapeutic Potential - Guangya Liu; Weixian Li; Jiangmin Chen; Shuyu Xu; Xinyuan Liu; Zijie Wang; Qihui Yang; Anqi Xie; Yanjun Du (Molecular Neurobiology, 2026)

Optimizing O3-UV process for wastewater advanced treatment with a novel mini-fluidic experimental system to minimize energy consumption: Chemical oxidation vs. advanced oxidation - Jinyu Shi; Zhimin Qiang; Yanjun Jiang; Yanyan Huang; Zhe Sun; Mohamed Gamal El-Din; Wentao Li; Mengkai Li (Water Research, 2025)

Biochar promoted soil organic carbon accumulation and aggregate stability by increasing the content of organic complex metal oxides in paddy soil - Jiajun Wu; Bin Zhou; Zichuan Li; Cheng Liu; Yan Li; Yulin Wang; Ning Zhao; Zhuozhe Wang; Yanjun Chai; Antonio Scopa; Marios Drosos; Vishnu D. Rajput; et al. (Soil and Tillage Research, 2025)

A novel compact magnetic quad-stable mechanism for efficiency improvement in point absorber wave energy converters - Xuening Song; Jian Qin; Zekai Wang; Fagang Bai; Lilei Li; Yanjun Liu; Gang Xue (Ocean Engineering, 2025)

Influence and optimization of hydrogen-based mineral phase transformation on grinding characteristics of polymetallic oxide and recovery of valuable elements by response surface methodology - Pengcheng Tian; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Minerals Engineering, 2025)

Sustainable and efficient barite recovery from low-grade tailings waste: A combined and innovative solution for resource utilization - Yuanxing Yue; Yongsheng Sun; Xiaolong Zhang; Jianping Jin; Yanjun Li (Minerals Engineering, 2025)

Thermal decomposition behavior of boron-bearing iron concentrate under nitrogen atmosphere: Kinetics, mineral phase transformation and microstructure evolution - Jianwen Yu; Xuanxiong Kang; Peiyu Li; Xuesong Sun; Yanjun Li; Yuexin Han; Zhongxu Qi; Dayon Sun (Minerals Engineering, 2025)

Formation of the Da'anhe reduced gold skarn in NE China: Evidence from U-Pb geochronology, and whole-rock and mineral geochemistry - Litian Zhang; Qihai Shu; Kai Xing; Fan Yu; Yanjun Wang; Zhonghai Zhao; Bing Li; Qingfei Wang; Jun Deng (Lithos, 2025)

Safe recycling of oxytetracycline fermentation residue by thermal pretreatment coupled with compost: Antibiotic degradation, resistance gene removal, nutrient release, and soil improvement - Guocheng Liu; Zhiying Li; Wenzhuo Xu; Lingyun Meng; Xicheng Yuan; Jinying Li; Xue Li; Qianwen Wang; Qinghua Yan; Shuaishuai Xin; Mengwei Xie; Yanling Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Mussel-inspired coating anchored polyquaternium functionalized nonwoven fabrics for microplastic adsorption - Yuanshuai Wan; Yanjun Jia; Yonggui Guo; Jianteng Sun; Maofeng Liang; Lichao Gao; Haidong Cao; Tiantian Liu; Hongxiang Zhao; Yuliang Pang; Yanwei Fu; Yu Zhao; et al. (Journal of Environmental Chemical Engineering, 2025)

Effects of apoptosis on quality changes of Larimichthys crocea postmortem storage with emphasis on cytochrome c-mediated lipid deterioration - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Research International, 2025)

Analysis on the difference of nutrient components of black wolfberry seed grown in different regions - Yichen Liu; Wenyuan Zhang; Yanjun Li; Ruhui Shen; Shuaibei Wang; Xue Wang; Jianjun Deng; Zhenzhen Xu; Haixia Yang (Food Research International, 2025)

Multi-perspective investigation of the effects and interaction mechanisms of three common dietary fiber on cassava starch properties - Guangjia Lv; Yihong Bao; Shuxia Dai; Yajuan Qin; Bo Li; Xuan Zhang; Dehai Li; Yanjun Zhang; Yutong Zhang (Food Chemistry, 2025)

Structural characterization of water-soluble pectin in NFC orange juice during cloud destabilization - Shiying Yang; Jian Xu; Siying Liu; Yujie Cheng; Fengjiao Cai; Yanjun Zhang; David Julian McClements; Peiyi Shen; Qian Li (Food Chemistry, 2025)

Egg yolk phospholipid peptide-dihydromyricetin nano-composites: Temperature-driven assembly and evaluation of stability and pharmacokinetics - Yingxin Wei; Jinping Zhang; Wenhui Feng; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

Exploring the potential impact of GPC-enriched egg yolk derivatives on cognitive vitality in aging brains: A preliminary study - Wen Yu; Qing Gao; Yanjun Yang; Cuihua Chang; Wei Hu; Yujie Su; Luping Gu; Junhua Li (Food Bioscience, 2025)

Shading-induced canopy cooling alleviates waterlogging damage during flowering by disrupting heat synergism in field-grown cotton - Yanjun Zhang; Yabin Yuan; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Comparative study of injectable and stimuli-responsive hydrogels reinforced with cellulose nanofibers and chitosan for controlled drug delivery - Yaoting Liang; Tong Luo; Feiyun Li; Jifu Wang; Yanjun Tang (Chemical Engineering Journal, 2025)

Se-doped MoS2/CoFe2O4/CNT heterostructures with enhanced electromagnetic wave absorption via structural optimization and phase engineering - Zhigang Wu; Jin Chen; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Chemical Engineering Journal, 2025)

Tannic acid-assisted construction of ZIF-8/cellulose nanofiber composite aerogels for efficient oil adsorption and oil/water separation - Wenting Huang; Yahui Tao; Ya Li; Tong Luo; Yanjun Tang (Carbohydrate Polymers, 2025)

How topographic and pedological factors affect vegetation responses to drought: a study from the Qinling Mountains, China - Chao Li; Zhao Jin; Chengcheng Jiang; Yanjun Shen; Rui Wang; Jianbing Peng (CATENA, 2025)

The Holocene stalagmite trace element and Sr isotope records from Central China and the inferred hydroclimate changes - Yuting Wu; Yanjun Cai; Fugui Xiao; Mei He; Shouyi Huang; Xiangkun Zhai; Ruoxin Li; Gang Xue; Hanying Li; Chunlei Zong; Hai Cheng (Chemical Geology, 2025)

Unveiling the hidden threat: heavy metal accumulation in crops and soil microbial dynamics in a teaching experimental farmland - Xue Gu; Xuegang Yu; Qing Li; Yanjun Mao; Zhiwei Zhou; Huan Hu; Rui Huang; Jiayu Zhou; Yuanyi Sun; Yancheng Li; Aijiang Yang (Plant and Soil, 2025)

Tyro3 upregulation is associated with muscle involvement in patients with idiopathic inflammatory myopathies - Huan Liu; Ying Ren; Qianwei Li; Yanjun Si; Yuehong Chen; Min Dong; Geng Yin; Qibing Xie (Immunologic Research, 2025)

Evaluation of the working performance of different digging shovels based on the maize root-soil complex model - Hailong Che; Hua Zhou; Zhengzhong Li; Xian Wang; Xianliang Wang; Zhongcai Wei; Yanjun Li; Yinping Zhang (Biosystems Engineering, 2025)

Chrysin enhances sunitinib sensitivity in renal cell carcinoma by inducing ferroptosis via targeting PI3K/Akt/GPX4 pathway - Zixuan Chen; Weiyuan Li; Boshen Jia; Guohuan Yin; Zongrun Sun; Yanjun Tong; Sheng Cheng; Min Liu (Toxicology and Applied Pharmacology, 2025)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

Integrating LCZ framework and ENVI-met simulation for multi-scale assessment of urban thermal characteristics and blue-green infrastructure performance - Zhixing Li; Yanjun Su; Rong Xia; Yujie Pan (Sustainable Cities and Society, 2025)

The soil organic carbon sequestration potential and formation efficiency of China’s temperate grasslands - Lu Yang; Ping Li; Yuntao Wu; Nairsag Jalaid; Weixing Liu; Xiaoqiang Liu; Ziyang Peng; Junsheng Huang; Xiaoxia Zhao; Lubing Jiang; Zhaoyu Peng; Sen Yang; et al. (Science Bulletin, 2025)

Development and validation of 10 K liquid chip for Inner Mongolia cashmere goat - Qi Xu; Haijiao Xi; Dongmei Shen; Tao Zhang; Jinquan Li; Rui Su; Qi Lv; Yanjun Zhang; Ruijun Wang; Na Wang; Baichuan Liu; Dong He; et al. (Small Ruminant Research, 2025)

In situ probing and microstructural evolution mechanisms of hydrogen-derived manganosite (MnO) during oxidative cooling - Wu Zijian; Yuan Shuai; Zhu Feng; Gao Peng; Li Yanjun; He Jiahao (Minerals Engineering, 2025)

From iron concentrate to clean steel: A green short-process production technology centered on preparing high-purity iron concentrate - Wencheng Ge; Jie Liu; Tianjiao Chang; Yanjun Li; Yongsheng Sun; Shumin Zhang; Yuexin Han; Yimin Zhu (Minerals Engineering, 2025)

Sediment dredging effects on nitrogen and phosphorus release in a stratified reservoir: Implications for internal loading management - Yanjun Wu; Hongwei Wang; Zhu Bao; Yunchuang Li; Xiaokang Hu; Chuanzhe Sun; Fanyan Yang; Baoquan Li; Shanshan Liu; Yuyi Wang; Jicheng Zhong (Journal of Environmental Management, 2025)

Assessing the effect of composted cyclosporin A fermentation residue as organic fertilizer: Focus on soil fertility and antibiotic resistance - Dong Wang; Xiang Chen; Xiaofen Li; Qingwen Zhang; Jiaqi Hou; Yuefei Li; Beidou Xi; Zhihao Sun; Shuaishuai Xin; Guocheng Liu; Huiling Liu; Yanjun Xin (Journal of Environmental Sciences, 2025)

Emergence and genomic characterization of Vibrio parahaemolyticus serotype O10:K4 from seafood-linked diarrheal cases in Zhejiang, China (2016–2023) - Jiewen Huang; Zhen Zhang; Qingtian Li; Jiancai Chen; Lingling Mei; Xiaojuan Qi; Lili Chen; Junyan Zhang; Chao Lv; Min Li; Honghu Chen; Yanjun Zhang; et al. (Food Research International, 2025)

Correlation between multi-scale structure and log-of-slope digestive kinetics of a novel slowly digestible starch: Self-assembled chempedak seed amylopectin ternary complex - Bo Li; Xin Yang; Yuan Zhao; Chunguang Yao; Chongxing Huang; Shuangfei Wang; Debao Niu; Lehe Tan; Yanjun Zhang; Yutong Zhang (Food Research International, 2025)

Polybutylene succinate/fractionated nano lignin@Ag composite films with tunable functions for active food packaging - Shiqi Qin; Zelong Li; Jianpeng Huang; Zhipeng Hu; Wei Liu; Yanjun Xie; Qingwen Wang; Zhijun Zhang (Food Chemistry, 2025)

Effect of egg yolk component and its enzymatic hydrolysate on the flavor and texture of walnut cake - Tingting Tang; Qing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Chemistry, 2025)

Effects of enzyme treatment on structural characteristics of egg yolk, plasma and granule and their correlation with flavor components - Tingting Tang; Wen Yu; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2025)

Light-hormone crosstalk modulates vegetative branching and yield stability in dual-planting cotton systems - Jingyuan Zhou; Ziqing Hua; Yanjun Zhang; Zhenhuai Li; Shizhen Xu; Xiaoli Tian; Hezhong Dong; Zhaohu Li (Field Crops Research, 2025)

Controllable mesoporous wrinkling design realizes interfacial charge engineering in hierarchical MBene/MoS2 heterostructures for enhanced microwave absorption - Yiming Wang; Jin Chen; Bo Li; Meidan Que; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Chemical Engineering Journal, 2025)

Facilitating carrier kinetics in dual S-Scheme heterojunctions through interface regulating strategy for H2O2 generation and nizatidine degradation - Sheng Liu; Yanjun Zhang; Jun Du; Yuan Xue; Cheng Huang; Zushun Xu; Peng Wang; Zhengrong Wei; Zhanhui Yuan; Guangfu Liao; Qing Li (Chemical Engineering Journal, 2025)

Global sustainable pathway for lithium metal production: A critical review and best practice guide - Ruichen Wang; Yuexin Han; Yanjun Li; Feilong Zhang; Chunge Dang; Zhiguo Yuan; Jie Liu (Chemical Engineering Journal, 2025)

CFD simulation of multifluid mixing and structure optimization of rotating liquid film reactor for magnesium hydroxide production - Wenwen Lin; Jiahao Wan; Yingying Zhang; Wenyan Liu; Kaitao Li; Xiongzhong Yan; Jicang Li; Shengting Li; Wendi Liu; Yanjun Lin (Chemical Engineering Journal, 2025)

In-situ pH regulation of biomass-based hydrogel composite: A green approach to efficient lithium ion capture from salt lake brine - Shengkai Liu; Chunling Cao; Huiling Li; Wenxuan Wang; Birong Yan; Junreng Liu; Wei Wang; Tai Peng; Daxin Liang; Yanjun Xie (Chemical Engineering Journal, 2025)

Chlorination volatilization mechanism for decoupling phosphorus from lead and chromium during sludge incineration - Aijia Zhang; Jing Liu; Yingju Yang; Yanjun Hu; Rundong Li (Chemical Engineering Journal, 2025)

Synergistic defense mechanisms between soybean disease resistance genes and stomatal regulation - Jikai Li; Yanjun Li; Chunmei Luo; Shubo Zhou; Jemaa Essemine; Weibo Han; Mingnan Qu (Euphytica, 2025)

The use of predictive, preventive, and personalized medical approaches to optimize hypertension management - Ousman Bajinka; Lamarana Jallow; Yanjun Zhang; Xiaoxia Feng; Xianquan Zhan; Na Li (EPMA Journal, 2025)

Effects of rice straw biochar application rates on soil aggregate biogeochemistry and linkages to microbial community structure and enzyme activities - Jiajun Wu; Zichuan Li; Yong Li; Jiawen Liu; Cheng Liu; Yanjun Chai; Chao Ai; Qaiser Hussain; Marios Drosos; Shengdao Shan (Soil and Tillage Research, 2025)

Enhanced hydrogen-based reduction of hematite by bastnaesite: Kinetics and microstructural evolution mechanisms - Lingbo Zhao; Peng Gao; Bing Zhao; Zhenyue Zhang; Xiangyan Kong; Yuexin Han; Yanjun Li (Minerals Engineering, 2025)

Multidimensional characterization of microplastic pollution in subtropical urban soils: Combining geospatial analysis and polymer risk indexing - Aolei Du; Yanjun Li; Qiying Jian; Kai Zhang; Yutang Luo; Jun Yan; Peixin Du; Deborah M. Power; Ying Li; Yibing Ma (Journal of Hazardous Materials, 2025)

Agricultural films derived microplastics intensify acetochlor toxicity on soil health - Zhaojiang Liu; Jiayang Hu; Yanjun Li; Yong Yu (Journal of Hazardous Materials, 2025)

WB-assisted activation of periodate by Fe(III) for decontamination: Periodate concentration-dependent mechanistic shift - Yulu Xu; Yu Mei; Yanjun Li; Chenye Fu; Yuantai Li; Yuheng Zhong; Junxi Song; Gang Yang; Shihuai Deng; Xiaohui Lu; Jiali Peng; Bo Lai (Journal of Hazardous Materials, 2025)

Spatiotemporal diversification enables sustainable cotton-soybean production with enhanced yield and reduced emissions - Qingqing Lv; Ning He; Baojie Chi; Shizhen Xu; Zhenhuai Li; Li Wang; Yanjun Zhang; Dongmei Zhang; Zhengpeng Cui; Jianlong Dai; Junjun Nie; Yongjiang Zhang; et al. (Journal of Cleaner Production, 2025)

Metal organic frameworks (MOFs) synthesis and their use as a loading agent in oxidative stress-based diseases - Muhammad Saqib Saif; Sana Batool; Yusra Majeed; Asadullah; Tuba Tariq; Li Haitao; Yanjun Duan; Ghazala Mustafa; Murtaza Hasan (Journal of Environmental Chemical Engineering, 2025)

Efficient flotation of surface reconstructed hemimorphite subjected to fluidization sulfidation roasting - Yuangan Chen; Yongsheng Sun; Peng Gao; Yanjun Li (Journal of Environmental Chemical Engineering, 2025)

Engineering of Foeniculum vulgare with material science: La2O3-CeO2-CuO nanocomposites to revolutionize photocatalysis and antimicrobial challenges - Sana Batool; Iftikhar Ahmed; Calvyn Howells; Muhammad Saqib Saif; Tuba Tariq; Muhammad Waqas; Li Haitao; Yanjun Duan; Mumtaz Hussain; Mansour Ghorbanpour; Ghazala Mustafa; Murtaza Hasan (Journal of Environmental Chemical Engineering, 2025)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

Sunlight-driven hydrogen peroxide activation via copper hydroxyphosphate with broad spectrum response for imidacloprid degradation: Mechanism insight and DFT calculation - Haoran Zhang; Jiang Li; Yujiao Liu; Sihao Fu; Tianjie Su; Lingyu Meng; Yunfei Wang; Nian Ma; Guocheng Liu; Qinghua Yan; Yanjun Xin; Shuaishuai Xin (Chemical Engineering Journal, 2025)

Biocasting bioorthogonal gelatin with expanded primary hepatocytes to engineer therapeutic liver grafts for acute liver failure - Siqi Li; Tiemei Zheng; Yusen Li; Xiaoli Wang; Yanjun Jiang; Pengyu Huang (Chemical Engineering Journal, 2025)

Pulled GA signal orchestration proteome reconfiguration and redundancy cycling via PtGA2ox10-mediated metabolic gatekeeping in Chinese pine seeds - Xinxiu Zuo; Shuai Liu; Yanjun Li; Yanyan Zhang; Duxian Lu; Shihui Niu; Xiaojuan Li; Jinxing Lin; Yaning Cui (Plant Cell Reports, 2025)

Effects of Dish-Shaped Buoy and Perforated Damping Plate on Power Absorption in Floating Two-Body Wave Energy Converters - Lilei Li; Changdong Wei; Mingchen Li; Xuening Song; Yanjun Liu; Gang Xue (Journal of Marine Science and Engineering, 2025)
Floating two-body wave energy converters (WECs) exhibit advantages, including insensitivity to water depth and tidal range, along with adaptability to multi-level sea states. However, WECs suffer from drawbacks, including unstable power generation and low wave energy capture efficiency. To enhance the hydrodynamic performance and energy capture efficiency, a dish-shaped buoy and perforated damping plate configuration was designed based on conventional two-body WECs. First, four two-body WECs were developed according to these configurations. Second, a numerical model based on potential flow theory and the boundary element method (BEM) was established, with its accuracy validated through sea trials. Finally, the frequency domain response, motion response, mooring tension and power absorption effect of the WECs under wave excitation of grades 3, 4 and 5 were analyzed. The results demonstrate that both the dish-shaped buoy and perforated damping plate significantly improve the device stability and energy capture potential. Regarding the motion response, both configurations reduced the peak response amplitudes in heave and roll, enhancing the device stability. For mooring tension, both configurations reduced the mooring line tension. For power absorption, the perforated damping plate effectively increased the energy capture efficiency, while the dish-shaped buoy also demonstrated superior performance under higher-energy wave conditions. Overall, this study provides a theoretical foundation and design guidance for floating two-body WECs.

OSNet: an oriented instance segmentation network of breeding plot extraction from UAV RGB imagery - Ruinan Zhang; Yuanhao Zhang; Shichao Jin; Jingrong Zang; Ruofan Zhao; Jiaqi Yao; Shaochen Li; Qing Li; Yanjun Su; Jin Wu; Qinghua Guo; Yanfeng Ding; et al. (Computers and Electronics in Agriculture, 2025)

Strategy to kill two birds with one stone: Contribution of hydrogen-based mineral phase transformation on enhancing the grinding and flotation characteristics of bastnaesite and fluorite - Pengcheng Tian; Jian Zhang; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Process Safety and Environmental Protection, 2025)

Electric field distribution and selective liberation in magnetite quartzite under high voltage pulse discharge - Yonghong Qin; Ziyu Yang; Yuexin Han; Peng Gao; Yanjun Li; Ningyu Zhang (Minerals Engineering, 2025)

Enhanced pre-selection of spodumene via ultraviolet-induced fluorescence and improved YOLOv8 deep learning algorithm - Tianyou Yu; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Minerals Engineering, 2025)

Mechanistic insights into plasmon-mediated charge transfer in Pt@BiOBr/g-C3N4 S-scheme heterojunction for solar-driven water treatment - Jin Chen; Ke Li; Jie Yan; Suqing Qin; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Journal of Water Process Engineering, 2025)

Seasonal freeze-thaw CO2 sink 'midday rest' phenomenon in lakes: A case study of the largest freshwater lake in the Yellow River Basin - Yue Sun; Xiaohong Shi; Ruli Kang; Zhaoxia Yang; Shengnan Zhao; Guohua Li; Yanjun Wang; Jussi Huotari (Journal of Hydrology, 2025)

Mobilization of water-dispersible colloidal chromium and nickel in basalt-derived paddy soils: Role of Fe (hydr)oxides and organic matter - Ting Liu; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Zhuobiao Ni; Qingqi Lin; Rongliang Qiu (Journal of Hazardous Materials, 2025)

Identifying nitrate pollution of groundwater based on aquifer vulnerability and surface nitrogen loads in the Northern Foot of the Qinling Mountains, China - Yixin Liu; Hui Qian; Yanyan Gao; Siqi Li; Xiaoxin Shi; Zhiming Cao; Qi Long; Yi He; Yandong Ma; Puxia Wu; Yanjun Shen (Journal of Hazardous Materials, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Carbon footprint and environmental impact of reconstituted bamboo material based on life cycle assessment - Jingwen Chen; Yan Ma; Xiaomei Zhang; Nina Yan; Yanjun Li; Lei Xu; Zhichao Lou (Journal of Cleaner Production, 2025)

Effect of ultrasonic oscillation combined with atomization on enhancing ammonia-water falling film process and performance of absorption refrigeration system - Chuang Pan; Jinlei Li; Runfa Zhou; Shuhong Li; Yanjun Li; Jun Wu; Gui Li (International Journal of Refrigeration, 2025)

STANet-TLA: leveraging deep learning and prior knowledge for large-scale soybean breeding plot segmentation and high-yielding variety screening from UAV time-series data - Shaochen Li; Yinmeng Song; Ke Wang; Yiqiang Liu; Junhong Xian; Hongshan Wu; Xintong Zhang; Yanjun Su; Jin Wu; Qinghua Guo; Shan Xu; Dong Jiang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

The effect and mechanism analysis of calcium and magnesium between the blank roasting-leaching process of vanadium shale - Jianping Jin; Xiaolong Yu; Zhe Bai; Zhenya Zhou; Yuexin Han; Yanjun Li (Fuel, 2025)

The gastrointestinal digestion fates and postprandial plasma fatty acid profiles of four dietary lipids with different unsaturated levels: A comparative study using Sprague-Dawley rats - Yanjun Guo; Zhan Ye; Yanjun Liu; Jiaying Yan; Rui Li; Yanan Wang; Yuanfa Liu (Food Bioscience, 2025)

Multifunctional solar evaporation device integrating the advantages of azo COF and sunflower stalk for efficient pure water production and inactivation of pathogenic microorganisms in the residue - Jiayi Wang; Chenyu Li; Xuejia Chang; Yanfei Liu; Nurimangul Muntiza; Futai Lu; Yanjun Yu; Qiliang Deng (Chemical Engineering Journal, 2025)

MOF-based hypocrellin composite nanomaterials as advanced plant-derived photosensitizers for multimodal therapy - Ying'’ao Wu; Yanjun Guo; Kaijie Feng; Miao Li; Hongxue Li; Jiasheng Wu; Pengfei Wang; Rungong Yang; Xiao He; Xiong Yin; Min Li (Chemical Engineering Journal, 2025)

Unlocking the potential of cotton-derived carbon aerogel for uranium extraction from real radioactive wastewater: A path to amidoxime and polyguanidine modification - Yang Wang; Yun Wang; Qi Ren; Zihao Feng; Yang Li; Yanjun Du; Xiaoyan Li; Yan Liu; Dingzhong Yuan; Tu Lan (Chemical Engineering Journal, 2025)

Risk factors for severe lower respiratory tract infection among children under 5 years of age hospitalized with respiratory syncytial virus - Yanjun Wang; Yuanxuan Xiang; Ruohong Jin; Bin Li; Xingxing Feng; Qian Han; Xishu Deng; Yunfang Lu; Chengyan Zhang; Shufang Xiao (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Evaluating carbon footprint calculators: a comprehensive assessment framework - Ziqian Xia; Kuang Liu; Jiangnan Li; Yanjun Gu; Bo Hu; Yun Zhong; Jinquan Ye; Ka Leung Lam (Clean Technologies and Environmental Policy, 2025)

The interaction between mycorrhiza and phoD-harbouring bacteria influencing soil available phosphorus in Pinus massoniana plantations - Lifen Li; Yueming Liang; Qiang Li; Fujing Pan; Zhangqi Yang; Yanlan Wei; Yijing Li; Yanjun Chen; Hanlian Qin; Guangping Xu (Applied Soil Ecology, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Optimization of discharge parameters for high-voltage pulse crushing technology − A review - Bo Zhang; Rui Han; Peng Gao; Shuai Yuan; Yanjun Li; Honghao Zhang (Minerals Engineering, 2025)

Desulfurization, desilication, and the separation and recovery of iron from bauxite: A review - Qinglong Fan; Shuai Yuan; Rui Han; Yanjun Li; Jiahao He; Xiaobin Ning (Minerals Engineering, 2025)

The impact of microplastics and nanoplastics on biological nitrogen removal processes: Exacerbating the greenhouse effect - Yuliang Zhu; Ben Ma; Dong Li; Tongshuai Liu; Yanjun Zhu; Huiping Zeng; Jie Zhang (Journal of Hazardous Materials, 2025)

Insights to enhanced coagulation based on the control of metal forms for treating acid mine drainage: Performance and mechanisms - Kun Wu; Yanjun Jia; Dandan Song; Angzhen Li; Xue Bai; Xuan Sun; Rongle Li; Zhihua Li (Journal of Hazardous Materials, 2025)

Mitigating waterlogging-induced yield loss in cotton through removal of early fruits: Agronomic and physiological mechanisms - Yanjun Zhang; Shen Qiu; Tiantian Liang; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Geopolymers prepared from industrial solid waste: Comprehensive properties and application prospects - Wenxing Chen; Huanyi Zhu; Yongmei Li; Fang Liu; Qing Li; Yanjun Mao; Aijiang Yang (Environmental Research, 2025)

Earthworm survival adaptations to arsenate exposure: Links between behavioral inhibition, mitochondrial dysfunction, and oxidative stress responses - Yunxiang Xu; Songge Deng; Yanjun Shen; Muyuan Wang; Yifan Zhang; Yizhao Wu; Qi Zhao; Jibao Jiang; Xianqing Zheng; Weiguang Lv; Yinsheng Li (Environmental Pollution, 2025)

Inspiring the potential of graphene oxide aerogel for uranium(VI) electrosorption: A precursor reconfiguration strategy and synergistic integration with polyethyleneimine - Qi Ren; Yun Wang; Yang Wang; Zihao Feng; Yanjun Du; Changfu Wang; Yan Liu; Dingzhong Yuan; Hao Jiang; Yang Li (Desalination, 2025)

Synergistic nano-bioeffects: Dual impact of bisphenol-derived carbon dots on environmental health and antimicrobial therapy - Siyuan Hu; Xinzhong Zhang; Jiayu Li; Xiang Wang; Chen Gao; Jiatong Zhou; Jing Cai; Miaomiao Yin; Rufang Zhao; Xin Ding; Wei Hong; Yanjun Hu (Chemical Engineering Journal, 2025)

Cu@SnO₂/rGO to Cu@Sn/rGO transition: A strategy for tuning plasmon resonance and Schottky junctions in excellent microwave absorbers - Yanjun Jiang; Shuai Lv; Tiantian Li; Xinyu Wang; Pianpian Zhang; Dongdong Lv; Yanan Yang; Xin Wu; Xiaoxiao Huang; Long Xia (Chemical Engineering Journal, 2025)

Effects of methoxy groups and carbon–carbon double bonds in phenolic acids on the physicochemical characteristics and digestibility of cassava starch - Guangjia Lv; Dehai Li; Yihong Bao; Yajuan Qin; Xuan Zhang; Fei Xu; Kexue Zhu; Yutong Zhang; Yanjun Zhang (Carbohydrate Polymers, 2025)

Economic model predictive control for an office building with photovoltaic, heat pump, thermal storage and electric vehicle under time-of-use tariff - Ruimiao Liu; Zhongbing Liu; Yanjun Leng; Benjia Li; Yaling Wu (Building and Environment, 2025)

Coupled mutual feedback and interaction mechanisms among the geological environment, ecological environment and human activities in the Qinling Mountains - Chao Li; Zhao Jin; Chengcheng Jiang; Yanjun Shen; Rui Wang; Jianbing Peng (Science China Earth Sciences, 2025)

Divergent Flowering Time Responses to Increasing Temperatures Are Associated With Transcriptome Plasticity and Epigenetic Modification Differences at FLC Promoter Region of Arabidopsis thaliana - Yu Han; Li Liu; Mengyu Lei; Wei Liu; Huan Si; Yan Ji; Qiao Du; Mingjia Zhu; Wenjia Zhang; Yifei Dai; Jianquan Liu; Yanjun Zan (Molecular Ecology, 2025)
Understanding the genetic, and transcriptomic changes that drive the phenotypic plasticity of fitness traits is a central question in evolutionary biology. In this study, we utilised 152 natural Swedish Arabidopsis thaliana accessions with re‐sequenced genomes, transcriptomes and methylomes and measured flowering times (FTs) under two temperature conditions (10°C and 16°C) to address this question. We revealed that the northern accessions exhibited advanced flowering in response to decreased temperature, whereas the southern accessions delayed their flowering, indicating a divergent flowering response. This contrast in flowering responses was associated with the isothermality of their native ranges, which potentially enables the northern accessions to complete their life cycle more rapidly in years with shorter growth seasons. At the transcriptome level, we observed extensive rewiring of gene co‐expression networks, with the expression of 25 core genes being associated with the mean FT and its plastic variation. Notably, variations in FLC expression sensitivity between northern and southern accessions were found to be associated with the divergence FT response. Further analysis suggests that FLC expression sensitivity is associated with differences in CG, CHG and CHH methylation at the promoter region. Overall, our study revealed the association between transcriptome plasticity and flowering time plasticity among different accessions, providing evidence for its relevance in ecological adaptation. These findings offer deeper insights into the genetics of rapid responses to environmental changes and ecological adaptation.

Simultaneously enhance nutrient removal and sludge settleability through hydrocyclone-based technology in a full-scale high-inert containing activated sludge process - Yanjun Shao; Sisi Chen; Xiang Tao; Weilan Yang; Tao Liu; Binzheng Wang; Yan Wang; Shuo Wang; Dongdong Xu; Jianhua Guo; Ji Li (Water Research, 2025)

On the propagation arrest and crossover behavior of pipe bends under external overpressure - Zhenmian Li; Xiangyang Wang; Yanjun Wang; Mingze Huang; Yang Yu; Yaqian Zhao (Ocean Engineering, 2025)

Hydrogen-based fluidization direct reduction of high purity iron concentrate: Experimental optimization and mechanism analysis - Tingbo Zhou; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2025)

Renewable bamboo-based composites for electromagnetic and thermal applications - Xiaolong Li; Haonan Ding; Yu Wang; Jinhai Guo; Yanjun Li; Tiancheng Yuan (Journal of Cleaner Production, 2025)

Fabrication of TiO2/CuFeO2 composites for oxytetracycline degradation through heterogeneous photo-Fenton-like process under visible light - Xue Li; Jinying Li; Jiaying Song; Zhiying Li; Xicheng Yuan; Lingyun Meng; Wenzhuo Xu; Qianwen Wang; Qinghua Yan; Shuaishuai Xin; Chengzhi Zhou; Guocheng Liu; et al. (Journal of Environmental Management, 2025)

Cysteine and dialysis mediated inhibition of dynamic changes in glycosylated egg white protein during storage - Lulu Guo; Wanqiu Zhang; Fan Zhang; Shende Hu; Qianwen Zhao; Cuihua Chang; Junhua Li; Zijian Huang; Luping Gu; Yanjun Yang; Yujie Su (Food Chemistry, 2025)

Preparation of macroporous Cu-SSZ-13-supported MOx catalysts and their catalytic performance for the simultaneous removal of soot and NOx - Lanyi Wang; Yanjun Chen; Shiwei Wang; Xinyu Chen; Shengran Zhou; Jiahong Li; Di Yu; Chunlei Zhang; Siyu Gao; Xuehua Yu; Chengyang Yin; Xiaoqiang Fan; et al. (Chemical Engineering Journal, 2025)

Impact of anti-solvents on the characteristics of hemicellulose fractionated from bleached bamboo pulp using lithium bromide hydrates - Xuejing Yu; Runzhu Gong; Meiyan Wu; Yufa Gao; Qian Li; Fang Zhang; Mehdi Rahmaninia; Bin Li; Yanjun Tang (Carbohydrate Polymers, 2025)

GPS flex power detection leveraging XGBoost machine learning based on LEO satellites - Yanjun Du; Yuanxi Yang; Xiaolin Jia; Wanqiang Yao; Qin Li (GPS Solutions, 2025)

Optimal design of marine nuclear power deaerator based on improved particle swarm optimization algorithm - Jiarui Zhao; Yanjun Li; Xu Chen; Yuan Fu; Baozhi Sun; Yuanwei Cao; Jianxin Shi (Annals of Nuclear Energy, 2025)

Corrigendum to “Complete biosynthesis of the potential medicine icaritin by engineered Saccharomyces cerevisiae and Escherichia coli” [Sci. Bull. 66(18) (2021) 1906–1916] - Pingping Wang; Chaojing Li; Xiaodong Li; Wenjun Huang; Yan Wang; Jiali Wang; Yanjun Zhang; Xiaoman Yang; Xing Yan; Ying Wang; Zhihua Zhou (Science Bulletin, 2025)

Effects of microplastics on black soil health: A global meta-analysis - Zhaojiang Liu; Yanjun Li; Guanghui Xu; Yong Yu (Journal of Hazardous Materials, 2025)

Signal-on aptasensors on paper-based platform: Application of multilayer MXene nanoquencher and stabilized luminescent carbon dots - Jincai Yang; Mingzhu Liu; Jin Wu; Tianyi Ma; Yanxuan Li; Yue Zhang; Jingran Sun; Xiaoli Li; Yanjun Fang; Yonghui Wang; Lingchao Cai; Yuan Peng; et al. (Journal of Hazardous Materials, 2025)

Decoding the effect of antibiotics on biofilm formation in biofilters - Sen Yang; Dong Li; Sibo Fu; Jifang Zheng; Yanjun Zhu; Hongpeng Li; Huiping Zeng; Jie Zhang (Journal of Environmental Management, 2025)

Organic substitution enhances soil quality, soil microbial community stability, foxtail millet productivity, and grain quality in North China - Mengen Nie; Xue Gao; Lijie Zhao; Genlan Han; Yanyan Duan; Ruihua Han; Shuqi Dong; Yongling Li; Huiling Du; Xiangyang Yuan; Yanjun Yang (Journal of Environmental Management, 2025)

Effect of adding different egg yolk oil on the flavor and physicochemical properties of mayonnaise - Xuejing Gao; Tingting Tang; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (Food Chemistry, 2025)

Production of glycerylphosphorylcholine-enriched defatted egg yolk powder through integrated enzymatic and supercritical CO2 processing - Wen Yu; Luping Gu; Cuihua Chang; Yujie Su; Yi Wang; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

Recent advances in heteroatom doping for performance optimization of inorganic metal-based lithium-ion adsorbents - Birong Yan; Shengkai Liu; Yimin Shi; Huiling Li; Xi Li; Yonggui Wang; Yabei Xu; Wei Wang; Tai Peng; Daxin Liang; Yanjun Xie (Desalination, 2025)

Preparation of temperature-dependent flux controllable cellulose nanofiber-based films and their application in oil-water separation - Feiyun Li; Jinxian Shan; Helin Li; Hongming Lou; Yanjun Tang (Carbohydrate Polymers, 2025)

Decoding the fate of antibiotic resistance genes in soil with the application of thermally treated gentamicin mycelial residues - Dong Wang; Qingwen Zhang; Zhihao Sun; Yuefei Li; Xiaomei Xie; Shuaishuai Xin; Guocheng Liu; Huiling Liu; Yanjun Xin (Bioresource Technology Reports, 2025)

The catalytic activity of Ca/Fe-rich incineration ash in the pyrolysis of epidemic wood - Yanjun Hu; Zhenxing Luo; Long Jiao; Caimeng Yu; Jian Li; Qianqian Guo; Jian Song (Waste Disposal & Sustainable Energy, 2025)

The performance of an embankment over soft clay under rainfall with tension cracks at soil-pile interface caused by lateral deformation - Xing Wei; Shitao Cheng; Yanjun Li; Rui Chen; Zijian Wang; Fan Tang; Bingkun Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Single-B-cell cloning and recombinant antibodies generation to analyze the antigenicity of porcine reproductive and respiratory syndrome virus nonstructural protein 12 - Hongyong Duan; Chaozhi Tang; Song Han; Nan Yang; Shumao Wang; Fei Gao; Yanjun Zhou; Guangzhi Tong; Kuan Zhao; Liwei Li (Veterinary Microbiology, 2025)

Millennial-scale climate variability of the Asian summer monsoon over the last 690,000 years: insights from cave records - Xiaowen Niu; Jian Wang; Le Kang; Youwei Li; Haiwei Zhang; Xiyu Dong; Hanying Li; Lijuan Sha; Liang Yi; Ashish Sinha; Youfeng Ning; Xue Jia; et al. (Science Bulletin, 2025)

Tectonic setting, paleoenvironment and REE source of the Lower Cambrian phosphorites, Yangtze Block (South China) - Chuan Guo; Yong Fu; Peng Xia; Zhen Yang; Yanjun Li; Zhongfei Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Piezo-promoted Fe3+/Fe2+ cycling in Bi4Ti3O12/α-FeOOH heterojunction for enhanced Fenton-like degradation of refractory organic pollutants: A sustainable strategy and mechanism insights - Wei Guo; Bingjie Yin; Chengjie Chen; Dingxun Ma; Shanshan Li; Guodong Zhang; Guangshan Zhang; Yanjun Xin; Qinghua Chen (Journal of Water Process Engineering, 2025)

The role of defatted hydrolyzed egg yolk powder in protecting DHA algal oil - Yingxin Wei; Huan Rui; Xuechun Wang; Cuihua Chang; Yi Wang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Chemistry, 2025)

Bonding of wood with high strength and excellent water resistant cellulose colloidal adhesives - Yuyan Jiang; Tian Ju; Liangxian Liu; Haiyu Li; Yue Zhang; Na Wang; Zetan Lu; Ming Wei; Dexiu Min; Yanjun Xie; Jian Li; Yonggui Wang; et al. (Chemical Engineering Journal, 2025)

Visible-light-driven biochar supported CuMnO2 activating hydrogen peroxide for chlortetracycline degradation through promoting photocarriers separation - Shuaishuai Xin; Yiyun Wang; Haoran Zhang; Jiang Li; Zhihai Liu; Jing Jiao; Guocheng Liu; Chengzhi Zhou; Qinghua Yan; Yanjun Xin (Chemical Engineering Journal, 2025)

Exploring the interaction between quorum sensing and sludge physical properties in Anammox systems - Yanjun Zhu; Dong Li; Sibo Fu; Hongpeng Li; Sen Yang; Songyue Li; Yuliang Zhu; Huiping Zeng; Jie Zhang (Bioresource Technology, 2025)

Physiological and transcriptomic responses of the microalga Isochrysis galbana during exposure to Hg(II) stress - Linlin Zhang; Na Li; Xinfeng Xiao; Linke Guo; Wenfang Li; Yanjun Li; Fei Ling (World Journal of Microbiology and Biotechnology, 2025)

Mechanism of rainfall-induced loess landslides revealed by multi-source data - HongYu Liu; YanJun Li; MingZhou Bai; Xu Gao; Ling Yang; ZiLun Zhang; MingHui Zuo; Qain Liu (Natural Hazards, 2025)

The Roles of DMT1 in Inflammatory and Degenerative Diseases - Haigang Liu; Mi Li; Yi Deng; Yanjun Hou; Liangcai Hou; Xiong Zhang; Zehang Zheng; Fengjing Guo; Kai Sun (Molecular Neurobiology, 2025)

Maternal-offspring brain and tissue cross-talk in preeclampsia: insights from a rat model - Xiaomin Xu; Haiyin Chen; Lidan Gao; Congcong Sun; Xiaoqing Li; Yanjun Li; Wenhuan Wang; Yanyan Zheng (Metabolic Brain Disease, 2025)

AGSPNet: A framework for parcel-scale crop fine-grained semantic change detection from UAV high-resolution imagery with agricultural geographic scene constraints - Yanjun Wang; Shaochun Li; Hengfan Cai; Lina Deng; Yunhao Lin (Computers and Electronics in Agriculture, 2025)

Adsorption of polycyclic aromatic hydrocarbons (PAHs) in soil and water on pyrochars: A review - Lishi Tang; Panpan Wang; Chengze Yu; Ning Jiang; Jiaqi Hou; Jun Cui; Shuaishuai Xin; Yanjun Xin; Mingxiao Li (Journal of Environmental Chemical Engineering, 2025)

Lactic acid/tartaric acid-maltitol antibacterial activity against spoilage bacteria and prevention of yellowing and wilting in spinach and oilseed rape - Dengyi Ye; Jing Ren; Yanan Zhang; Xiyu Wang; Jiali Guo; Bing Li; Quanliang Li; Yanjun Chen; Ping Chen; Biying Zhang (Food Chemistry, 2025)

Preparation of SCOF/UiO-66-NH2 immobilized laccase biocatalytic membrane for micropollutants removal from water - Tiantian Wang; Lingfeng Zhao; Guanhua Liu; Xiaoyang Yue; Xiaobing Zheng; Li Ma; Yunting Liu; Mimi Chen; Yanjun Jiang (Chemical Engineering Journal, 2025)

Light regulates seed dormancy through FHY3-mediated activation of ACC OXIDASE 1 in Arabidopsis - Yitong Liu; Shuangrong Liu; Yanjun Jing; Jialong Li; Rongcheng Lin (Plant Molecular Biology, 2025)

Towards new bioactive fluorine-containing 1,3,4-oxadiazole-amide derivatives: synthesis, antibacterial activity, molecular docking and molecular dynamics simulation study - Fei Xiong; Yanjun Zhang; Jinlong Jiao; Yiren Zhu; Tianlu Mo; Yeji Li (Molecular Diversity, 2025)

Numerical study of hybrid systems combining different WECs microarrays based on the TGL semi-submersible floating platform - Mingchen Li; Changdong Wei; Lilei Li; Zhenyu Yuan; Yanjun Liu; Gang Xue (Frontiers in Marine Science, 2025)
In this study, a novel wind-wave energy hybrid concept is proposed, consisting of a Three Gorges Leading semi-submersible floating wind turbine and multiple point absorption wave energy converters (WECs). Based on three-dimensional potential flow theory, numerical simulations are conducted using the hydrodynamic analysis software AQWA. The existing experimental data are used to validate the reliability of the numerical model by comparing and analyzing the hydrodynamic responses of the semi-submersible platform and WECs. Subsequently, the Y-shaped WECs microarray form and the Triangular WECs microarray form are designed based on the different connection methods between WECs and the turbine platform. Numerical simulation is conducted to study the influence of these WECs microarrays on the hybrid system’s performance. The results show that WECs microarray significantly affects the wave contours under short waves. Regarding platform motion stability, the Y-shaped microarray shows superior performance. Regarding mooring line tension, the hybrid system has an advantage under short waves. Regarding absorbed power, multi-body hydrodynamic interactions significantly enhance the WECs’ power absorption capacity. Overall, this study will contribute to the design of wind-wave energy hybrid systems.

Comparative analysis of chromatin accessibility in porcine oocytes from follicles of different sizes - Yazhuo Cheng; Jingyu Li; Jiyong Shang; Xilong Jia; Yeling Bi; Jiaxu Gu; Nan Jiang; Yanjun Huan; Youwei Li; Mingju Sun (Research in Veterinary Science, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Insights into relationship of oxidative potential of particles in the atmosphere and entering the human respiratory system with particle size, composition and source: A case study in a coastal area in Northern China - Ruiyu Li; Caiqing Yan; Yingze Tian; Yan Wu; Ruizhi Zhou; Qingpeng Meng; Li Fang; Yang Yue; Yanjun Yang; Haibiao Chen; Lingxiao Yang; Wei Jiang (Journal of Hazardous Materials, 2025)

Effects of mitochondrial lipidome alterations on quality deterioration of Larimichthys crocea postmortem storage: New insight from the perspective of mediating mitochondria-dependent apoptosis - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Optimizing geographical traceability models of Chinese Lycium barbarum: Investigating effects of region, cultivar, and harvest year on nutrients, bioactives, elements and stable isotope composition - Yanjun Ju; Hejiang Liu; Shuhui Niu; Lu Kang; Lei Ma; An Li; Yan Zhao; Yuwei Yuan; Duoyong Zhao (Food Chemistry, 2025)

Long-term diversified cropping promotes wheat yield and sustainability across contrasting climates: Evidence from China and Switzerland - Zhengjun Yan; Yi Xu; Juncong Chu; Thomas Guillaume; Luca Bragazza; Hongjun Li; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Achieving stable partial nitrification by exploiting lag phase of NOB recovery for selective washout - Dong Li; Luyao Teng; Kehuan Guo; Yanjun Zhu; Jie Zhang (Environmental Research, 2025)

Rational design of hierarchical porous structure of ZSM-22 for boosting high-efficiency selective hydrogenation of oleic acid to jet fuel - Zhentao Liu; Jinlin Mei; Xiaoyang Kong; Zikang Chen; Dong Li; Haidong Li; Chunya Wang; Yanjun Gong; Chunming Xu; Xilong Wang (Chemical Engineering Journal, 2025)

Design and properties of graphene film/polymer square-wave-like composites - Yanjun Xu; Shasha Wang; Xianxian Sun; Wenbo Han; Yibin Li (Chemical Engineering Journal, 2025)

BES-Designer: A Web Tool to Design Guide RNAs for Base Editing to Simplify Library - Qian Zhou; Qian Gao; Yujia Gao; Youhua Zhang; Yanjun Chen; Min Li; Pengcheng Wei; Zhenyu Yue (Interdisciplinary Sciences: Computational Life Sciences, 2025)

High-temperature treated oil-rich bedded rock layer and deterioration mechanism of heat transfer performance - Yanjun Shen; Ziyi Li; Cheng Peng; Jianshuai Hao (Bulletin of Engineering Geology and the Environment, 2025)

Passivity-Based Sliding Mode Control for the Robust Trajectory Tracking of Unmanned Surface Vessels Under External Disturbances and Model Uncertainty - Luke Ma; Siyi Pang; Yao He; Yongxin Wu; Yanjun Li; Weijun Zhou (Journal of Marine Science and Engineering, 2025)
This study uses a port-Hamiltonian framework to address trajectory tracking control for unmanned surface vessels (USVs) under unknown disturbances. A passivity-based sliding mode controller is designed, integrating adaptive disturbance estimation and an RBFNN-based uncertainty estimator. Stability is rigorously proven, and simulations confirm superior tracking performance, strong disturbance rejection, and accurate uncertainty estimation.

Utilization of cold-rolling oil sludge via iron ore sintering co-processing technology: A strategy for industrial-scale disposal of hazardous solid waste - Shengxuan Fan; Mengting Qin; Yong Chen; Jinchao Wei; Qian Li; Wenjie Ren; Ying Liu; Yi Wang; Yanjun Huang; Lei Zhang (Process Safety and Environmental Protection, 2025)

A clean and convenient way to utilize naturally air-dried bamboo tubes and increase their economic value - Tiancheng Yuan; Yuan Feng; Tao Zhang; Wenkai Zhu; Yu Wang; Xinzhou Wang; Yanjun Li (Journal of Cleaner Production, 2025)

Pilot-scale recovery of iron from refractory specularite ore using hydrogen-based mineral phase transformation technology: Process optimization, mineral characterization, and green production - Pengcheng Tian; Peng Gao; Mingxing Wang; Yanjun Li; Yuexin Han (Journal of Cleaner Production, 2025)

The catalytic mechanism for H2 production on MgO-CaO materials through the water gas shift reaction: A DFT study - Pengfei Zhao; Yanjun Wu; Chuanjiang Yang; Ke Wang; Peisheng Li; Edward J. Anthony; Cheng Fang (Gas Science and Engineering, 2025)

Multi-omics research reveals the genetic characteristics and acid resistance mechanism of Lactobacillus delbrueckii subsp. lactis DB-8 screening from Xizang fermented dairy - Yali Tan; Sidong Qin; Luoxi Sun; Zhixuan Wang; Xiao Li; Lingyan Liu; Hanjian Zhu; Qingyu Wang; Yanjun Cai; Mengxiang Gao (Food Bioscience, 2025)

Effect of enzymatic hydrolysis on flavor enhancement of yogurt fermented by lactic acid bacteria in egg white - Qing Gao; Ruolin Xu; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Bioscience, 2025)

Preserving wild edible plants using antibacterial and antibiofilm activities of Lactobacillus paracasei Z21 cell-free supernatant and thymol against Pseudomonas spp. - Xiyu Wang; Jiali Guo; Qi'ao Guo; Dengyi Ye; Quanliang Li; Yanjun Chen; Ping Chen; Biying Zhang (Food Bioscience, 2025)

Zonal gaming and overall enhancement of ecosystem services: A case from the compound area of mine-city and agriculture-forestry-grass in loess region, China - Shufei Wang; Yingui Cao; Shengpeng Li; Xiaoyang Liu; Jinxin He; Yanjun Guan; Zhongke Bai (Ecological Engineering, 2025)

Multifunctional all-liquid microfluidic devices stabilized with molecular brush surfactants - Zhao Zhang; Weixiao Feng; Kaijuan Li; Jiaqiu Luo; Yunhui Wen; Yang Yang; Yanjun Lin; Shaowei Shi (Chemical Engineering Journal, 2025)

PVA-enhanced green synthesis of CMC-based lithium adsorption films - Shengkai Liu; Huiling Li; Xi Li; Wei Wang; Chunguang Rong; Mengjie Yang; Yonggui Wang; Jing Wang; Yabei Xu; Daxin Liang; Yanjun Xie (Carbohydrate Polymers, 2025)

The interactive effect of extreme weather events and PM2.5 on respiratory health among the elderly: a case-crossover study in a high-altitude city - Zhenxu Ning; Yanjun Ma; Shuzhen He; Genshan Li; Ting Xiao; Chunguang Ma; Jing Wu (International Journal of Biometeorology, 2025)

Actinobacteria derived from soybean/corn intercropping influence the subsequent wheat - Songhe Chen; Ruirui Li; Bo Lv; Yanjun Li; Junda Li; Mengzhen Zhang; Xiaoxiao Ma; Cunhu Wang; Ruineng Xu; Yonghong Wang; Hong Liao; Yongjia Zhong (Agriculture, Ecosystems & Environment, 2025)

Emerging role of adaptive immunity in diabetes-induced cognitive impairment: from the periphery to the brain - Genhui Yang; Runtao Su; Jie Bu; Ying Li; Xueling Lin; Jiahui Jin; Yanjun Zhang; Pengwei Zhuang; Hong Guo; Qingsheng Yin (Metabolic Brain Disease, 2025)

Uncovering a cryptic Streptococcus suis endemic post-outbreak: Evidence of host switching to humans - Shuirong Zhu; Shengkai Li; Beibei Wu; Zhangnv Yang; Yuwen Zhang; Jiancai Chen; Yanjun Zhang; Lei Fang (Science of The Total Environment, 2025)

A sustainable process for Pb, Zn, and Fe from copper slag by salt roasting-magnetization roasting-magnetic separation - Xinze Gao; Yinhe Lin; Dong Guan; Zhaohua Liu; Bo Deng; Qingshan Du; Yanjun Liu; Sen Yu; Juncheng Li; Lingling Cao (Process Safety and Environmental Protection, 2025)

Numerical study of regular wave dynamics for optimizing coral reef restoration - Jiuming Han; Yanjun Li; Xizeng Zhao; Tao Liu; Yanzhen Gu; Shuangyan He; Peiliang Li; Ruili Sun (Ocean Engineering, 2025)

Iron-doped titanium lithium-ion Sieves@Sodium alginate-enhanced carboxymethyl cellulose aerogels: A synergistic leap in adsorption and sustainability - Shengkai Liu; Birong Yan; Yu Han; Wei Wang; Yimin Shi; Yonggui Wang; Huiling Li; Junhao Liu; Zefang Xiao; Daxin Liang; Yanjun Xie (Journal of Cleaner Production, 2025)

A new analysis of an application of low-carbon pre-selecting technology (LCPT) for minerals: An evolutionary game model among stakeholders - Tianyou Yu; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Journal of Cleaner Production, 2025)

Constructing of ultrahigh pH-responsive polycarboxylic copolymers for enhanced recycling cellulase from enzymatic hydrolyzate of corncob resides - Huinan Liang; Feiyun Li; Hongming Lou; Yanjun Tang (Fuel, 2025)

Reduction characteristics and mechanism of mechanically activated iron ore powder by lignin - Wangsheng Cheng; Yanjun Wang; Rufei Wei; Jiaxin Li; Hongming Long (Fuel, 2025)

Mechanisms by which Ganglioside GM1, a specific type of glycosphingolipid, ameliorates BMAA-induced neurotoxicity in early-life stage of zebrafish embryos - Yanjun Liu; Yuhe Zhu; Xiaoxu Wang; Yiyang Li; Shuaiqi Yang; Hongyan Li; Bo Dong; Zhigao Wang; Yu Song; Jie Xu; Changhu Xue (Food Research International, 2025)

Chronic high temperature exposure, brain structure, and mental health: Cross-sectional and prospective studies - Wenxin Xiang; Keyi Lyu; Yanjun Li; Bo Yin; Limei Ke; Qian Di (Environmental Research, 2025)

Rigid polymethacrylimide composites foam for efficient electromagnetic dissipation and infrared stealth - Zihang Zhang; Zixuan Wang; Yanjun Zhang; Peiyuan Zou; Mingyang Zhu; Shuangshuang Li; Xinwei Tang; Yezi Lu; Wei Li; Kaixin Lai; Wei Hong; Yufei Li; et al. (Chemical Engineering Journal, 2025)

Bypassing gas-liquid mass transfer resistance in a Fenton wet scrubber for boosting the removal of hydrophobic styrene: Construction of a novel gas-solid-liquid triple-phase interface - Zhiru Suo; Yuan Zhuang; Yanjun Zhao; Peng Zhou; Fushun Li; Binbin Huang; Chen Qu; Wenhui Li; Chuandong Wu; Jiemin Liu (Chemical Engineering Journal, 2025)

Biochar-supported MnFeO2 for heterogeneous photo-Fenton degradation of doxycycline: Collaborative promotion of electron transfer and H2O2 activation - Shuaishuai Xin; Yingchen Zhu; Yiyun Wang; Jiang Li; Haoran Zhang; Jing Jiao; Zhihai Liu; Qinghua Yan; Chengzhi Zhou; Guocheng Liu; Yanjun Xin (Chemical Engineering Journal, 2025)

Hierarchical carbon-incorporated boron nitride derived from protein flocculation for efficient oxidative dehydrogenation of propane - Dong Li; Yanjun Chen; Mengyao Sun; Wenwen Ma; Zean Xie; Lian Kong; Shuchong Bai; Zhen Zhao (Chemical Engineering Journal, 2025)

Durable and degradable adhesive-free wood straw via cell wall activation and self-bonding - Liangxian Liu; Guoqing Mu; Haiyu Li; Haozhou Huang; Yuyan Jiang; Yutong Chen; Ming Wei; Dexiu Min; Jian Li; Yanjun Xie; Zhenqian Pang; Shaoliang Xiao (Chemical Engineering Journal, 2025)

Deciphering the dead zone on anammox system in biofilters - Yanjun Zhu; Dong Li; Jie Zhang (Bioresource Technology, 2025)

Damage evolution characteristics of freeze–thaw rock combined with CT image and deep learning technology - Hui Liu; Xinyue Dai; Gengshe Yang; Yanjun Shen; Pengzhi Pan; Jiami Xi; Borong Li; Bo Liang; Yao Wei; Huiqi Huang (Bulletin of Engineering Geology and the Environment, 2025)

Sonothrombolysis Using Microfluidically Produced Microbubbles in a Murine Model of Deep Vein Thrombosis - Yanjun Xie; Yi Huang; Hugo C. S. Stevenson; Li Yin; Kaijie Zhang; Zain Husain Islam; William Aaron Marcum; Campbell Johnston; Nicholas Hoyt; Eric William Kent; Bowen Wang; John A. Hossack (Annals of Biomedical Engineering, 2025)
The need for safe and effective methods to manage deep vein thrombosis (DVT), given the risks associated with anticoagulants and thrombolytic agents, motivated research into innovative approaches to resolve blood clots. In response to this challenge, sonothrombolysis is being explored as a technique that combines microbubbles, ultrasound, and thrombolytic agents to facilitate the aggressive dissolution of thrombi. Prior studies have indicated that relatively large microbubbles accelerate the dissolution process, either in an in vitro or an arterial model. However, sonothrombolysis using large microbubbles must be evaluated in venous thromboembolism diseases, where blood flow velocity is not comparable. In this study, the efficacy of sonothrombolysis was validated in a murine model of pre-existing DVT. During therapy, microfluidically produced microbubbles of 18 μm diameter and recombinant tissue plasminogen activator (rt-PA) were administered through a tail vein catheter for 30 min, while ultrasound was applied to the abdominal region of the mice. Three-dimensional ultrasound scans were performed before and after therapy for quantification. The residual volume of the thrombi was 20% in animals post sonothrombolysis versus 52% without therapy ( $$p = 0.012 p = 0.012 0.05 ), indicating a significant reduction in DVT volume. Histological analysis of tissue sections confirmed a reduction in DVT volume post-therapy. Therefore, large microbubbles generated from a microfluidic device show promise in ultrasound-assisted therapy to address concerns related to venous thromboembolism.

Insights into the effects of environmental factors on phytoplankton and microzooplankton at a basin scale: diversity, assembly mechanisms, and co-occurrence networks - Yanjun Shen; Xinxin Zhou; Jiaming Zhang; Qinghua Li; Yufeng Zhang; Qing Zuo (Frontiers in Marine Science, 2024)
Mastering the characteristics of planktonic microbial communities under the influence of basin-scale environmental factors can provide scientific basis to develop more targeted protection and restoration measures. Here, an environmental DNA metabarcoding technology was applied to investigate the phytoplankton and microzooplankton simultaneously along the whole basin of Jialing River, one of the most important rivers in Southwest China with large scale altitude gradient and water temperature discrepancy. Along the river-way from upper to lower reach, an upward trend in richness of both phytoplankton and microzooplankton was observed with significant positive and negative correlations to water temperature and altitude (Spearman correlation, p < 0.05), respectively. Significant variations in their compositions along the river were also uncovered with Chrysophyta and Foraminifera was potential keystones recognized by the co-occurrence network analysis. Additionally, exponential distance-decay of similarities were detected for both phytoplankton and microzooplankton, which were stronger for phytoplankton. Based on the results of variation partitioning analysis and null model, variations in phytoplankton communities were more governed by environmental selection than those in microzooplankton. Furthermore, the co-occurrence network showed a declining trend in the complexity and stability from the upper to lower reaches. These findings could serve to establish a basis for the investigation of phytoplankton and microzooplankton communities in rivers with multiple artificial modifications.

Recent advances in biosynthesis mechanisms and yield enhancement strategies of erythritol - Wenli Yang; Xiangying Zhao; Mo Han; Yuchen Li; Yanjun Tian; Zhangbo Rong; Jiaxiang Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Assessment and prevention of combustion and explosion risk in underground space energy storage system: A review - Chenghao Qian; Xinxin Li; Yanjun Chen; Que Huang; Changcheng Liu (Tunnelling and Underground Space Technology, 2024)

Evaluating and locating a suitable bedrock drilling site near zhongshan station with airborne and ground-based observations - Yanjun Li; Xiangbin Cui; Gang Qiao; Lin Li; Shinan Lang (Polar Science, 2024)

Adaptation mechanisms and efficiency of anammox bacterial aggregates in various reactor systems during the start-up period - Yanjun Zhu; Dong Li; Sibo Fu; Hongpeng Li; Sen Yang; Jifang Zheng; Huiping Zeng; Jie Zhang (Journal of Water Process Engineering, 2024)

An evaluation method for synergistic effect of air pollutants and CO2 emission reduction in the Chinese petroleum refining technology - Dandan Liu; Xueying Li; Dong Wang; Hao Wu; Yanping Li; Yanjun Li; Qi Qiao; Zhou Yin (Journal of Environmental Management, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Analytical model of three-dimensional concentric ellipsoidal soil arching in geosynthetic-reinforced pile-supported embankments - Rong Sun; Xin Jiang; Lei Zhang; Canyang Cui; Zhengxian Li; Yanjun Qiu (Geotextiles and Geomembranes, 2024)

Characterization of liquid egg yolks hydrolyzed by phospholipase: Structure, thermal stability and emulsification properties - Ruolin Xu; Qing Gao; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Research International, 2024)

Extraction of egg yolk lipids via salt-induced synergistic heat treatment: Fabrication, characterization and flavor analysis - Xuejing Gao; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Chemistry, 2024)

LC-MRM-MS-based lipidomics reveals differences in the digestion, absorption, and metabolism of phosphatidylcholines from Egg, Soy, and Krill in vivo - Runfeng Du; Yanjun Liu; Zhan Ye; Jian Zhang; Cailing Li; Yuanfa Liu (Food Bioscience, 2024)

Effects of non-covalently bound polyphenols/vitamins on the structure and functional characteristics of egg yolk powder - Tingting Tang; Xuejing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2024)

Towards a high-rate operation of contact stabilization process: A microscopic view of carbon capture properties - Sibo Fu; Dong Li; Kunming Fu; Xiaohang Zhang; Yanjun Zhu; Sen Yang; Huiping Zeng; Jie Zhang (Environmental Research, 2024)

3D electric field coupling with Cu foam hydrogel: Achieving efficient and high-speed solar interfacial evaporation - Yanjun Chen; Huiyong Lan; Dongzhi Liu; Xiuliang Liu; Changzheng Li; Deqiang He (Chemical Engineering Journal, 2024)

Separation of Gold(I) from cyanide-containing wastewater by functional polymer inclusion membrane containing guanidinium ionic liquid - Guiping Zhu; Yanjun Chen; Yewei Qiu; Yuan Zhang; Feng Li; Fengzhi Jiang; Xiangjun Yang; Shixiong Wang (Chemical Engineering Journal, 2024)

Impact of urbanized atmosphere-land processing to the near-ground distribution of air pollution over Central Liaoning Urban Agglomeration - Wenxi Zhang; Zhenxin Liu; Xiaolan Li; Yuhao Mao; Yanjun Ma; Hong Liao (Atmospheric Environment, 2024)

Environmental DNA (eDNA) reveals the effects of cascade dam development on the distribution patterns of aquatic biodiversity in mountain rivers - Yanjun Shen; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Ruli Cheng (Frontiers in Marine Science, 2024)
The rich and special biodiversity in mountain rivers is experiencing a continuous decline due to the influence of climate change and anthropogenic factors. To explore the alterations in the distribution of aquatic biodiversity in mountain rivers in the context of cascade dam development, the environmental DNA (eDNA) metabarcoding technique was used to examine the aquatic biodiversity of the Wujiang River, a representative mountain river with an 11-stage cascade dam. In this study, a comprehensive analysis of aquatic organisms in the Wujiang River mainstem was conducted, and 17 phyla and 38 classes were detected in the 36 water samples. The most abundant group is the benthic organisms, and the least abundant group is the amphibians. The results of the diversity analysis showed a clear longitudinal distribution pattern of aquatic organisms along the altitudinal gradient, with higher richness of aquatic organism communities the further to the lower reaches. Meanwhile, RDA analysis revealed that altitude, dissolved oxygen, reservoir length, and reservoir construction time were the key environmental factors influencing the distribution of aquatic organisms in the Wujiang River mainstem. The findings of this research also showed the applicability of the eDNA method in detecting aquatic biodiversity.

Hydroxylamine-induced activation of permanganate for enhanced oxidation of sulfamethoxazole: Mechanism and products - Xiaohui Lu; Yanjun Li; Hongyu Zhou; Siyu Li; Wei Wei; Guochun Lv; Gang Yang; Shihuai Deng; Bo Lai; Jiali Peng (Science of The Total Environment, 2024)

Differential expression of TOR complex 1 components in Colletotrichum camelliae isolates confers natural resistance to rapamycin - Yuanye Zhu; Yanjun Li; Hong Liu; He Li (Pesticide Biochemistry and Physiology, 2024)

An Al2O3@ZnO membrane for oil-in-water emulsion separation with photocatalytic regeneration prepared via a simple deposition route - Chenggui Kuang; Yanjun Li; Donghua Liu; Yongfeng Li; Daofeng Sun; Jin Chen; Donghai Ding; Guoqing Xiao (Journal of Water Process Engineering, 2024)

Freeze-thaw aging increases the toxicity of microplastics to earthworms and enriches pollutant-degrading microbial genera - Yanjun Li; Guanghui Xu; Jian Wang; Yong Yu (Journal of Hazardous Materials, 2024)

Visible-light-driven photobiocatalytic synthesis of chiral sulfoxides over immobilized chloroperoxidase on magnetic yolk–shell Fe3O4@Cu-H-TiO2 photocatalyst - Xiaoyang Yue; Yuying Hou; Cuiyao Cao; Xue Cao; Haolei Song; Yanjun Jiang; Liya Zhou; Ying He; Xiaobing Zheng; Li Ma; Shijie Li (Journal of Cleaner Production, 2024)

Towards a high-rate operation of contact stabilization process: Challenges of flocculation and floc stability - Sibo Fu; Dong Li; Kunming Fu; Yanjun Zhu; Sen Yang; Xiaohang Zhang; Jie Zhang (Journal of Environmental Management, 2024)

Effect of cytochrome c release on the mitochondrial-dependent apoptosis and quality deterioration of black rockfish (Sebastes schlegelii) postmortem storage - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Chemistry, 2024)

Relationship between environmental evolution and human activities in the northeastern Qinghai-Xizang Plateau throughout the past millennium and its implications for the onset of the Anthropocene - Yang Pu; Xueqiong Wei; Jianbao Liu; Ke Zhang; Beibei Li; Zhudeng Wei; Mengmeng Zhang; Tong He; Yanjun Wang; Xiaohua Shao (Science China Earth Sciences, 2024)
In current research on the Anthropocene, assessing the impact of human activities via stratigraphic records of sediments and demarcating the Anthropocene epoch globally are critical scientific issues that urgently need to be addressed. The northeastern Qinghai-Xizang Plateau (QXP), where humans first settled permanently in large numbers in the QXP, has varying sedimentary environments that are extremely sensitive to human activities. In contrast to other regions of the QXP, the northeastern sector boasts a richer array of climatic and environmental reconstruction sequences. This distinctive feature renders it an exemplary locale for investigating the stratigraphic boundary of the Anthropocene. Through in-depth analysis and integration of existing paleoclimate and paleoenvironment sequences in the northeastern QXP, we draw the following conclusions: (1) Throughout the past millennium, the impact of human activities on the environment of the northeastern QXP has become increasingly significant, especially in the past 200–300 years, gradually overshadowing climatic factors. (2) Since AD 1950, multiple physicochemical indicators related to human activities in the northeastern QXP have shown exponential growth, forming a distinct peak within the past millennium and clearly depicting the global “Great Acceleration” phenomenon and its development process. (3) Intensified human activities have driven swift environmental shifts and “decoupled” the interplay between climatic variations and the ecological environment, propelling the northeastern QXP into the “Early Anthropocene” from the “Late Holocene”. On the basis of the above findings, we construct a model suitable for identifying the stratigraphic boundary of the Anthropocene in the northeastern QXP and note that since the ecological environment in the northeastern QXP has entered the “Early Anthropocene”, the climate signals of certain physicochemical indicators in sediments are gradually becoming weaker, whereas the signals of human activities are becoming stronger.

Establishment of a standardized daily behavior collection and analysis system for brain disease models of rhesus and cynomolgus monkeys and its application in autism spectrum disorder - Xiaofeng Ren; Huimin Wang; Xiaoman Lv; Yi Zhou; Yingyin Fan; Yanjun Yu; Christoph W. Turck; Yuhui Chen; Longbao Lv; Yingzhou Hu; Hao Li; Wenchao Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2024)
Complex brain diseases seriously endanger human health, and early diagnostic biomarkers and effective treatments are currently lacking. Due to ethical constraints on human research, establishing monkey models is crucial to address these issues. With the rapid development of technology, transgenic monkey models of a range of brain diseases, especially autism spectrum disorder (ASD), have been successfully established. However, to establish practical and effective brain disease models and subsequently apply them to disease mechanism and treatment studies, there is still a lack of a standard tool, i.e., a system for collecting and analyzing the daily behaviors of brain disease model monkeys. Therefore, with the goal of undertaking a comprehensive and quantitative study of behavioral phenotypes, we established a standard daily behavior collection and analysis system, including behavioral data collection protocols and a monkey daily behavior ethogram (MDBE) for rhesus and cynomolgus monkeys, which are the most commonly used non-human primates in model construction. Then, we used ASD as an application example after referring to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR), which is widely used in clinical disease diagnosis to obtain ASD core clinical symptoms. We then established a sub-ethogram (ASD monkey core behavior ethogram (MCBE-ASD)) specifically for quantitative assessment of the core clinical symptoms of an ASD monkey model based on MDBE. Subsequently, we demonstrated the high reproducibility of the system.

Study on the source identification and migration and transformation characteristics of heavy metal pollution in sediments of Chaohu Lake Tongyang River Basin - Zhenyu He; Yanjun Li; Bo Kang; Rui Li; Kun Chen; Jie Yang; Yuezan Tao (Environmental Monitoring and Assessment, 2024)

Selective depression of galena in the galena and chalcopyrite system by the Fe(II)-activated persulfate process - Qinbo Cao; Yan Yan; Heng Zou; Haiyu Zhang; Dianwen Liu; Shuming Wen; Yanjun Li (Minerals Engineering, 2024)

New insight into catalytic performance and reaction mechanism for butyl acetate over CeO2 catalysts: Oxygen vacancy and surface reactive oxygen species - Jiajia Lin; Wenjing Kong; Chuying Qiu; Xueyun Zhong; Yanjun Li; Mingli Fu; Zhenguo Li (Journal of Environmental Chemical Engineering, 2024)

Development of egg yolk lipoprotein hydrolysate for nano-delivery of curcumin: Structure-function relationship - Lili Jiang; Yanjun Yang; Yujie Su; Cuihua Chang; Luping Gu; Chunfang Liu; Junhua Li (Innovative Food Science & Emerging Technologies, 2024)

Hydrodesulfurization kinetic modeling of mixed Feedstocks: An approach using structure-oriented lumping for complex diesel oils - Mengfei Wang; Heping Yang; Xiaowei Bai; Zhenghua Dai; Yunpeng Zhao; Yanjun Hu; Jian Li (Fuel, 2024)

Advancing bioethanol production with a new kinetic model based on structure-oriented lumping for cellulose conversion - Heping Yang; Mengfei Wang; Xiaowei Bai; Zhenghua Dai; Yunpeng Zhao; Yanjun Hu; Jian Li (Fuel, 2024)

Anthropogenic activities have accelerated the restoration of carbon sequestration services in the upper Yellow River - Junyi Yang; Junsheng Li; Xiao Guan; Yanjun Chen; Zemin Zhang; Wenjie Li (Ecological Engineering, 2024)

Timescale dependent homogeneous assembly of lipid-polymer hybrid nanoparticles in laminar mixing for enhanced lung cancer treatment - ShiXin Li; Bing Yang; Liang Ye; ShuQi Hu; BenHong Li; Yanjun Yang; XiaoBin Jia; Liang Feng; ZhiWei Xiong (Chemical Engineering Journal, 2024)

R-Q@P-D nanoparticle for improving the oral bioavailability and therapeutic efficacy: A novel reversible dual-target-mild-inhibition intestinal metabolic enzymes strategy for resveratrol delivery - Qingchen Cui; Yanling Li; Liping Zhou; Zongtao Liu; Yanjun Wei; Weihao Dong; Xianggen Wu (Chemical Engineering Journal, 2024)

Parametric study of correlation of mainshock-aftershock ground motions based on Copula theory - Ziyan Wang; Xiaojun Li; Su Chen; Lei Fu; Bin Zhang; Xianwei Liu; Yanjun Zhu (Journal of Seismology, 2024)

Parameter calibration of the angle of repose of particle materials based on convolutional neural network - Sifang Long; Yanjun Zhang; Shuo Kang; Boliao Li; Jun Wang (Biosystems Engineering, 2024)

Chemical fertilizers promote dissemination of ARGs in maize rhizosphere: An overlooked risk revealed after 37-year traditional agriculture practice - Xiaolong Lin; Guanghui Xu; Yanjun Li; Yong Yu (Science of The Total Environment, 2024)

A novel selective collector MIBATC and its performance on flotation separation of chalcopyrite from sphalerite and pyrite - Xuesong Sun; Jianwen Yu; Yanjun Li; Yuexin Han; Peng Gao (Minerals Engineering, 2024)

Bamboo-inspired lightweight, mechanically-stable and vibration-damping structural members for engineering applications - Shanyu Han; Deyue Li; Fuming Chen; Mingqian Wang; Yubing Leng; Yanjun Li; Hanzhou Ye; Ge Wang (Engineering Structures, 2024)

Effectiveness of government subsidies for biomass-based industries: Incorporating the feedstock acquisition process - Jun Lin; Yanan Li; Yanjun Qian; Guoquan Liu (Energy Policy, 2024)

Highly efficient and secure recycling of neomycin fermentation residue by optimum temperature: Nutrients release, neomycin degradation and safety evaluation - Yuefei Li; Jiaqi Hou; Dong Wang; Junhao Ma; Weikai Sun; Mingxiao Li; Zhihao Sun; Yulin Liu; Guocheng Liu; Qinghua Yan; Qianwen Wang; Beidou Xi; et al. (Chemical Engineering Journal, 2024)

Molecular characteristics and phylogenetic definition on the complete chloroplast genome of Petrocodon longitubus - Zaiqi Luo; FengXia Yan; Ronghui Jiang; Yanjun Chen; Changsha Luo; CongRui Li (Plant Biotechnology Reports, 2024)

Effects of GPS flex power on DCBs, ionospheric delays and positioning - Yanjun Du; Yuanxi Yang; Xiaolin Jia; Yan Xiang; Wanqiang Yao; Ting Ma; Qin Li (Advances in Space Research, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

New insights of selective rupture of synthetic sample under high voltage pulse discharge: A numerical simulation of electric field distribution - Yonghong Qin; Ziyu Yang; Yuexin Han; Peng Gao; Yanjun Li; Ningyu Zhang; Jianming Gao (Minerals Engineering, 2024)

Investigation of high-risk antibiotic resistance bacteria and their associated antibiotic resistance genes in different agricultural soils with biogas slurry from China - Yi Lu; Junhui Wu; Jiwei Li; Zailin Du; Changai Zhang; Yanjun Chai; Zewen Jin; Zichuan Li; Jun Meng; Haifeng Zhuang; Lifeng Ping; Ming Hung Wong; et al. (Journal of Hazardous Materials, 2024)

Dual pathways of aragonite-to-calcite transformation in stalagmites: Implications for paleoclimate reconstructions - Rui Zhang; Haiwei Zhang; Christoph Spötl; Hai Cheng; Yanjun Cai; Carlos Pérez-Mejías; Xiyu Dong; Lijuan Sha; Youwei Li; Liangcheng Tan; Jingjie Zang; Xunlin Yang; et al. (Geochimica et Cosmochimica Acta, 2024)

Differential effects of egg consumption on fecal lipid metabolism: Insights from C57BL/6J mice under chow diet and high-fat diet - Fan Zhang; Tian Yang; Junhua Li; Luping Gu; Cuihua Chang; Li Yang; Zijian Huang; Yujie Su; Yanjun Yang (Food Bioscience, 2024)

Efficient industrial-current-density H2O2 production in neutral medium via external-shell boron regulation on single-atom VN4 sites - Dingding Li; Yanjun Guo; Yubo Sun; Lei Bai; Jiangwei Shi; Gang Chen; Jingbo Shi; Yijiang Liu; Chenghao Jin; Zongye Yue; Jinbo Bai; Kunyue Leng; et al. (Chemical Engineering Journal, 2024)

A yarn-based sweat-activated battery constructed with conjugated electrospun nanofiber separators as a durable and high-capacity power source in textile electronics - Yanling Zheng; Huijun Sun; Yanjun Cheng; Wenhu Gao; Chenyu Wang; Jun Ju; Min Li; Xuemei Xiang; Wei Sun; Wei Wang; Zhisong Lu; Yan Qiao (Chemical Engineering Journal, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

New approach to reduce carbon emissions by hydrogen reduction of boron-bearing iron concentrate in a fluidized bed: Reduction kinetics and microstructure analysis - Peiyu Li; Jianwen Yu; Yanjun Li; Peng Gao; Yuexin Han (Minerals Engineering, 2024)

In vitro and in vivo activity of ceftazidime/avibactam and aztreonam alone or in combination against mcr-9, serine- and metallo-β-lactamases–co-producing carbapenem-resistant Enterobacter cloacae complex - Wengang Li; Jisheng Zhang; Yanjun Fu; Jianmin Wang; Longjin Liu; Wenzhang Long; Kaixin Yu; Xinhui Li; Chunli Wei; Xushan Liang; Jin Wang; Chunjiang Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

A convolutional neural network prediction model for aviation nitrogen oxides emissions throughout all flight phases - Longfei Chen; Qian Zhang; Meiyin Zhu; Guangze Li; Liuyong Chang; Zheng Xu; Hefeng Zhang; Yanjun Wang; Yinger Zheng; Shenghui Zhong; Kang Pan; Yiwei Zhao; et al. (Science of The Total Environment, 2024)

Short-term forecasting for ship fuel consumption based on deep learning - Yumei Chen; Baozhi Sun; Xianwei Xie; Xiaohe Li; Yanjun Li; Yuhao Zhao (Ocean Engineering, 2024)

SPR effect and internal electric field in Pt@BiOBr/(001)-TiO2 S-scheme heterojunction for visible-light-driven photocatalytic degradation of tetracycline hydrochloride and dyes - Jie Yan; Jin Chen; Xiaofeng Yang; Yueying Wang; Xinle Wang; Jianye Shi; Jing Zhang; Yuzhao Ma; Yanjun Li (Journal of Water Process Engineering, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

System-wide coordination and communication of lipid metabolism atlas revealed cytotoxicity of epoxy triglyceride in deep-frying oil - Xue Li; Yanjun Liu; Yong-jiang Xu; Yuanfa Liu (Food Bioscience, 2024)

Investigation into the impact of enzyme treatment on the structural characteristics of egg yolk protein and its correlation with flavor constituents - Tingting Tang; Xuejing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2024)

Development of a novel dual-enzyme modification method for the functionality improvement of egg yolk powder - Huan Rui; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2024)

A new method for generating equidistant/equiratio line between two points on the earth ellipsoid - Jianhui Zhang; Ruiquan Fu; Yanjun Cui; Shaoyang Chen; Mingjie Li; Xuefeng Zhang (Computers & Geosciences, 2024)

Scalable, flexible, ultra-strong, free-standing papery all carbon nanotube membrane with excellent separation and antifouling properties - Yang Yang; Yuhang Cheng; Si Ling; Yanjun Wan; Zhu Xiong; Chunhong Li; Jiangyan Lu; Li Yu; Gaosheng Zhang; Shuaifei Zhao (Chemical Engineering Journal, 2024)

miR-29a-SIRT1-Wnt/β-Catenin Axis Regulates Tumor Progression and Survival in Hepatocellular Carcinoma - Liqiang Qian; Yanjun Zhang; Gang Wang; Bin Li; Hemei Zhou; Jie Qiu; Lei Qin (Biochemical Genetics, 2024)

Design and Analysis of a Buoy-Based Cable Seafloor Observatory System Response under Extreme Weather Conditions - Wenjie Zhou; Yanjun Li; Yulu Zhang; Qingyan Jiang; Dong Chen; Yanzhen Gu; Yuan Lin (Journal of Marine Science and Engineering, 2024)
In order to address the requirements of scientific multidisciplinary observation in diverse small-scale regions, we have introduced the Buoy-based Cable Seafloor Observatory System (BCSOS). This system offers a distinct advantage in contexts where the use of shorter cables is feasible, contrasting with the lengthy cables typically necessary for conventional observatories. The BCSOS consists of three primary components: the Real-Time Electric Communication (RTEC) Buoy, the Power Information Transmission System (PITS), and the Seafloor Observation Subsystem (SOS). The RTEC Buoy is equipped with instruments for measuring sea surface parameters and serves as a data and power hub. The PITS, comprising a robust EM cable, connects the buoy to the SOS, which houses instruments for seafloor observations. The system is designed for a maximum water depth of 100 m and has an expected lifespan of about 5 years. The BCSOS prototypes were deployed at the Huangqi Peninsula, Fujian Province, and successfully documented the process during Typhoon Doksuri (international code 2305) at the end of July 2023. The recorded data from the BCSOS revealed a significant increase in wave height and period as the storm approached the Huangqi Peninsula. Additionally, the RTEC buoy exhibited a notable response to the large waves. The data analysis revealed a distinct pattern between the buoy response and the direction of wave propagation across various sea conditions, that the buoy’s angular movement in pitch and roll directions follows a regular elliptical distribution corresponding to different wave propagation directions. Upon thorough evaluation, future enhancements to the system are slated to concentrate on refining its design, with a particular emphasis on bolstering stability and enhancing corrosion resistance. These improvements are aimed at cementing the system’s long-term viability and performance within the challenging marine environment.

A computational neural model that incorporates both intrinsic dynamics and sensory feedback in the Aplysia feeding network - Yanjun Li; Victoria A. Webster-Wood; Jeffrey P. Gill; Gregory P. Sutton; Hillel J. Chiel; Roger D. Quinn (Biological Cybernetics, 2024)
Studying the nervous system underlying animal motor control can shed light on how animals can adapt flexibly to a changing environment. We focus on the neural basis of feeding control in Aplysia californica . Using the Synthetic Nervous System framework, we developed a model of Aplysia feeding neural circuitry that balances neurophysiological plausibility and computational complexity. The circuitry includes neurons, synapses, and feedback pathways identified in existing literature. We organized the neurons into three layers and five subnetworks according to their functional roles. Simulation results demonstrate that the circuitry model can capture the intrinsic dynamics at neuronal and network levels. When combined with a simplified peripheral biomechanical model, it is sufficient to mediate three animal-like feeding behaviors (biting, swallowing, and rejection). The kinematic, dynamic, and neural responses of the model also share similar features with animal data. These results emphasize the functional roles of sensory feedback during feeding.

Supply and demand of ecosystem services and their interaction with urbanization: The case of Chengdu-Chongqing urban agglomeration - Yuqi Xie; Wencai Dai; Shujiang Xiang; Hua Deng; Zifang Wang; Yanjun Li; Zhongshu Wang; Mi Zhou; Ming Gao (Urban Climate, 2024)

A review of quantification methods for light absorption enhancement of black carbon aerosol - Yao Kong; Guorui Zhi; Wenjing Jin; Yuzhe Zhang; Yi Shen; Zhengying Li; Jianzhong Sun; Yanjun Ren (Science of The Total Environment, 2024)

TIC-driven sustainable land use mode in the Loess Plateau: A case study of gully land consolidation project in Yan'an City, China - Yanjun Guo; Yansui Liu; Ruotong Li; Yurui Li; Jieyong Wang (Land Use Policy, 2024)

Freeze-thaw aged polyethylene and polypropylene microplastics alter enzyme activity and microbial community composition in soil - Yanjun Li; Guanghui Xu; Yong Yu (Journal of Hazardous Materials, 2024)

Treatment of chromium-containing sludge using sintering and ironmaking combined technology: A risk-reducing strategy for environmental impact - Shengxuan Fan; Jinchao Wei; Xiaorong Xu; Ran Yan; Qian Li; Ying Liu; Yanjun Huang; Yi Wang; Guozhi Fan; Lei Zhang (Journal of Environmental Management, 2024)

Consumers' willingness to pay for carbon-labeled agricultural products and its effect on greenhouse gas emissions: Evidence from beef products in urban China - Xuan Chen; Shihang Zhen; Shaoting Li; Jieyu Yang; Yanjun Ren (Environmental Impact Assessment Review, 2024)

A Pickering emulsion stabilized by Chitosan-g-Poly(N-vinylcaprolactam) microgels: Interface formation, stability and stimuli-responsiveness - Yue Li; Mengting Chen; Yanjun Ding; Yanke Li; Mingming Guo; Yichuan Zhang (Carbohydrate Polymers, 2024)

Lactate coordinated with exercise promoted the browning of inguinal white adipose tissue - Xuefei Chen; Yanjun Li; Jingbo Zhang; Wenhua Huang; Jie Su; Jing Zhang (Journal of Physiology and Biochemistry, 2024)

Potential mitigation of titanium dioxide nanoparticles against 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis through inhibiting the canonical NF-κB pathway - Yanjun Gao; Langzhi He; Shumin Duan; Hasen Bilige; Lizhi Lyu; Zihui Li; Hongbo Wang; Chen Li; Yun Wang (NanoImpact, 2024)

Valorization of waste graphite in spent lithium-ion batteries to graphene via modified mechanical exfoliation and the mechanism exploration - Yanjun Liu; Jiadong Yu; Yukun Zhao; Jiarui Lai; Jinhui Li; Quanyin Tan (Journal of Cleaner Production, 2024)

Facile dissolution of cellulose by superbase-derived ionic liquid using organic solvents as co-solvents at mild temperatures - Yuhui Ci; Yunqian Ma; Tianying Chen; Feiyun Li; Yanjun Tang (Carbohydrate Polymers, 2024)

Citric acid/chitosan adhesive with viscosity-controlled for wood bonding through supramolecular self-assembly - Lijian Cai; Yutong Chen; Zetan Lu; Ming Wei; Xin Zhao; Yanjun Xie; Jian Li; Shaoliang Xiao (Carbohydrate Polymers, 2024)

Mineral transformation, element transport and hydrological impact in weathering at the Bingling Temple Grottoes: Implications for weathering in alkaline environments in NW China - Ruxue Liao; Wenwu Chen; Peiran Liu; Li Wang; Qian Xia; Xiaoyan Yang; Yanjun He; Qinglin Guo (CATENA, 2024)

Probiotics and Prebiotics in Subclinical Hypothyroidism of Pregnancy with Small Intestinal Bacterial Overgrowth - Qian Ouyang; Yajuan Xu; Yanjie Ban; Jingjing Li; Yanjun Cai; Bo Wu; Yingqi Hao; Zongzong Sun; Miao Zhang; Mengqi Wang; Wentao Wang; Yinkai Zhao (Probiotics and Antimicrobial Proteins, 2024)
Evaluating efficacy of probiotics combined with prebiotics in small intestinal bacterial overgrowth (SIBO) in subclinical hypothyroidism (SCH) in the second trimester. We collected data from 78 pregnant women with SCH (SCH group) and 74 normal pregnant women (control group) in second trimester, compare the differences in high sensitivity C-reactive protein (hsCRP), result of lactulose methane-hydrogen breath test and gastrointestinal symptoms assessed by GSRS scale between two groups. In SCH group, 32 patients with SIBO were selected as intervention group. Treatment with probiotics + prebiotics for 21 days; The differences of lipid metabolism, hsCRP, thyroid function level, methane-hydrogen breath test results and GSRS scores before and after treatment were compared to evaluate the therapeutic effect. (1) The positive rate of SIBO and methane, hsCRP levels in SCH group were higher than those in control group ( P < 0.05), the total score of GSRS scale, mean score of indigestion syndrome, and constipation syndrome in SCH group were higher ( P < 0.05). (2) The mean abundance of hydrogen and methane were higher in SCH group. (3) After treatment, serum levels of thyrotropin(TSH), total cholesterol(TC), triglyceride(TG), low-density lipoprotein (LDL), and hsCRP in intervention group were decreased, and high-density lipoprotein (HDL) was increased compared with before treatment ( P < 0.05). (4) After treatment, methane positive rate, total score of GSRS scale, mean score of diarrhea syndrome, dyspepsia syndrome, and constipation syndrome were decreased ( P < 0.05). (5) The average abundance of methane and hydrogen were lower. Probiotics combined with prebiotics are effective in the treatment of SIBO in pregnant SCH patients. Clinical Trial Registration Number: ChiCTR1900026326.

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Fasting and metabolic syndrome: A systematic review and Meta-analyses - Xue Li; Binbin Nian; Ruizhi Li; Xinyu Cao; Yanjun Liu; Yuanfa Liu; Yong-Jiang Xu (Critical Reviews in Food Science and Nutrition, 2024)

Design and Experimental Study of 50 kW Ocean Thermal Energy Conversion Test Platform Based on Organic Rankine Cycle - Beichen Lu; Yanjun Liu; Xiaoyu Zhai; Li Zhang; Yun Chen (Journal of Marine Science and Engineering, 2024)
In recent years, clean and renewable energy sources have received much attention to balance the contradiction between resource needs and environmental sustainability. Among them, ocean thermal energy conversion (OTEC), which consists of surface warm seawater and deep cold seawater, can rely on thermal cycling to generate electricity and has great potential in alleviating the energy crisis. In this paper, the design and experiment study of a 50 kW OTEC platform is proposed. Thermodynamic modeling, calculation, optimization, and engineering calibration of the system were carried out, and the thermal efficiency reached 2.63% to meet the power generation demand. Experiments were also carried out by using a heat pump unit to simulate hot and cold seawater environments, and data on the stable operation of the system were obtained, with the grid-connected power reaching 47.5 kW and a thermal efficiency of 2.46%. The accuracy of the design scheme is verified, and the theoretical basis and data support are provided for the practical development and application of ocean thermal energy conversion.

Real-time detection and counting of wheat ears based on improved YOLOv7 - Zanpeng Li; Yanjun Zhu; Shunshun Sui; Yonghao Zhao; Ping Liu; Xiang Li (Computers and Electronics in Agriculture, 2024)

Safe utilization of bioresources in gentamicin mycelial residues by thermal treatment: Antibiotic degradation, resistance gene inactivation and available nutrients promotion - Dong Wang; Yanan Dong; Shuaishuai Xin; Yuefei Li; Ningyi Chen; Yulin Liu; Qianwen Wang; Guocheng Liu; Yucan Liu; Huiling Liu; Yanjun Xin (Waste Management, 2024)

Non-negligible contribution from coastal erosion to sedimentation around the archipelago: A case study of Miaodao Archipelago - Rijun Hu; Wenkai Liu; Jingrui Li; Bo Liu; Longhai Zhu; Yanjun Yin; Jiandong Qiu; Zhaohan Yi; Jun Ye; Xiaodong Zhang (Marine Geology, 2024)

Separation and quantification of tire and road wear particles in road dust samples: Bonded-sulfur as a novel marker - Yifan Ren; Wenhui Li; Qi Jia; Yanjun Zhao; Chen Qu; Li Liu; Jiemin Liu; Chuandong Wu (Journal of Hazardous Materials, 2024)

Fabrication of phosphatidylcholine-EGCG nanoparticles with sustained release in simulated gastrointestinal digestion and their transcellular permeability in a Caco-2 monolayer model - Mengya Zhang; Yujie Su; Junhua Li; Cuihua Chang; Luping Gu; Yanjun Yang (Food Chemistry, 2024)

Tributyrin microcapsule prepared by ultrahigh methoxylated pectin combination with maltodextrin: The characterization, gastrointestinal digestion, and fecal fermentation behavior - Weichao Cao; Shuyi Guan; Nerissa Arviana Tristanto; Yuying Yuan; Zhitao Li; Yanjun Tong; Xiao Hua (Food Hydrocolloids, 2024)

Regulation of interfacial polymerization by organic base for high-permselective nanofiltration - Huiying Ding; Yuting Liu; Zhong Zhang; Yanjun Cheng; Jiahao Mo; Lu Elfa Peng; Cheng Xiang; Hongchang Pei; Xianhui Li (Desalination, 2024)

Pore structure-dependent sieving effect of mesoporous carbon to mitigate the interference of natural organic matter for selective sulfamethoxazole removal from wastewater - Jiajun Zou; Yanjun Shao; Xinyu Hu; Haichuan Zhang; Shanshan Ye; Ji Li (Chemical Engineering Journal, 2024)

Adsorption behaviors and atomistic mechanisms of iodate and iodide on hollow spherical allophane nanoparticles - Shun Wang; Yanjun Zhang; Dong Liu; Peng Yuan; Mengyuan Li; Peixin Du; Jinkui Zhao; Wenbin Yu; Howard Wang (Applied Clay Science, 2024)

Photocatalytic degradation of fluoranthene in soil suspension by TiO2/α-FeOOH with enhanced charge transfer capacity - Bingjie Yin; Jingying Li; Wei Guo; Haoqing Dong; Guangshan Zhang; Yanjun Xin; Guodong Zhang; Qinghua Chen (Environmental Science and Pollution Research, 2024)

Cobalt etched graphite felt electrode for enhanced removal of organic pollutant in aqueous solution with a solid polymer electrolyte - Xinyu Li; Yanjun Yu; Ruijuan Zhang; Weilin Guo (Environmental Science and Pollution Research, 2024)

Heat and carbon co-activated persulfate to regenerate gentamicin-laden activated carbon: Performance, mechanism, and safety assessment - Dong Wang; Shuaishuai Xin; Yanan Dong; Zhihao Sun; Xiaofen Li; Qianwen Wang; Guocheng Liu; Yucan Liu; Yanjun Xin (Chemosphere, 2024)

Effects and mechanisms of polystyrene micro- and nano-plastics on the spread of antibiotic resistance genes from soil to lettuce - Guanghui Xu; Yanjun Li; Xiaolong Lin; Yong Yu (Science of The Total Environment, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

Aluminum speciation in polymerized aluminum chloride: Roles and chloride ion migration in sludge dewatering - Yanjun Zhu; Hongyun Li; Peng Yang; Dong Li; Ziyan Wang; Yunpeng Qi; Jie Zhang (Journal of Environmental Chemical Engineering, 2024)

Mathematical model and experiment investigation on electrodialysis separation process of LiBr from NH3-H2O-LiBr ternary solution in ammonia absorption refrigeration system - Mengkai Xu; Shuhong Li; Zhenghao Jin; Weixue Jiang; Yanjun Li (International Journal of Refrigeration, 2024)

PhenoNet: A two-stage lightweight deep learning framework for real-time wheat phenophase classification - Ruinan Zhang; Shichao Jin; Yuanhao Zhang; Jingrong Zang; Yu Wang; Qing Li; Zhuangzhuang Sun; Xiao Wang; Qin Zhou; Jian Cai; Shan Xu; Yanjun Su; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Coal structure identification based on geophysical logging data: Insights from Wavelet Transform (WT) and Particle Swarm Optimization Support Vector Machine (PSO-SVM) algorithms - Zhongzheng Tong; Yanjun Meng; Jinchuan Zhang; Yaning Wu; Zhen Li; Dongsheng Wang; Xingqi Li; Guangxi Ou (International Journal of Coal Geology, 2024)

Adsorption behaviors for clathrate hydrates of CO2 with mixed gases - Ningru Sun; Yanjun Li; Nianxiang Qiu; Zhen Liu; Joseph S. Francisco; Shiyu Du (Fuel, 2024)

Investigation of the NH3 consumption and H2O/NO formation during the oxidation of n-heptane and iso-octane blended with ammonia - Dao Zheng; Zhimin Peng; Dong He; Meng Zhang; Jidong Li; Yanjun Ding; Yanjun Du (Fuel, 2024)

Mid-infrared absorption spectroscopy measurements and model improvements during the oxidation of ammonia/ethanol and ammonia/diethyl ether blends in a shock tube - Dao Zheng; Dong He; Yanjun Du; Meng Zhang; Jidong Li; Yanjun Ding; Zhimin Peng (Fuel, 2024)

Effects of cholesterol removal treatment on the flavor and physicochemical properties of hot gel egg yolk - Tingting Tang; Xuejing Gao; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (Food Chemistry, 2024)

Differences in the gelation, digestibility and release of antioxidant peptides of egg white/yolk in boiled eggs - Min Zhu; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2024)

Xylan cinnamoylation for reinforcing poly (butylene adipate-co-terephthalate): Molecule design and interaction optimization - Yanjun Chen; Jie Dai; Xin Shen; Junqiang Shan; Yulian Cao; Tianpeng Chen; Hanjie Ying; Chenjie Zhu; Ming Li (Carbohydrate Polymers, 2024)

Corrigendum to “Salecan confers anti-inflammatory effects in liver injury via regulating gut microbiota and its metabolites” [Carbohydrate Polymers. (2023) 120418] - Yanjun Liu; Panpan Li; Wenjie Pan; Juan Zhao; Chen Guang Olnood; Yuanfa Liu; Yong-Jiang Xu (Carbohydrate Polymers, 2024)

An experimental study of mitigating coastal dune erosion by using bio-carbonization of reactive magnesia cement - Jiaming Zhang; Yuhao Li; Yi Luo; Yanjun Li; Qinggang Yang; Zijian Shen (Marine Georesources & Geotechnology, 2024)

ETV7 promotes colorectal cancer progression through upregulation of IFIT3 - Bao Chai; Yanjun Li; Yarong Guo; Zhuowei Zhang; Kai Jia; Xinhao Chai; Yuhong Suo (Functional & Integrative Genomics, 2024)
Members of the E26 transformation-specific (ETS) variant transcription factor family act as either tumor suppressors or oncogenic factors in numerous types of cancer. ETS variant transcription factor 7 (ETV7) participates in the development of malignant tumors, whereas its involvement in colorectal cancer (CRC) is less clear. In this study, The Cancer Genome Atlas (TCGA) and immunochemistry staining were applied to check the clinical relevance of ETV7 and interferon-induced protein with tetratricopeptide repeats 3 (IFIT3) in CRC patients. Overexpression and knockdown of ETV7 and IFIT3 were conducted by transfecting the cells with pCDNA3.1 plasmids and siRNAs, respectively. Western blotting was used to detect the protein expression of ETV7 in CRC cells. Cell Counting Kit-8, cell colony formation, and Transwell assays, as well as flow cytometry, were used to evaluate the proliferation, migration, cell cycle, and apoptosis of CRC cells. Furthermore, western blotting, RT-qPCR, and luciferase assay were used to explore the regulation of ETV7 on IFIT3. Rescue assay was used to investigate the significance of ETV7/IFIT3 axis on CRC progression. We found that ETV7 was upregulated in CRC tissues and cells. Overexpression of ETV7 stimulated the proliferation, migration, and cell cycle amplification, and reduced the apoptosis of CRC cells. Downregulation of ETV7 exerted the opposite effect on CRC cell progression. Moreover, we demonstrated that ETV7 stimulated the transcription activity, the mRNA and protein expression of IFIT3 in CRC cells. There was a positive correlation between ETV7 and IFIT3 in CRC patients. IFIT3 knockdown reversed the promotive effect exerted by overexpression of ETV7 on the amplification and migration of CRC cells. By contrast, overexpression of IFIT3 blocked the inhibitory effect of ETV7-targeting siRNA. In summary, ETV7 induces progression of CRC by activating the transcriptional expression of IFIT3. The EVT7/IFIT3 axis may be a novel target for CRC therapy.

Ocular topical application of alpha-glucosyl hesperidin as an active pharmaceutical excipient: in vitro and in vivo experimental evaluation - Linrong Yu; Qiliang Zhang; Liping Zhou; Yanjun Wei; Mengshuang Li; Xianggen Wu; Meng Xin (Drug Delivery and Translational Research, 2024)

Communication Management and Data Compression Algorithm Design of BeiDou Transparent Transmission Terminal for Argo Buoy - Hongyu Li; Yanjun Fan; Yicheng Wen; Yanchao Zou; Qingfeng Ma; Shaobo Yang (Journal of Marine Science and Engineering, 2024)
The Argo buoy detects marine environmental data by making profile movements in the ocean and transmits the profile detection data to the shore base through the communication terminal. However, due to the large volume of data collected from profile detections and the continuous operation of the terminal, the remote communication of buoys is characterized by lengthy communication times and significant power consumption. A low-power Beidou transparent transmission terminal is designed to solve these problems in this paper. The terminal performs low-power operation management and power management for terminal remote communication. After the end of a communication process, the microcontroller turns the Beidou module power off and enters STOP mode. Before the next communication process begins, the serial port wakes up the microcontroller, which powers up the Beidou module. Before the remote communication, the microcontroller compacts the profile detection data collected by the buoy to reduce the quantity of remote communication data. In this paper, a variety of data compression methods are used to compare the compression rate, and the best compression method is selected according to the format characteristics of the data. The results show that the Beidou transparent transmission terminal of the Argo buoy can realize low power consumption for remote communication in ocean exploration. The terminal reduces power consumption by 77.282% per communication, and the average number of remote communications for each profile detection data are reduced by 55 times. The low-power Beidou transparent transmission terminal improves the battery life and is conducive to the long-term operation of the buoy.

A real-time fluorogenic recombinase polymerase amplification microfluidic chip (on-chip RPA) for multiple detection of pathogenic microorganisms of penaeid shrimp - Qiang Li; Lijun Duan; Dongsheng Jin; Yuxin Chen; Yirong Lou; Qianjin Zhou; Zhongjie Xu; Fangjie Chen; Hongxian Chen; Guizong Xu; Maocang Yan; Guanjun Yang; et al. (Aquaculture, 2024)

Urban shrinkage in the regional multiscale context: Spatial divergence and interaction - Zuopeng Ma; Guolei Zhou; Jing Zhang; Yanjun Liu; Pingyu Zhang; Chenggu Li (Sustainable Cities and Society, 2024)

Toxic effects and mechanisms of engineered nanoparticles and nanoplastics on lettuce (Lactuca sativa L.) - Yanjun Li; Xiaolong Lin; Guanghui Xu; Qiuliang Yan; Yong Yu (Science of The Total Environment, 2024)

Catalytic stepwise pyrolysis for dechlorination and chemical recycling of PVC-containing mixed plastic wastes: Influence of temperature, heating rate, and catalyst - Yanjun Hu; Mingzhe Li; Nan Zhou; Hao Yuan; Qianqian Guo; Long Jiao; Zengyi Ma (Science of The Total Environment, 2024)

Synergistic effects of ultrasonication on the flotation separation of galena from chalcopyrite using sulfuric acid as a depressant - Qinbo Cao; Yanjun Li; Heng Zou; Dianwen Liu; Yan Yan; Haiyu Zhang (Minerals Engineering, 2024)

A sustainable pore wall strengthening for strong and fire-retardant nanopolymerised wood - Kun Zhang; Wenxiang Zhai; Zhifeng Cao; Yaoxing Wang; Lianzhen Li; Jian Li; Jiuqing Liu; Yanjun Xie; Wentao Gan (Chemical Engineering Journal, 2024)

Solar-driven biomass chemical looping gasification using Fe3O4 for syngas and high-purity hydrogen production - Dequan Xu; Bo Wang; Xian Li; Yoke Wang Cheng; Wenming Fu; Yanjun Dai; Chi-Hwa Wang (Chemical Engineering Journal, 2024)

Biocatalytic membranes with crosslinked enzyme aggregates for micropollutant removal - Guanhua Liu; Luting Wang; Anan Zhao; Leijie Guo; Liya Zhou; Ying He; Li Ma; Yunting Liu; Jing Gao; Yanjun Jiang (Chemical Engineering Journal, 2024)

Exploring recharge mechanisms of soil water in the thick unsaturated zone using water isotopes in the North China Plain - Huawu Wu; Fan Song; Leilei Min; Jing Li; Yanjun Shen; Yanan Huang; Hongxiang Fan; Jinzhao Liu; Congsheng Fu (CATENA, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Will the ‘evapotranspiration paradox’ phenomenon exist across China in the future? - Zhenjie Li; Buda Su; Miaoni Gao; Hui Tao; Shan Jiang; Yu Gong; Yanjun Wang; Jian Zhou; Tong Jiang (International Journal of Climatology, 2023)
The uneven changes in potential evapotranspiration (PET) in response to temperature rise are called the ‘evapotranspiration paradox’ phenomenon, which is expected to intensify further under a warming climate. In this paper, we explored the spatial–temporal changes in the future ‘evapotranspiration paradox’ phenomenon over China and its 10 major river sub‐regions under different climate change scenarios. Thus, this paper uses four global climate model outputs under seven shared socioeconomic pathway‐based scenarios (SSP1‐1.9, SSP1‐2.6, SSP2‐4.5, SSP3‐7.0, SSP4‐3.4, SSP4‐6.0 and SSP5‐8.5) from the sixth phase of the Coupled Model Intercomparison Project (CMIP6). Considering the latest IPCC's 6th Assessment Report (AR6), this research emphasizes the 2021–2040 (near‐term), 2041–2060 (mid‐term) and 2081–2100 (long‐term) periods to anticipate the ‘evapotranspiration paradox’ phenomenon. In this study, PET is estimated based on the modified Penman–Monteith (P‐M) method (considering CO 2 ). Furthermore, the paradox phenomenon in this study is defined considering two pivotal conditions: the surface temperature increases but the evaporation decreases (Type I), and the temperature decreases but the evaporation still tends to increase (Type II). The results show that there were only Type I ‘evapotranspiration paradoxes’ that existed in the historical period, which were dominant especially before the 1990s. Nearly 50% of the areas experienced the Type I ‘evapotranspiration paradox’ phenomenon that occurred during 1975–1994 and 1995–2014. Spatially, it covered 100% of the area of the Southeast River (SER) and the Liaohe River (LR) during 1975–1994 and the area of the SER, the HAR, the HHR and the LR during 1995–2014. In the future, the interdecadal growth rate of PET in China is projected to be the highest under the SSP5‐8.5 and the lowest under the SSP3‐7.0 with spatial variation. Importantly, the largest areas of approximately 36% and 45% with the Type I phenomenon are inclined to occur under the SSP1‐1.9 and SSP4‐6.0, respectively, over the long‐term period (2081–2100). The area with the Type I phenomenon will be less than 20% in the near‐term, and it is less than 12% in the mid‐term period. For the Type II evapotranspiration paradox, the uppermost 45% of the area is expected to experience the Type II phenomenon under SSP1‐1.9 during the mid‐term period, while it is 30% under SSP1‐2.6 during the long‐term period. However, this study's findings provide the scientific basis for formulating adaptation and mitigation strategies to combat ‘evapotranspiration paradox’‐related extremes at regional scales.

Historical trends and pollution assessment of heavy metals in core sediments from the Jiangsu offshore area, China - Li He; Shenghui Jiang; Xuhui Chen; Haiyan Cheng; Peng Ye; Lu Chen; Yuan Liu; Yanjun Yin; Xing Leng (Regional Studies in Marine Science, 2023)

Enhanced electrocatalytic degradation of acid orange 7 by using double perovskite La2CoxNi1-xMnO6/nickel foam as the electro-Fenton cathodes - Ruijuan Zhang; Xinyu Li; Yanjun Yu; Weilin Guo (Journal of Water Process Engineering, 2023)

Rapid start-up of the biofilter for simultaneous manganese and ammonia removal at low temperature: Effects of phosphate and copper - Jifang Zheng; Dong Li; Huiping Zeng; Sen Yang; Yanjun Zhu; Jie Zhang (Journal of Cleaner Production, 2023)

Obtention, interaction, and characterization of the soy protein isolate-glycyrrhizin nanocomplex for encapsulating naringenin - Qingchen Cui; Xixi Song; Mengshuang Li; Yanjun Wei; Juan Dong; Xianggen Wu (Food Hydrocolloids, 2023)

Self-standing porous MXene film via in situ formed microgel induced by 2- methylimidazole for high rate supercapacitor - Sai Yan; Chenjing Shi; Zhen Tian; Dan Li; Yanjun Chen; Li Guo; Yanzhong Wang (Chemical Engineering Journal, 2023)

Critical impact of pyrolysis temperatures on biochars for peroxymonosulfate activation: Structural characteristics, degradation performance and mechanism - Suyun Pei; Yanjun Zhao; Wenhui Li; Chen Qu; Yifan Ren; Yue Yang; Jiemin Liu; Chuandong Wu (Chemical Engineering Journal, 2023)

Cellulose eutecticgel electrolytes based on ethylene glycol/zinc chloride deep eutectic solvent for flexible solid-state capacitors - Yanjun Pang; Kefeng Zhang; Xinxin Luan; Baolong Zhu; Wei Shen; Congxia Xie; Lu Li; Jinhui Pang (Chemical Engineering Journal, 2023)

Experimental studies on the effects of thermal damage in coal-derived mudstones caused by high temperatures - Yanjun Shen; Ziyi Li; Cheng Peng; Bohan Yang; Tianchi Ma (Acta Geodaetica et Geophysica, 2023)

Mass-based trophic transfer of polystyrene nanoplastics in the lettuce-snail food chain - Yanjun Li; Xiaolong Lin; Jian Wang; Guanghui Xu; Yong Yu (Science of The Total Environment, 2023)

Energy-based trajectory tracking control of under-actuated unmanned surface vessels - Weijun Zhou; Zishi Xu; Yongxin Wu; Ji Xiang; Yanjun Li (Ocean Engineering, 2023)

New insights on the breakage mechanism of magnetite quartzite via high voltage pulse discharge: liberation, property difference, micro morphology, and numerical simulation - Yonghong Qin; Yuexin Han; Peng Gao; Yanjun Li; Yanxia Guo; Fangqin Cheng (Minerals Engineering, 2023)

Cotton yield stability achieved through manipulation of vegetative branching and photoassimilate partitioning under reduced seedling density and double seedlings per hole - Jingyuan Zhou; JunJun Nie; Xiangqiang Kong; Jianlong Dai; Yanjun Zhang; Dongmei Zhang; Zhengpeng Cui; Ziqing Hua; Zhenhuai Li; Hezhong Dong (Field Crops Research, 2023)

Interfacial engineering of MXene-based composite aerogel for high-performance, multifunctional solar steam generator - Yuanjin Wang; Yanjun Li; Qin Huang; Weijing Qi; Ruhao Zan; Min Gan; Zhenggang Rao; Linfeng Fei (Desalination, 2023)

A dual-enzyme microreactor based on encapsulation and covalent bond for enzymatic electrocatalytic CO2 reduction - Guanhua Liu; Lirong Wang; Lihang Yan; Hao Zhao; Yaoxuan Li; Liya Zhou; Ying He; Li Ma; Yunting Liu; Jing Gao; Yanjun Jiang (Chemical Engineering Journal, 2023)

Adhesive injectable cellulose-based hydrogels with rapid self-healing and sustained drug release capability for promoting wound healing - Lu Li; Lixin Wang; Xinxin Luan; Yanjun Pang; Kefeng Zhang; Yushuai Cheng; Zhe Ji; Jinhui Pang (Carbohydrate Polymers, 2023)

Hygrothermal and energy performance assessment of a passive building wall integrating PCM and bio-based hygroscopic material - Dongxia Wu; Mourad Rahim; Wendong Li; Mohammed El Ganaoui; Rachid Bennacer; Kaiyong Hu; Huan Sun; Zhili Sun; Tonghua Zou; Yanjun Zhang (Building and Environment, 2023)

Application of eDNA metabarcoding for monitoring the fish diversity of the Jiangjin to Fuling section of the upper reaches of the Yangtze River - Ruli Cheng; Yang Luo; Qinghua Li; Yufeng Zhang; Zhihao Liu; Qiliang Chen; Yingwen Li; Yanjun Shen (Hydrobiologia, 2023)

Manganese losses induced by severe soil acidification in the extensive Lei bamboo (Phyllostachys violascens) plantation stands in Eastern China - Yutong Zong; Zichuan Li; Renyi Gui; De Chen; Mengting Yuan; Yanjun Chai; Shengdao Shan; Ming Hung Wong (Chemosphere, 2023)

Astaxanthin enhances the development of bovine cloned embryos by inhibiting apoptosis and improving DNA methylation reprogramming of pluripotency genes - Fanglong Bi; Hongxiao Xiang; Jian Li; Jianqiang Sun; Ning Wang; Wenju Gao; Mingju Sun; Yanjun Huan (Theriogenology, 2023)

Astaxanthin protects oocyte maturation against cypermethrin-induced defects in pigs - Jianqiang Sun; Jian Li; Yaodi Wang; Jiadan Qu; Fanglong Bi; Hongxiao Xiang; Xintao Zhao; Mingju Sun; Yanjun Huan (Theriogenology, 2023)

Interfacial permeation preparation of ZIF-8 in reactive deep eutectic for efficient adsorption and selective removal of Congo red - Yiwen Li; Huanhuan Zhang; Shikuan Xu; Yangyang Wang; Qi Guo; Rong Li; Yanjun Xing (Journal of Environmental Chemical Engineering, 2023)

A pilot study on recovery of iron from sulfur-bearing hematite ore using hydrogen-based mineral phase transformation followed by magnetic separation - Jianwen Yu; Hao Sun; Peiyu Li; Wenjie Han; Yanjun Li; Yuexin Han (Journal of Environmental Chemical Engineering, 2023)

Effect of Dual-frequency ultrasonic on subcooled water freezing - Zhao Zilei; Zhou Runfa; Jin Zhenghao; Qin Luwen; Li Shuhong; Li Yanjun (International Journal of Refrigeration, 2023)

Highly sensitively detection of amine vapors released during shrimp spoilage by fluorescent molecules locked in covalent organic frameworks - Jingru Mi; Yongxian Guo; Yanjun Gong; Shuya Liu; Mei Zhao; Qiongzheng Hu; Li Yu (Food Chemistry, 2023)

Fabrication of egg white protein/phosphatidylcholine-EGCG co-assembled nanoparticles with sustained release in simulated gastrointestinal digestion and their transcellular permeability in Caco-2 cultures - Mengya Zhang; Xuejing Gao; Yujie Su; Junhua Li; Cuihua Chang; Luping Gu; Yanjun Yang (Food Hydrocolloids, 2023)

Terminal removal at first square enhances vegetative branching to increase seedcotton yield at low plant density - Junjun Nie; Lin Sun; Lijie Zhan; Xue Li; Wenting Hou; Yanjun Zhang; Weijiang Li; Dongmei Zhang; Zhengpeng Cui; Zhenhuai Li; Shizhen Xu; Jianlong Dai; et al. (Field Crops Research, 2023)

Field-grown cotton shows genotypic variation in agronomic and physiological responses to waterlogging - Yanjun Zhang; Yan Li; Tiantian Liang; Yabin Yuan; Zhenhuai Li; Shizhen Xu; Jianlong Dai; Shoujin Fan; Cundong Li; Hezhong Dong (Field Crops Research, 2023)

Adaptive corrected parameters algorithm applied in cooling load prediction based on black-box model: A case study for subway station - Yuanyang Hu; Luwen Qin; Shuhong Li; Xiaohuan Li; Runfa Zhou; Yanjun Li; Wei Sheng (Energy and Buildings, 2023)

Synthesis of bifunctional thermal response promoters for improved high-solids enzymatic hydrolysis of corncob residues - Feiyun Li; Haohao Li; Hongming Lou; Fubao Sun; Yanjun Tang (Bioresource Technology, 2023)

Highly efficient nanocomposite of Y2O3@biochar for oxytetracycline removal from solution: Adsorption characteristics and mechanisms - Jiaying Song; Lun Lu; Jian Wang; Xue Li; Jinying Li; Qianwen Wang; Haiyan Du; Shuaishuai Xin; Lina Xu; Qinghua Yan; Chengzhi Zhou; Guocheng Liu; et al. (Bioresource Technology, 2023)

Root predominant overexpression of iaaM and CKX genes promotes root initiation and biomass production in citrus - Dan Tang; Yanjun Li; Longmei Zhai; Wei Li; Rahul Kumar; Huseyin Yer; Hui Duan; Baoping Cheng; Ziniu Deng; Yi Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Promoting initiation and biomass production of roots is significant for plant-based industries including using roots as bioreactors. Two citrus genotypes, Carrizo and US-897, were used as model plants to test the effects of root-predominantly overexpressed the iaaM (indoleacetic acid-tryptophan monooxygenase) gene and a CKX (a cytokinin oxidase/dehydrogenase) gene. The iaaM transgenic lines exhibited markedly faster root initiation, more root numbers, and higher root biomass compared to their wild-type counterparts. The transgenic iaaM + CKX plants also exhibited similar phenotypes, albeit to a lesser extent than the iaaM plants. Molecular analysis revealed an auxin-responsive CsGH3.1 gene was up-regulated in the iaaM roots and iaaM + CKX roots, and a cytokinin-responsive gene CsARR5 gene was down-regulated in the iaaM + CKX roots. Our results demonstrate that root predominant overexpression of the iaaM or both the iaaM and CKX genes drastically enhances the initiation, growth and biomass production of roots. These results provide additional support that manipulation of auxin and cytokinin levels in roots via transgenic or gene-editing technologies may benefit production of high-value secondary metabolites using roots as bioreactors and also improve rooting of recalcitrant plant species.

Micropore Structure Changes in Response to H2O2 Treatment of Coals with Different Ranks: Implications for Oxidant Stimulation Enhancing CBM Recovery - Yuan Zhao; Yanjun Meng; Kunjie Li; Sujuan Zhao; Haojie Ma (Natural Resources Research, 2023)

Unsupervised deep consistency learning adaptation network for cardiac cross-modality structural segmentation - Dapeng Li; Yanjun Peng; Jindong Sun; Yanfei Guo (Medical & Biological Engineering & Computing, 2023)

Fenton oxidation treatment of oxytetracycline fermentation residues: Harmless performance and bioresource properties - Wenqiang Jia; Jiaying Song; Jian Wang; Jinying Li; Xue Li; Qianwen Wang; Xiang Chen; Guocheng Liu; Qinghua Yan; Chengzhi Zhou; Shuaishuai Xin; Yanjun Xin (Chemosphere, 2023)

Evolution of the foreland basins on either side of the Tian Shan and implications for lithospheric architecture - Chao Li; Shengli Wang; Yanjun Wang; Zhiyuan He; Chuang Sun; Hugh Sinclair; Yan Chen; Shaowen Liu; Guohui Chen; Fei Xue (Marine and Petroleum Geology, 2023)

Uncovering the virome and its interaction with antibiotic resistome during compost fertilization - Qingxia Zhang; Lei Zhou; Yilong Zhao; Shuhong Gao; Yanjun Yang; Qingyun Chen; Wenhui Li; Qi Qi; Qiang Dong; Jiesi Lei; Xue Guo; Qun Gao; et al. (Journal of Hazardous Materials, 2023)

Mechanism of adsorption capacity enhancement of coal due to interaction with high-pressure scCO2-water system - Siyuan Liu; Chuanjie Zhu; Yanjun Li; Sijia Hu; Xiangliang Zhang; Cong Ma (Gas Science and Engineering, 2023)

In-situ constructing pearl necklace-shaped heterostructure: Zn2+ substituted Na3V2(PO4)3 attached on carbon nano fibers with high performance for half and full Na ion cells - Yanjun Chen; Zeyi Tian; Jiahao Li; Tao Zhou (Chemical Engineering Journal, 2023)

Trace Ru-tuned NiO/CNT electrocatalysts outperform benchmark Pt for alkaline hydrogen evolution with superior mass activity - Yanjun Chen; Yiyang Lee; Wei Chu; Jing Li (Chemical Engineering Journal, 2023)

Unraveling roles of the intermediate settler in a microaerobic hydrolysis sludge in situ reduction process - Zhen Zhou; Yiyue Sun; Li Fu; Yi Zuo; Yanjun Shao; Lihua Wang; Chuanting Zhou; Ying An (Bioresource Technology, 2023)

Chinese economic growth and sustainable development: Role of artificial intelligence and natural resource management - Yanjun Wang; Yongfang Li (Resources Policy, 2023)

Applying mass flow analysis and aeration optimization strategy to reduce energy consumption of a full-scale anaerobic/anoxic/oxic system - Lu-Man Jiang; Wen Zhang; Yunhui Li; Yanjun Shao; Zhenjian Zhang; Ming Zhang; Junli He; Ji Qiu; Wenxiang Li; Junwei Wang; Zhen Zhou (Journal of Water Process Engineering, 2023)

Combined effect of heating and enzymatic hydrolysis on the dispersibility and structure properties of egg white powder - Tingting Wang; Cuihua Chang; Wanying Cheng; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Journal of Food Engineering, 2023)

ROS-activated selective fluorescence imaging of cancer cells via the typical LDH-based nanozyme - Zhengdi Wang; Jiancheng Liu; Min Feng; Kai Song; Kaitao Li; Wendi Liu; Shanyue Guan; Yanjun Lin (Chemical Engineering Journal, 2023)

Self-adhesive frost-resistant conductive hydrogel electrolytes based on TA@WSCA-Zn autocatalytic system for flexible and foldable solid-state capacitors - Yanjun Pang; Xinxin Luan; Kefeng Zhang; Yuxiang Liu; Lu Li; Congxia Xie; Jinhui Pang (Chemical Engineering Journal, 2023)

Identification of table grapes in the natural environment based on an improved Yolov5 and localization of picking points - Yanjun Zhu; Shuangshuang Li; Wensheng Du; Yuanpeng Du; Ping Liu; Xiang Li (Precision Agriculture, 2023)

Combined contributions of cytochrome P450s (CYPs) and non-enzymatic metabolism in the in vitro biotransformation of anaprazole, a novel proton pump inhibitor - Fei Liu; Yanjun Xu; Li Wang; Xifeng Ma; Zhen Zhang; Xiaomei Zhuang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Dynamic effects of miR-20a-5p on hippocampal ripple energy after status epilepticus in rats - Xinyu Zhang; Yanjun Yi; Li Cheng; Hengsheng Chen; Yue Hu (Experimental Brain Research, 2023)

Novel metallic Fe recovery from copper smelting slag by the deep reduction method with renewable biochar reducing agent: Phase transformation process and Fe particle growth optimization - Bing Zhao; Xiangyan Kong; Yongsheng Sun; Yuexin Han; Yanjun Li (Process Safety and Environmental Protection, 2023)

Cobalt induces neurodegeneration through FTO-triggered autophagy impairment by targeting TSC1 in an m6A-YTHDF2-dependent manner - Jianping Tang; Fuli Zheng; Xu Liu; Yanjun Li; Zhenkun Guo; Xinpei Lin; Jinfu Zhou; Yu Zhang; Guangxia Yu; Hong Hu; Wenya Shao; Siying Wu; et al. (Journal of Hazardous Materials, 2023)

Anticipating on potential electron acceptors for Anammox - Yanjun Zhu; Dong Li; Saiyue Qi; Sen Yang; Jie Zhang; Wenqiang Wang; Shuai Li (Chemical Engineering Journal, 2023)

Study on the Law of Fracture Development in Plasma-Induced Broken Coal - Yanjun Li; Baiquan Lin; Xiangliang Zhang; Minghua Lin (Rock Mechanics and Rock Engineering, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Comparative study of sediment phosphorus immobilization via the addition of lanthanum-modified and thermal-modified drinking water treatment sludge - Fei Sun; Yu Chen; Liwenze He; Jingxiang Tang; Yanjun Li (Environmental Science and Pollution Research, 2023)

Wheat PHT1;9 acts as one candidate arsenate absorption transporter for phytoremediation - Pengfei Wang; Zedong Chen; Yanjun Meng; Huanting Shi; Chuang Lou; Xu Zheng; Gezi Li; Xiangnan Li; Wanxi Peng; Guozhang Kang (Journal of Hazardous Materials, 2023)

Cyanide detoxification and iron mineral recycle of cyanide tailings by the sustainable utilization technology of oxidation-reduction roasting: Process optimization and mechanism study - Bing Zhao; Lingbo Zhao; Peng Gao; Yuexin Han; Yanjun Li; Zaizheng Dong; Yan Song (Journal of Environmental Chemical Engineering, 2023)

Visualization study on the flow and migration characteristics of R290/PAG oil in a room air conditioner during startup and defrosting processes - Che Wang; Jianhua Wu; Bowen Lei; Yanjun Du; Jinbo Li (International Journal of Refrigeration, 2023)

Enhanced electroenzymatic CO2 reduction by a multifunctional ZIF-8 layer on silica nanoflower with immobilized enzyme - Yaoxuan Li; Lihang Yan; Guanhua Liu; Huaxun Chen; Hao Zhao; Lihui Wang; Jing Gao; Yunting Liu; Xiaobing Zheng; Yanjun Jiang (Chemical Engineering Journal, 2023)

Seasonal evolution of aerosol loading and its vertical distribution in northeastern China from long-term satellite observations and model reanalysis - Hujia Zhao; Ke Gui; Yanjun Ma; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Lei Zhang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2023)

Effects of different fracture parameters on microseisms induced by hydraulic fracturing - Kun Shan; Yanhao Zheng; Yanjun Zhang; Zhigang Shan; Zhihai Li (Bulletin of Engineering Geology and the Environment, 2023)
The microseism induced by hydraulic fracturing is of great significance to the development of geothermal reservoirs and the site selection of geothermal systems. In this study, taking geothermal field data from Qiabuqia as a geological reference, several models are developed for hydraulic fracturing simulations based on the models included in the commercial FracMan™ software suit. A series of numerical simulations are carried out to explore the effects of different fracture parameters, including the existence of faults, in-situ stress state, fracture occurrence, and fracture distribution near faults, on the induced microseisms. The results show that during hydraulic fracturing, the existence of faults does affect the propagation direction of the newly generated fractures, causing the fractures to extend toward the fault. The faults also increase the magnitude of microseismic events and make the distribution of microseismic events farther. Under three different in-situ stress states, the magnitudes of induced microseisms and the distance between microseismic events and injection wells are different, mainly due to the different forms of energy release. The total energy of induced microseisms under the reverse faulting stress state (RF) is the largest. Under the normal faulting stress state (NF), the number of microseismic events is the least, with only 28, and these microseismic events are concentrated near the well, with the farthest distribution distance of only 150 m. The fracture occurrence has a significant effect on induced microseisms, mainly affecting the number and distribution range of induced microseisms. With the same number of fractures, as the fracture concentration to the fault increases, both the maximum magnitude and the farthest distribution distance of the induced microseisms increase.

A novel reutilization of ash from biomass gasification process: Feasibility and products improvement analysis - Qianqian Guo; Beibei Yan; Yanjun Hu; Xiang Guo; Wenzhu Wu; Zhanjun Cheng; Guanyi Chen; Li'an Hou (Fuel, 2023)

Thermal gelation and digestion properties of hen egg white: Study on the effect of neutral and alkaline salts addition - Junhua Li; Weijian Zhang; Tingting Tang; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Food Chemistry, 2023)

Influence of selected gums on the foaming properties of egg white powders: Kinetics of foam formation and baking performance - Junhua Li; Jinjing Sun; Cuihua Chang; Luping Gu; Yujie Su; Jiali Zhai; Yanjun Yang (Food Hydrocolloids, 2023)

Polysaccharides from Artocarpus heterophyllus Lam. (jackfruit) pulp alleviate obesity by modulating gut microbiota in high fat diet-induced rats - Shunjiang Zeng; Jun Cao; Chenxi Wei; Yuzi Chen; Qibing Liu; Chuan Li; Yanjun Zhang; Kexue Zhu; Gang Wu; Lehe Tan (Food Hydrocolloids, 2023)

The Potential of NLRP3 Inflammasome as a Therapeutic Target in Neurological Diseases - Wenfang He; Zhiping Hu; Yanjun Zhong; Chenfang Wu; Jinxiu Li (Molecular Neurobiology, 2023)

Associations between congenital heart disease and air pollutants at different gestational weeks: a time-series analysis - Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Zhou; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Geochemistry and Health, 2023)

Meeting the heavy-metal safety requirements for food crops by using biochar: An investigation using sunflower as a representative plant under different atmospheric CO2 concentrations - Yiying Wang; Guiying Lin; Xian Li; Ming Hang Tai; Shuang Song; Hugh Tiang Wah Tan; Ken Leong; Elvis Yew Boon Yip; Grace Yoke Chin Lee; Yanjun Dai; Chi-Hwa Wang (Science of The Total Environment, 2023)

Foaming properties of dried egg white at different outlet temperatures - Junhua Li; Jinjing Sun; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Journal of Food Engineering, 2023)

Sugar alcohols as cryoprotectants of egg yolk: Inhibiting crystals and interactions - Haosheng Zhu; Junhua Li; Yujie Su; Luping Gu; Cuihua Chang; Yanjun Yang (Journal of Food Engineering, 2023)

Essential role of atomic H* in activating hydrogen peroxide to produce singlet oxygen for emerging organic contaminants degradation - Xixi Chen; Wanyi Fu; Yulong Yang; Yanjun Li; Kai Yang; Xuanbo Xu; Xihui Zhang (Journal of Environmental Chemical Engineering, 2023)

Highly efficient electrochemical oxidation of hexafluoropropylene oxide homologues at a boron-doped diamond anode - Zizi Li; Hai-Hua Huang; Yanjun Huang; Junlong Huang; Minhui Shen; Juan Zheng; Jia-Wei Wang; Gangfeng Ouyang (Journal of Environmental Chemical Engineering, 2023)

Ultrafast loose nanofiltration membrane intercalated by in-situ grown nanoparticles for dye purification and reuse - Yuting Liu; Jiahao Mo; Huiying Ding; Yanjun Cheng; Zhong Zhang; Chen Wang; Xianhui Li (Desalination, 2023)

A new automatic quality control system for ocean profile observations and impact on ocean warming estimate - Zhetao Tan; Lijing Cheng; Viktor Gouretski; Bin Zhang; Yanjun Wang; Fuchao Li; Zenghong Liu; Jiang Zhu (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

The regulatory roles of DDIT4 in TDCIPP-induced autophagy and apoptosis in PC12 cells - Li Li; Lingyi Xi; Jin Wu; Zunquan Zhao; Youliang Chen; Weili Liu; Zhihui Pan; Mingzhu Liu; Danfeng Yang; Zhaoli Chen; Yanjun Fang (Journal of Environmental Sciences, 2023)

Characterization of physical properties, volatile compounds and aroma profiles of different salted egg yolk lipids - Xuejing Gao; Junhua Li; Cuihua Chang; Luping Gu; Wen Xiong; Yujie Su; Yanjun Yang (Food Research International, 2023)

Ridge intertillage alters rhizosphere bacterial communities and plant physiology to reduce yield loss of waterlogged cotton - Yanjun Zhang; Shizhen Xu; Guangya Liu; Tengxiang Lian; Zhenhuai Li; Tiantian Liang; Dongmei Zhang; Zhengpeng Cui; Lijie Zhan; Lin Sun; Junjun Nie; Jianlong Dai; et al. (Field Crops Research, 2023)

Verticillium dahliae Asp1 regulates the transition from vegetative growth to asexual reproduction by modulating microtubule dynamic organization - Juan Tian; Mengli Pu; Bin Chen; Guangda Wang; Chunli Li; Xiaxia Zhang; Yanjun Yu; Zhi Wang; Zhaosheng Kong (Environmental Microbiology, 2023)
Verticillium dahliae is a devastating pathogenic fungus that causes severe vascular wilts in more than 400 dicotyledonous plants. The conidiation of V. dahliae in plant vascular tissues is the key strategy for its adaptation to the nutrient‐poor environment and is required for its pathogenicity. However, it remains unclear about the regulatory mechanism of conidium production of V. dahliae in vascular tissues. Here, we found that VdAsp1 , encoding an inositol polyphosphate kinase, is indispensable for the pathogenicity of V. dahliae . Loss of VdAsp1 function does not affect the invasion of the host, but it impairs the colonization and proliferation in vascular tissues. The Δ VdAsp1 mutant shows defective initiation of conidiophore formation and reduced expression of genes associated with the central developmental pathway. By live‐cell imaging, we observed that some of Δ VdAsp1 mutant hyphae are swollen, and microtubule arrangements at the apical region of these hyphae are disorganized. These results indicate that VdAsp1 regulates the transition from vegetative growth to asexual reproduction by modulating microtubule dynamic organization, which is essential for V. dahliae to colonize and proliferate in vascular tissues. These findings provided a potential new direction in the control of vascular wilt pathogen by targeting conidium production in vascular tissues.

Study Regarding the Influence of Blade Rotation Angle Deviations on the Hydraulic Pulsation Characteristics of a Mixed-Flow Pump - Yanjun Li; Danghang Sun; Fan Meng; Yunhao Zheng; Yi Zhong (Journal of Marine Science and Engineering, 2023)
Mixed-flow pumps with adjustable blades are widely used in municipal, agricultural, and hydropower applications. However, a limitation of adjustable blades is that the influence of the water pressure in the pump causes the rotation angle to deviate, which not only reduces the hydraulic efficiency of the pump and increases energy consumption, but it is also detrimental to the stable operation of the pump. To investigate the influence of blade rotation angle deviations (BRADs) on the hydraulic pulsation characteristics of a mixed-flow pump, in this study, a three-dimensional unsteady numerical simulation was adopted to analyze the effects of seven BRAD design schemes on the energy performance, pressure pulsation characteristics, and axial and radial forces in the impeller. When the rotation angle of a single blade deviated counterclockwise, the optimal hydraulic efficiency point of the mixed-flow pump moved toward larger flow rates, and vice versa. Unlike a situation with no BRADs, when there were BRADs, the central symmetry of the low-pressure area near the suction surface of the impeller blades was destroyed. BRADs led to increases in the pressure pulsation amplitudes at the inlet and outlet of the impeller. The dominant pressure pulsation frequencies near the shroud side at the inlet and outlet of the impeller were not affected by BRADs (both of them were equal to the blade frequency). However, the amplitude of the dominant pressure pulsation frequency at the impeller outlet and the radial force of the impeller both increased with increases in the absolute value of the deviation angle. Moreover, when the rotation angle of a single blade was only in the counterclockwise direction, the axial force of the impeller increased. This study can provide an engineering reference for the stability of mixed-flow pumps with BRADs.

Offshore, Unmanned Auto-Leveling Sea-Surface Drifting Platform with Compact Size - Zonglai Mo; Kexiang Li; Kefeng Xie; Jun Li; Yanjun Li (Journal of Marine Science and Engineering, 2023)
This paper proposes an offshore, unmanned auto-leveling sea-surface drifting platform, with a compact size of 0.7 m in diameter, used for obtaining air-sea interface environmental parameters. The platform was designed based on the parallel mechanism with limited degrees of freedom. The mechanical structure, control system hardware, and software of the principal prototype are introduced. A ground-based device was developed to simulate wave disturbance, based on which the static and dynamic simulation experiments were carried out. Experimental results show that the auto-leveling system can achieve real-time leveling against the angle deviation induced by waves, with a leveling accuracy of 0.2° in a simulated wave with an angle of 12°, which meets the requirements of observation equipment.

Recent trends in degradation strategies of PFOA/PFOS substitutes - Zizi Li; Zhi-Mei Luo; Yanjun Huang; Jia-Wei Wang; Gangfeng Ouyang (Chemosphere, 2023)

Enhanced H2O2 utilization efficiency in Fenton-like system for degradation of emerging contaminants: Oxygen vacancy-mediated activation of O2 - Xixi Chen; Wanyi Fu; Zhichao Yang; Yulong Yang; Yanjun Li; Hui Huang; Xihui Zhang; Bingcai Pan (Water Research, 2023)

Vanadium extraction from V-bearing shale using oxidation roasting and acid leaching - Xinran Zhu; Zhenya Zhou; Jianping Jin; Yanjun Li; Yuexin Han (Minerals Engineering, 2023)

Low-temperature upcycling of PET waste into high-purity H2 fuel in a one-pot hydrothermal system with in situ CO2 capture - Hongcai Su; Tian Li; Shurong Wang; Lingjun Zhu; Yanjun Hu (Journal of Hazardous Materials, 2023)

Gel properties of soy protein isolate-potato protein-egg white composite gel: Study on rheological properties, microstructure, and digestibility - Yuanqi Lv; Lilan Xu; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Ming Zhang; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2023)

Salecan confers anti-inflammatory effects in liver injury via regulating gut microbiota and its metabolites - Yanjun Liu; Panpan Li; Wenjie Pan; Juan Zhao; Chen Guang Olnood; Yuanfa Liu; Yong-Jiang Xu (Carbohydrate Polymers, 2023)

Transparent, intrinsically stretchable cellulose nanofiber-mediated conductive hydrogel for strain and humidity sensing - Ziyu Bian; Yinghui Li; Hongling Sun; Mengyu Shi; Yanjun Zheng; Hu Liu; Chuntai Liu; Changyu Shen (Carbohydrate Polymers, 2023)

Impact of thermal structure of planetary boundary layer on aerosol pollution over urban regions in Northeast China - Shuo Lu; Xiaolan Li; Tianliang Zhao; Yanjun Ma; Yangfeng Wang; Yunhai Zhang; Yuehan Luo; Yushan Xin (Atmospheric Pollution Research, 2023)

Impacts of snow cover on micrometeorological conditions and rural air quality in Northeast China - Xiaolan Li; Xiaofeng Guo; Yanjun Ma; Yangfeng Wang; Qingyu Jia; Rihong Wen; Yanbin Xie (Atmospheric Research, 2023)

Genetic Diversity of Jinshaia sinensis (Cypriniformes, Balitoridae) Distributed Upstream of the Yangtze River - Yang Luo; Yufeng Zhang; Ruli Cheng; Qinghua Li; Yu Zhang; Yingwen Li; Yanjun Shen (Fishes, 2023)
The upper reaches of the Yangtze River (upper YR) are a biological zone with extremely rich fish diversity, especially endemic fish. However, long-term human interference, such as environmental pollution and cascade hydropower construction, has significantly changed the habitat of many fish and is threatening the number and genetic diversity of fish populations. Jinshaia sinensis is a typical small and endemic but rare fish that is found in the upper YR, and its genetic diversity and structure still need further study. To understand the current levels of genetic diversity in J. sinensis, we analyzed the genetic diversity, population history, genetic structure, etc., of three J. sinensis populations based on two mitochondrial genes (the cytochrome-c oxidase subunit I, COI, and cytochrome-b gene, Cytb) and two nuclear genes (recombination-activating protein 1, RAG1, and rhodopsin, RH). The genetic diversity analysis indicated that J. sinensis had high genetic diversity, with high haplotype diversity (h) and nucleotide diversity (Pi). Population pairwise FST analysis revealed a significant genetic divergence between the Lijiang and Luzhou populations for all genes and between the Panzhihua and Luzhou populations, except for the COI gene; however, analyses of molecular variance (AMOVA) showed no significant geographic genetic structure among populations, and gene flow analysis also indicated a certain degree of gene exchange among populations. Haplotype network structure analyses revealed low levels of shared haplotypes among populations. Neutrality test and mismatch distribution results indicated that only the Lijiang population had experienced obvious population expansion. Overall, these results indicate that J. sinensis is still a single evolutionarily significant unit, but when considering the threat of habitat disturbance to the population, it is still necessary to carry out long-term genetic monitoring on J. sinensis and on other endemic fishes with similar ecological habits in order to maintain the genetic diversity of fishes in the upper YR.

A Small Floating Platform Designed for Unmanned Defense System - Zonglai Mo; Kefeng Xie; Fengcheng Zhao; Jun Li; Yanjun Li (Journal of Marine Science and Engineering, 2023)
A small floating platform designed for an unmanned short-range defense system is proposed. The structures of the proposed floating platform and weapon system are detailed and described. The floating platform is investigated via virtual prototype technology in the aspects of the platform motion under sea waves of up to Beaufort wind and Douglas sea (wind-sea) scale 5. The motion equations of the floating platform are established according to the ship motion theory, and the movement of the floating platform under different wind-sea scales are simulated and analysed via multi-body fluid dynamics analysis software. To decide the proper size of the platform, the dynamic response of the floating platforms with different sizes is analysed and evaluated under various sea conditions based on multi-body dynamics. A scaled model experiment was conducted and compared with simulation results to verify the theoretical model. A verification experiment was also conducted in a water tank for the performance of the platform via simulated wave disturbance. Results show that the designed floating platform could provide a stable platform in the horizontal direction under a wind-sea scale 3 environment for the defense weapon system, which well meets the design requirement.

Constitutive relation and particle size distribution model of rock fragments in the goaf - Qian Liu; Baiquan Lin; Yan Zhou; Yanjun Li (Environmental Science and Pollution Research, 2023)

Dietary cholesterol enhances osmoregulation, antioxidant defenses and immune response of Litopenaeus vannamei to alleviate the macromolecular damage induced by salinity stress - Chen Su; Jinbao Li; Mengyu Zhang; Luqing Pan; Yuxuan Wang; Yanjun Ding; Zhifei Chen; Mingxiang Lu (Aquaculture, 2023)

Cobalt induces neurodegenerative damages through impairing autophagic flux by activating hypoxia-inducible factor-1α triggered ROS overproduction - Jianping Tang; Yanjun Li; Xu Liu; Guangxia Yu; Fuli Zheng; Zhenkun Guo; Yating Zhang; Wenya Shao; Siying Wu; Huangyuan Li (Science of The Total Environment, 2023)

Scalable fabrication of efficient and recycling wood residue-derived sponge for crude oil adsorption - Ying Shang; Runan Gao; Yaoxing Wang; Xiaofei Dong; Xueqi Li; Jianfu Tang; Xuan Wang; Jiuqing Liu; Yanjun Xie; Jian Li; Wentao Gan (Journal of Hazardous Materials, 2023)

Do behavioural interventions enhance waste recycling practices? Evidence from an extended meta-analysis - Ziqian Xia; Yanjun Gu; Jiangnan Li; Jinliang Xie; Fangyi Liu; Xing Wen; Xi Tian; Chao Zhang (Journal of Cleaner Production, 2023)

Review on recent progress in on-line monitoring technology for atmospheric pollution source emissions in China - Huanqin Wang; Jitong Zhou; Xue Li; Qiang Ling; Hongyuan Wei; Lei Gao; Ying He; Ming Zhu; Xiao Xiao; Youjiang Liu; Shan Li; Chilai Chen; et al. (Journal of Environmental Sciences, 2023)

Mixed heavy metals exposure affects the renal function mediated by 8-OHG: A cross-sectional study in rural residents of China - Xiaoyu Tian; Xiaobing Shan; Li Ma; Chenyang Zhang; Mei Wang; Jie Zheng; Ruoyi Lei; Li He; Jun Yan; Xun Li; Yanjun Bai; Keqin Hu; et al. (Environmental Pollution, 2023)

Ultrafast Self-propelling directionally water transporting wood via cell wall reshaping for water manipulation - Zhe Qiu; Fanjun Yu; Dan Xu; Zengbin Wang; Junya Huang; Shuo Wang; Yanxiao Yang; Yonggui Wang; Jian Li; Zefang Xiao; Yanjun Xie; Kai Zhang (Chemical Engineering Journal, 2023)

High performance Na3V2(PO4)3 with nitrogen-chlorine co-doped carbon matrix in-situ synthesized in chitosan quaternary ammonium hydrogel for sodium ion batteries - Jiahao Li; Yanjun Chen; Shengnan He; Yaxiong Yang; Yanzhong Wang; Li Guo (Chemical Engineering Journal, 2023)

Unravelling the regulation mechanism of nanoflower shaped Na3V2(PO4)3 in methanol–water system for high performance sodium ion batteries - Shiqi Sun; Yanjun Chen; Qiang Bai; Zhen Tian; Que Huang; Changcheng Liu; Shengnan He; Yaxiong Yang; Yanzhong Wang; Li Guo (Chemical Engineering Journal, 2023)

Scalable, large-size, and flexible transparent bamboo - Kaili Wang; Haozhe Peng; Qiyu Gu; Xinzhi Zhang; Xiaorong Liu; Youming Dong; Yahui Cai; Yanjun Li; Jianzhang Li (Chemical Engineering Journal, 2023)

Association between air pollutants and neural tube defects during pregnancy in Lanzhou, China: a time series analysis - Yan Yang; Li Zhou; Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Pan; Yanbei Huo; Ruijuan Wang; Yupei Ba; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2023)

Farmland quality assessment using deep fully convolutional neural networks - Junxiao Wang; Xingong Li; Xiaorui Wang; Shenglu Zhou; Yanjun Luo (Environmental Monitoring and Assessment, 2023)

Immunomodulatory Function of Egg White Peptides in RAW264.7 Macrophage Cells and Immunosuppressive Mice Induced by Cyclophosphamide - Fan Zhang; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (International Journal of Peptide Research and Therapeutics, 2022)

The increasing big gap of carbon sink between the western and eastern Pacific in the last three decades - Guorong Zhong; Xuegang Li; Jinming Song; Baoxiao Qu; Fan Wang; Yanjun Wang; Bin Zhang; Detong Tian; Jun Ma; Huamao Yuan; Liqin Duan; Ning Li; et al. (Frontiers in Marine Science, 2022)
The Pacific Ocean is one of the important carbon sink regions, and there is a significant west-east difference in sea-air CO 2 flux. However, the influence of the long-standing greater CO 2 uptakes in the western Pacific than in the east and the dynamic change of this west-east difference remain unclear. In this paper, using the gridded surface ocean p CO 2 product constructed by the stepwise FFNN algorithm, we reported an increasing west-east CO 2 flux difference from 0.41 PgC yr -1 in 1992 to 0.73 PgC yr -1 in 2020. This increase was mainly attributed to the strengthening western Pacific carbon sink and relatively stable eastern Pacific carbon source. During El Nino events, the west-east CO 2 flux difference decreased significantly in a few years, and it then rose back rapidly when El Nino events ended. In addition, the increasing west-east difference in CO 2 uptakes during the last three decades did not lead to a higher acidification speed in the western surface temperate Pacific than the east. The greater CO 2 absorbed in the west was mainly transported to the deeper waters and caused a more significant carbon inventory change at 200-600 m than the eastern Pacific.

MLRD-Net: 3D multiscale local cross-channel residual denoising network for MRI-based brain tumor segmentation - Xue Chen; Yanjun Peng; Yanfei Guo; Jindong Sun; Dapeng Li; Jianming Cui (Medical & Biological Engineering & Computing, 2022)

In vitro and in vivo efficacy of cefiderocol plus tigecycline, colistin, or meropenem against carbapenem-resistant Acinetobacter baumannii - Wentao Ni; Yifan Wang; Xinqian Ma; Yukun He; Jin Zhao; Jie Guan; Yanjun Li; Zhancheng Gao (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Discovery of the oncogenic MDM2, a direct binding target of berberine and a potential therapeutic, in multiple myeloma - Chuting Li; Ru Su; Xiuyuan Wang; Guiping Huang; Yanjun Liu; Juhua Yang; Zhao Yin; Chunming Gu; Jia Fei (Functional & Integrative Genomics, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Time series analysis on association between ambient air pollutants and orofacial clefts during pregnancy in Lanzhou, China - Yanyan Liu; Li Zhou; Wenling Zhang; Yanjun Yang; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2022)

Investigation of Energy Losses Induced by Non-Uniform Inflow in a Coastal Axial-Flow Pump - Fan Meng; Yanjun Li; Jia Chen (Journal of Marine Science and Engineering, 2022)
A non-uniform velocity profile occurs at the inlet of a coastal axial-flow pump which is placed downstream of the forebay with side-intake. As a result, the actual efficiency and head of the pump is dissimilar to the design parameters, and the lack of the theoretical investigation on the relationship between inflow distortion and energy losses restricts the application of the coastal axial-flow pump in the drainage project. In this paper, the unsteady numerical simulation and entropy production theory are employed to obtain the internal flow structure and quantify energy losses, respectively, with three inflow deflection angles (θ = 0°, 15°, or 30°). It is reported that the best efficiency point (BEP) shifts to large flow rate with θ increasing, due to the decline of the velocity component in axial direction at the impeller inlet. Therefore, the total entropy production (TEP) of the coastal axial-flow pump rises with θ increasing under small flow rates, but it decreases with θ increasing under large flow rates. The high total entropy production rate (TEPR) in the vicinity of the tailing edge of the impeller and guide vanes rises with θ increasing, caused by the enhanced wake vortex strength. In addition, the high TEPR area near the inlet of outflow conduit rises with θ increasing, originated from the improvement of secondary vortices intensity.

Quantification and distribution of extractable metals of MSWI bottom ash in view of its valorization in China - Yanjun Hu; Lingqin Zhao; Qianqian Guo; Lianming Li; Yihong Wang; Yufan Ye; Fuzhi Mao; Wangyang Tian (Waste Disposal & Sustainable Energy, 2022)

Molecular studies of cellulose synthase supercomplex from cotton fiber reveal its unique biochemical properties - Xingpeng Wen; Yufeng Zhai; Li Zhang; Yanjun Chen; Zhiyuan Zhu; Gang Chen; Kun Wang; Yuxian Zhu (Science China Life Sciences, 2022)

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

Formation and evolution of secondary particulate matter during heavy haze pollution episodes in winter in a severe cold climate region of Northeast China - Ye Hong; Junying Sun; Yanjun Ma; Yangfeng Wang; Xiaolan Li; Yunhai Zhang; Ningwei Liu; Deping Zhou (Environmental Science and Pollution Research, 2022)

Circular RNA circPBX3 promotes cisplatin resistance of ovarian cancer cells via interacting with IGF2BP2 to stabilize ATP7A mRNA expression - Lihua Fu; Dan Zhang; Nuo Yi; Yanjun Cao; Yaxian Wei; Wenjing Wang; Li Li (Human Cell, 2022)

Comparison in phytoplankton diversity-productivity-community stability between river-type reservoir and lake-type reservoir - Qiong Wu; Qiuhua Li; Huan Luo; Qian Chen; Huaxiang Chen; Yanjun Dong; Shenghua Li (Journal of Oceanology and Limnology, 2022)

Fracture Mechanical Properties of Frozen Sandstone at Different Initial Saturation Degrees - Ting Wang; Qiang Sun; Hailiang Jia; Yanjun Shen; Guoyu Li (Rock Mechanics and Rock Engineering, 2022)

Research on Trajectory Tracking Control of Underwater Vehicle Manipulator System Based on Model-Free Adaptive Control Method - Gang Xue; Yanjun Liu; Zhenjie Shi; Lei Guo; Zhitong Li (Journal of Marine Science and Engineering, 2022)
In order to improve the trajectory tracking accuracy of an Underwater Vehicle Manipulator System (UVMS) under uncertain disturbance conditions of ocean current, a Model-free Adaptive Control (MFAC) method was used. Combined with Radial Basis Function Neural Networks (RBFNN), the RBFNN-MFAC method is proposed to improve the performance of the controller. A hydrodynamic model of UVMS was defined in the commercial software, Fluent, to calculate hydrodynamics disturbance, and the mechanism of the dynamic model of UVMS was defined in the commercial software, Adams, to simulate the motion of UVMS. The trajectory tracking performance with various control schemes, including PID (Proportional Integral Derivative), MFAC and RBFNN-MFAC, were analyzed with the Adams and Simulink joint simulation model. The results show that the position tracking accuracy and the speed tracking accuracy with the MFAC control scheme were 68.1% and 81.0% better, respectively, than those with PID control scheme. The position tracking accuracy and the speed tracking accuracy with the RBFNN-MFAC control scheme were 66.3% and 43.1% better, respectively, than those with the MFAC control scheme. The MFAC control scheme and the RBFNN-MFAC control scheme proposed in this paper exhibit good trajectory tracking performance without the precise dynamic model of UVMS, which is of great importance to applications in engineering.

Complex Conductivity Tomography for the Identification of Filling Materials in a Karst Pipeline - Wei Liu; Qiyou Zhou; Yanjun Chang; Zhihua Li; Fuping Gan (Pure and Applied Geophysics, 2022)

The edited UPF1 is correlated with elevated asparagine synthetase in pancreatic ductal adenocarcinomas - Jiayang Hu; Zhen Wang; Shunchao Yang; Yanjun Lu; Gang Li (Molecular Biology Reports, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Investigation on oxygen-controlled sewage sludge carbonization with low temperature: from thermal behavior to three-phase product properties - Fan Yu; Yanjun Hu; Lianming Li; Qianqian Guo; Yonghao Zhu; Long Jiao; Yihong Wang; Xiaoqiang Cui (Environmental Science and Pollution Research, 2022)

Numerical Study on the Influence of Tropical Cyclone Characteristics on the Sea State and Sea Surface Roughness inside the Tropical Cyclones - Shuiqing Li; Rui Li; Yanjun Wang; Jiuyou Lu (Journal of Marine Science and Engineering, 2022)
The development of wind wave (i.e., sea state) inside an intense tropical cyclone (TC) is the dominant contributor to the sea surface roughness and thus significantly impacts the air–sea interaction. The sea state is known to vary with TC characteristics (intensity, size, and translation speed); however, comprehensive knowledge of the influence of TC characteristics on the sea state and sea surface roughness is quite limited, largely because of the lack of observations. In this study, numerical experiments are performed to investigate the influence of TC characteristics on the sea state and the sea surface roughness under a range of idealized TCs. The numerical results indicate that the sea states are systematically younger for a more intense or smaller TC, and their azimuthal variation is predominantly determined by the TC translation. The dependence of the sea surface roughness on wind speed shows systematic variations with the TC characteristics, which are most significant for a moderately moving TC.

Identification of Benign and Malignant Lung Nodules in CT Images Based on Ensemble Learning Method - Yifei Xu; Shijie Wang; Xiaoqian Sun; Yanjun Yang; Jiaxing Fan; Wenwen Jin; Yingyue Li; Fangchu Su; Weihua Zhang; Qingli Cui; Yanhui Hu; Sheng Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Projecting future changes in extreme climate for maize production in the North China Plain and the role of adjusting the sowing date - Dengpan Xiao; Huizi Bai; De Li Liu; Jianzhao Tang; Bin Wang; Yanjun Shen; Jiansheng Cao; Puyu Feng (Mitigation and Adaptation Strategies for Global Change, 2022)

Constraint relationship of ecosystem services in the Yangtze River Economic Belt, China - Zihui Li; Dongjie Guan; Lilei Zhou; Yanjun Zhang (Environmental Science and Pollution Research, 2022)

Dysregulated lncRNA and mRNA may promote the progression of ischemic stroke via immune and inflammatory pathways: results from RNA sequencing and bioinformatics analysis - Yingshuang Wang; Feifei Feng; Pingping Zheng; Lijuan Wang; Yanjun Wang; Yaogai Lv; Li Shen; Kexin Li; Tianyu Feng; Yang Chen; Zhigang Liu; Yan Yao (Genes & Genomics, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Major histocompatibility complex class II genetic diversity and the genetic influence on gut microbiota in Guizhou minipigs - Gang Yao; Min Fan; Jian Zhang; Yanjun Wu; Hai Zhao; Hui Zhang; Longfei Li; Shuguang Wu (Folia Microbiologica, 2021)

Co-pyrolysis of waste printed circuit boards with iron compounds for Br-fixing and material recovery - Weifang Chen; Yongkai Shu; Yonglun Li; Yanjun Chen; Jianbo Wei (Environmental Science and Pollution Research, 2021)

The association between fine particulate matter and acute lower respiratory infections in Yancheng City, China - Jin Zhuang; Hongjian Bai; Jian Sun; Ting Zhang; Jingjing Li; Yanjun Chen; Haiyan Zhang; Qian Sun (Environmental Science and Pollution Research, 2021)

Performance comparison of ejectors in ejector-based refrigeration cycles with R1234yf, R1234ze(E) and R134a - Shizhen Li; Yingxin Liu; Yanjun Liu; Jingzhi Zhang (Environmental Science and Pollution Research, 2021)

Variation of summer precipitation δ 18 O on the Chinese Loess Plateau since the last interglacial - Zeke Zhang; Gaojun Li; Yanjun Cai; Zhengyu Liu; Zhisheng An (Journal of Quaternary Science, 2021)
Orbital‐scale East Asian Summer Monsoon (EASM) variations inferred from loess deposits in northern China and speleothems from southern China display different dominant periods, complicating our understanding of monsoon response to insolation and ice‐volume forcings. Here we integrate a new microcodium δ 18 O record from a high‐resolution last interglacial loess profile with previously published data and provide a composite microcodium δ 18 O record on the Chinese Loess Plateau (CLP) since the last interglacial. The composite microcodium δ 18 O record displays distinct precessional cycles, consistent with speleothem δ 18 O records, but with different amplitude contrast (particularly during the peak interglacials). We propose that both loess and speleothem δ 18 O records exhibit covariations at precessional timescale oscillations. The discrepancy between loess and speleothem from southern China can be attributed to the influences of other processes besides summer precipitation on the proxies. A slight difference in amplitude between microcodium and speleothem δ 18 O records implies that the EASM is also influenced by inland surface boundary conditions, which has important impacts on the occurrence of EASM precipitation. Therefore, microcodium δ 18 O from the Chinese loess–paleosol sequences can be regarded as a representative proxy of EASM precipitation in northern China and then a reliable proxy reflecting the variation of EASM intensity.

Molecular phylogenetics and evolutionary history of Sinocyclocheilus (Cypriniformes: Cyprinidae) species within Barbinae in China - Na Yang; Yingwen Li; Zhihao Liu; Qiliang Chen; Yanjun Shen (Environmental Biology of Fishes, 2021)

Research on Optimization and Verification of the Number of Stator Blades of kW Ammonia Working Medium Radial Flow Turbine in Ocean Thermal Energy Conversion - Yun Chen; Yanjun Liu; Wei Yang; Yiming Wang; Li Zhang; Yongpeng Wu (Journal of Marine Science and Engineering, 2021)
Ocean Thermal Energy Conversion (OTEC) is one of the emerging industries of ocean energy and an important link in carbon neutrality. Turbine is a key component of ocean thermal energy conversion, which has an important impact on the performance and energy conversion efficiency of the system. This paper fully considers the application characteristics of ocean thermal energy conversion and the state conversion characteristics of ammonia working fluid. Taking the 100 kW radial inflow turbine in the OTEC application system as an example, based on the design, the turbine is optimized for the key parameters of the turbine stator and the influence of different geometric parameters is analyzed. Subsequently, the optimization results are verified by CFD numerical simulation analysis under different conditions. The results show that the number of stator blades has an important influence on the performance of the turbine. Further optimization studies have shown that through optimization, when the number of stator blades is 33, the internal flow field performance is the best, and the working conditions of the inlet and outlet working fluids are in accordance with the design points without obvious shock wave and reverse flow phenomenon, the efficiency is 89.46%, 3.94% higher than the design value.

Fracture recognition in ultrasonic logging images via unsupervised segmentation network - Wei Zhang; Tong Wu; Zhipeng Li; Shiyuan Liu; Ao Qiu; Yanjun Li; Yibing Shi (Earth Science Informatics, 2021)

Characteristics and Causes of Extreme Rainfall Induced by Binary Tropical Cyclones over China - Mingyang Wang; Fumin Ren; Yanjun Xie; Guoping Li; Ming-Jen Yang; Tian Feng (Asia-Pacific Journal of Atmospheric Sciences, 2021)
Binary tropical cyclones (BTC) often bring disastrous rainfall to China. From the viewpoint of the extreme of the BTC maximum daily rainfall, the characteristics of BTC extreme rainfall (BTCER) during 1960–2018 are analyzed, using daily rainfall data; and some representative large-scale mean flows, in which the associated BTCs are embedded, are analyzed. Results show that the frequency of BTCER shows a decreasing trend [−0.49 (10 yr) −1 ] and is mainly distributed within the BTC heavy rainstorm interval (100 mm ≤ BTCER

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Orbital-scale Asian summer monsoon variations: Paradox and exploration - Hai Cheng; Haiwei Zhang; Yanjun Cai; Zhengguo Shi; Liang Yi; Chenglong Deng; Qingzhen Hao; Youbing Peng; Ashish Sinha; Hanying Li; Jingyao Zhao; Ye Tian; et al. (Science China Earth Sciences, 2021)

Three-Dimensional Performance Analysis of a Radial-Inflow Turbine for Ocean Thermal Energy Conversion System - Yun Chen; Yanjun Liu; Li Zhang; Xiaowei Yang (Journal of Marine Science and Engineering, 2021)
Turbine is one of the key components of the ocean thermal energy conversion system (OTEC), and its aerodynamic performance and geometric dimension affect the performance of the system directly. This paper proposes a design method for the radial inflow turbine suitable for the ocean thermal energy conversion based on the parameter optimization of the ocean thermal energy conversion system. Aiming at the application characteristics of marine thermal energy conversion in a small temperature difference environment and the special thermophysical properties of the organic working fluid in this environment, one-dimensional design and three-dimensional CFD analysis of the turbine is separately done, of which the results were compared. At the same time, the performance of the turbine was verified by changing the inlet and outlet conditions of the radial turbine under the design conditions. The conclusion is that the three-dimensional CFD results of the turbine are in good agreement with the one-dimensional design, and the internal flow field of the turbine is stable, without obvious backflow and eddy current, which meets the application requirements of the ocean thermal energy conversion.

Identification of hub lncRNA ceRNAs in multiple sclerosis based on ceRNA mechanisms - Yanjun Ding; Taotao Li; Xinwei Yan; Mintian Cui; Chao Wang; Situo Wang; Fengmin Zhang; Ruijie Zhang (Molecular Genetics and Genomics, 2021)

Stimulation of melanin synthesis by UVB is mediated by NO/cGMP/PKG cascade targeting PAK4 in vitro - Linli Xue; Lucheng Chang; Yilei Li; Yanjun Dong; Xiaoyan He (In Vitro Cellular & Developmental Biology - Animal, 2021)

MiR-30a suppresses clear cell renal cell carcinoma proliferation and metastasis by targeting LRP6 - Yanjun Ren; Li Zhang; Wei Zhang; Yikai Gao (Human Cell, 2021)

Source Apportionment and Ecological-Health Risks Assessment of Heavy Metals in Topsoil Near a Factory, Central China - Jia Li; Guangcai Wang; Fei Liu; Linfeng Cui; Yanjun Jiao (Exposure and Health, 2021)

Mechanical Properties of Acid-corroded Sandstone Under Uniaxial Compression - Shuguang Li; Yingming Wu; Runke Huo; Zhanping Song; Yoshiaki Fujii; Yanjun Shen (Rock Mechanics and Rock Engineering, 2021)

Variations of soil organic matters and plant cuticular waxes along an altitude gradient in Qinghai-Tibet Plateau - Luhua Yao; Na Guo; Yuji He; Yu Xiao; Yang Li; Jianhua Gao; Yanjun Guo (Plant and Soil, 2021)

Spatial–temporal differences in disaster perception and response among new media users and the influence factors: a case study of the Shouguang Flood in Shandong province - Shuolin Geng; Qi Zhou; Mingjie Li; Dianxing Song; Yanjun Wen (Natural Hazards, 2021)

Effectiveness of predicting spatial contaminant distributions at industrial sites using partitioned interpolation method - Pengwei Qiao; Sucai Yang; Wenxia Wei; Peizhong Li; Yanjun Cheng; Shuang Liang; Mei Lei; Tongbin Chen (Environmental Geochemistry and Health, 2021)

Establishment of an Objective Standard for the Definition of Binary Tropical Cyclones in the Western North Pacific - Fumin Ren; Yanjun Xie; Biwen Yin; Mingyang Wang; Guoping Li (Advances in Atmospheric Sciences, 2020)

A multiple-proxy stalagmite record reveals historical deforestation in central Shandong, northern China - Liangcheng Tan; Wen Liu; Tianli Wang; Peng Cheng; Jingjie Zang; Xiqian Wang; Le Ma; Dong Li; Jianghu Lan; R. Lawrence Edwards; Hai Cheng; Hai Xu; et al. (Science China Earth Sciences, 2020)

Application of deep learning in ecological resource research: Theories, methods, and challenges - Qinghua Guo; Shichao Jin; Min Li; Qiuli Yang; Kexin Xu; Yuanzhen Ju; Jing Zhang; Jing Xuan; Jin Liu; Yanjun Su; Qiang Xu; Yu Liu (Science China Earth Sciences, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Dexmedetomidine had neuroprotective effects on hippocampal neuronal cells via targeting lncRNA SHNG16 mediated microRNA-10b-5p/BDNF axis - Li Wang; Weihua Liu; Yanjun Zhang; Zhanfei Hu; Hao Guo; Jingshu Lv; Hongyin Du (Molecular and Cellular Biochemistry, 2020)
Dexmedetomidine (DEX), a highly selective alpha2 adrenergic receptor agonist, is a commonly used anesthetic drug in surgical procedures. Previous studies have indicated that DEX exerts neuroprotective effects while the detailed mechanism has not been fully elucidated. Here, we aim to study the role of lncRNA SHNG16 in DEX-induced brain protection and its underlying molecular mechanism. The rats underwent middle cerebral artery occlusion (MCAO) surgery and oxygen–glucose deprivation (OGD)-treated HT22 hippocampal neurons were treated with DEX, respectively. CCK8 was used to evaluate cell viability. sh-SHNG16 as well as miR-10b-5p mimics were transfected into hippocampal neurons to further explore the bio-function of SNHG16 and miR-10b-5p in vitro. Furthermore, the interactions between SHNG16 and miR-10b-5p, miR-10b-5p and BDNF gene were confirmed by dual-luciferase report assay. Our data revealed that DEX attenuated neurological damage of the MCAO rats and also increased the cell viability of the neurons significantly. Besides, expression of SHNG16 and BDNF were both downregulated while miR-10b-5p was upregulated in MCAO brain tissues or OGD treated neurons. DEX inhibited miR-10b-5p expression but increased SHNG16 and BDNF levels with a dosage effect. After transfection with sh-SHNG16 or miR-10b-5p mimics, the expression of BDNF protein was downregulated, accompanied with decreased neuron viability. Dual-luciferase assay showed that SHNG16 targeted on miR-10b-5p, which also could bind directly to the 3′-UTR sites of BDNF and negatively regulate its expression. In conclusion, DEX exerts neuroprotective in ischemic stroke via improving neuron damage, the underlying mechanism may be upregulating SHNG16 and BDNF via sponging miR-10b-5p.

Faba Bean Organs Differed in Their Effects on Maize Seed Germination Rate and Soil Microbial Activities as well as Their Decomposition Patterns in a Regosol Soil - Zhibin He; Luhua Yao; Xuefeng Zhang; Yang Li; Dengke Wang; Lin Kang; Cui Cui; Aiying Huang; Ruiji Yang; Qianlin Xiao; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2020)

Origin and depositional paleoenvironment of Triassic polyhalite in the Jialingjiang Formation, Sichuan Basin - Yanjun Zhao; Chenglin Liu; Ting Ding; Luis A. Gonzalez; Zhaoqi Li; Mingquan Wang; Licheng Wang; Zhengjie Zhu (Carbonates and Evaporites, 2020)

Genome-wide association study of soybean seed germination under drought stress - Zhangxiong Liu; Huihui Li; Zuowang Gou; Yanjun Zhang; Xingrong Wang; Honglei Ren; Zixiang Wen; Beom-Kyu Kang; Yinghui Li; Lili Yu; Huawei Gao; Dechun Wang; et al. (Molecular Genetics and Genomics, 2020)

A transcriptomic analysis of Nsmce1 overexpression in mouse hippocampal neuronal cell by RNA sequencing - Mengting Gong; Zhen Wang; Yanjun Liu; Wenxing Li; Shoudong Ye; Jie Zhu; Hui Zhang; Jing Wang; Kan He (Functional & Integrative Genomics, 2020)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

The complete mitochondrial genome of Cobitis macrostigma (Cypriniformes: Cobitidae: Cobitinae) and a phylogenetic implication for its closely related species - Na Yang; Yingwen Li; Zhihao Liu; Qiliang Chen; Yanjun Shen (Biologia, 2020)

Permeability dynamic variation of coal under various confining pressures using LFNMR relaxation method - Peng Xia; Fangui Zeng; Xiaoxia Song; Beilei Sun; Taotao Yan; Wei Li; Yanjun Meng (Arabian Journal of Geosciences, 2020)

Growing‐season temperature and precipitation are independent drivers of global variation in xylem hydraulic conductivity - Pengcheng He; Sean M. Gleason; Ian J. Wright; Ensheng Weng; Hui Liu; Shidan Zhu; Mingzhen Lu; Qi Luo; Ronghua Li; Guilin Wu; Enrong Yan; Yanjun Song; et al. (Global Change Biology, 2020)
Stem xylem‐specific hydraulic conductivity ( K S ) represents the potential for plant water transport normalized by xylem cross section, length, and driving force. Variation in K S has implications for plant transpiration and photosynthesis, growth and survival, and also the geographic distribution of species. Clarifying the global‐scale patterns of K S and its major drivers is needed to achieve a better understanding of how plants adapt to different environmental conditions, particularly under climate change scenarios. Here, we compiled a xylem hydraulics dataset with 1,186 species‐at‐site combinations (975 woody species representing 146 families, from 199 sites worldwide), and investigated how K S varied with climatic variables, plant functional types, and biomes. Growing‐season temperature and growing‐season precipitation drove global variation in K S independently. Both the mean and the variation in K S were highest in the warm and wet tropical regions, and lower in cold and dry regions, such as tundra and desert biomes. Our results suggest that future warming and redistribution of seasonal precipitation may have a significant impact on species functional diversity, and is likely to be particularly important in regions becoming warmer or drier, such as high latitudes. This highlights an important role for K S in predicting shifts in community composition in the face of climate change.

Influence of Pore Water (Ice) Content on the Strength and Deformability of Frozen Argillaceous Siltstone - Hailiang Jia; Fan Zi; Gengshe Yang; Guoyu Li; Yanjun Shen; Qiang Sun; Pengyu Yang (Rock Mechanics and Rock Engineering, 2020)

An improved minimum bounding rectangle algorithm for regularized building boundary extraction from aerial LiDAR point clouds with partial occlusions - Maolin Feng; Tonggang Zhang; Shichao Li; Guoqing Jin; Yanjun Xia (International Journal of Remote Sensing, 2020)

Comparison of common spatial interpolation methods for analyzing pollutant spatial distributions at contaminated sites - Pengwei Qiao; Peizhong Li; Yanjun Cheng; Wenxia Wei; Sucai Yang; Mei Lei; Tongbin Chen (Environmental Geochemistry and Health, 2019)

Tropical cyclone damages in Mainland China over 2005–2016: losses analysis and implications - Hong Wang; Min Xu; Anselem Onyejuruwa; Yanjun Wang; Shanshan Wen; Andrew E. Gao; Yubin Li (Environment, Development and Sustainability, 2019)

Spatiotemporal Variations and Regional Transport of Air Pollutants in Two Urban Agglomerations in Northeast China Plain - Xiaolan Li; Xiaoming Hu; Shuaiyi Shi; Lidu Shen; Lan Luan; Yanjun Ma (Chinese Geographical Science, 2019)

Rising grain prices in response to phased climatic change during 1736–1850 in the North China Plain - Yanjun Wen; Xiuqi Fang; Yang Liu; Yikai Li (Science China Earth Sciences, 2019)

Impact of COMT haplotypes on functional connectivity density and its association with the gene expression of dopamine receptors - Jie Tang; Yanjun Li; Jiayuan Xu; Wen Qin; Qian Su; Qiang Xu; Bing Liu; Tianzi Jiang; Chunshui Yu (Brain Structure and Function, 2019)

Characteristics of the Tibetan Plateau vortices and the related large-scale circulations causing different precipitation intensity - Lun Li; Renhe Zhang; Min Wen; Jianping Duan; Yanjun Qi (Theoretical and Applied Climatology, 2019)

Molecular epidemiology of enterovirus from children with herpangina or hand, foot, and mouth disease in Hangzhou, 2016 - Wei Li; Cixiu Li; Lifang Liu; Xia Liu; Shiqiang Shang; Haiyan Mao; Yanjun Zhang (Archives of Virology, 2019)

Interannual relationship between intensity of rainfall intraseasonal oscillation and summer-mean rainfall over Yangtze River Basin in eastern China - Yanjun Qi; Tim Li; Renhe Zhang; Yang Chen (Climate Dynamics, 2019)

Is Chinese stalagmite δ18O solely controlled by the Indian summer monsoon? - Dong Li; Liangcheng Tan; Yanjun Cai; Xiuyang Jiang; Le Ma; Hai Cheng; R. Lawrence Edwards; Haiwei Zhang; Yongli Gao; Zhisheng An (Climate Dynamics, 2019)

Potential sources and associated risk assessment of potentially toxic elements in paddy soils of a combined urban and rural area - Yanjun Chai; Yan Li; Xiaolei Chen; Jin Zhang; Peter Christie; Ka Lai Chow; Chao Ai; Shengdao Shan (Environmental Science and Pollution Research, 2019)

Application of Avaatech X-ray fluorescence core-scanning in Sr/Ca analysis of speleothems - Dong Li; Liangcheng Tan; Fei Guo; Yanjun Cai; Youbin Sun; Gang Xue; Xing Cheng; Hong Yan; Hai Cheng; R. Lawrence Edwards; Yongli Gao; Jessica Kelley (Science China Earth Sciences, 2019)

Depletion of collagen by losartan to improve tumor accumulation and therapeutic efficacy of photodynamic nanoplatforms - Yuxia Tang; Ying Liu; Shouju Wang; Ying Tian; Yanjun Li; Zhaogang Teng; Guangming Lu (Drug Delivery and Translational Research, 2019)

Effects of the configuration of a baffle–avalanche wall system on rock avalanches in Tibet Zhangmu: discrete element analysis - YuZhang Bi; SiMing He; YanJun Du; XinPo Sun; XinPo Li (Bulletin of Engineering Geology and the Environment, 2019)

Cloning, Expression, and Bioinformatics Analysis of Heavy Metal Resistance Gene afe_1862 from Acidithiobacillus ferrooxidans L1 in Escherichia coli - Feifan Leng; Yuanli Li; Wen Luo; Qingwei Wei; Yanjun Jing; Xiaoli Wang; Mingjun Yang; Yonggang Wang (Biological Trace Element Research, 2019)

Flotation and adsorption of quartz with the new collector butane-3-heptyloxy-1,2-diamine - Zhouyueyang Cheng; Yimin Zhu; Yanjun Li; Yuexin Han (Mineralogy and Petrology, 2019)

Water-soluble ion components of PM10 during the winter-spring season in a typical polluted city in Northeast China - Ye Hong; Yanjun Ma; Junying Sun; Chaoliu Li; Yunhai Zhang; Xiaolan Li; Deping Zhou; Yangfeng Wang; Ningwei Liu (Environmental Science and Pollution Research, 2019)

Developing a comprehensive evaluation method for Interconnected River System Network assessment: A case study in Tangxun Lake group - Wei Yang; Liping Zhang; Yanjun Zhang; Zongli Li; Yi Xiao; Jun Xia (Journal of Geographical Sciences, 2019)

Primary limitation on vegetation productivity shifts from precipitation in dry years to nitrogen in wet years in a degraded arid steppe of Inner Mongolia, northern China - Lei Huang; Dangjun Wang; Luhua Yao; Xiaoting Li; Dengke Wang; Qingfeng Du; Yong Zhang; Xiangyang Hou; Yanjun Guo (Journal of Soils and Sediments, 2019)

An engineering site suitability index (ESSI) for the evaluation of geological situations based on a multi-factor interaction matrix - Kun Li; Yanjun Shang; Wantong He; Daming Lin; Muhammad Hasan; Kaiyang Wang (Bulletin of Engineering Geology and the Environment, 2019)

Boreal Summer Intraseasonal Oscillation in the Asian–Pacific Monsoon Region Simulated in CAMS-CSM - Yanjun Qi; Renhe Zhang; Xinyao Rong; Jian Li; Lun Li (Journal of Meteorological Research, 2019)

Antioxidant Properties and Arsenic Speciation of Ultrafiltration and Nanofiltration Derived Abalone Viscera Hydrolysate Fraction - Wuyin Weng; Jieyu Li; Ting Li; Yanjun Ye (Journal of Aquatic Food Product Technology, 2019)

Structural characterisation of a full-length mitochondrial outer membrane TOM40 preprotein translocase: implications for its interaction with presequence peptides - Wei Feng; Jinwen Li; Yanjun Liang; Yongqiang Zhang; Shu Jie Li (European Biophysics Journal, 2019)

Tracking climate change in Central Asia through temperature and precipitation extremes - Man Zhang; Yaning Chen; Yanjun Shen; Baofu Li (Journal of Geographical Sciences, 2019)

The CAMS Climate System Model and a Basic Evaluation of Its Climatology and Climate Variability Simulation - Xinyao Rong; Jian Li; Haoming Chen; Yufei Xin; Jingzhi Su; Lijuan Hua; Tianjun Zhou; Yanjun Qi; Zhengqiu Zhang; Guo Zhang; Jianduo Li (Journal of Meteorological Research, 2018)

Determination of the geometrical REV based on fracture connectivity: a case study of an underground excavation at the Songta dam site, China - Yanyan Li; Jianping Chen; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2018)

Imidazole-Bearing Polymeric Micelles for Enhanced Cellular Uptake, Rapid Endosomal Escape, and On-demand Cargo Release - Di Lu; Yang An; Simin Feng; Xiaodan Li; Aiping Fan; Zheng Wang; Yanjun Zhao (AAPS PharmSciTech, 2018)

Numerical analysis of effect of baffle configuration on impact force exerted from rock avalanches - YuZhang Bi; YanJun Du; SiMing He; XinPo Sun; DongPo Wang; XinPo Li; Heng Liang; Yong Wu (Landslides, 2018)

Glyphosate application increased catabolic activity of gram-negative bacteria but impaired soil fungal community - Yehao Liu; Yongchun Li; Xiaomei Hua; Karin Müller; Hailong Wang; Tongyi Yang; Qiong Wang; Xin Peng; Mengcheng Wang; Yanjun Pang; Jinliang Qi; Yonghua Yang (Environmental Science and Pollution Research, 2018)

Transcriptome analysis of alternative splicing in different moso bamboo tissues - Long Li; Qianqian Shi; Dan Hou; Zhanchao Cheng; Juan Li; Yanjun Ma; Xueping Li; Shaohua Mu; Jian Gao (Acta Physiologiae Plantarum, 2018)

Mineralogy and geochemistry of ash and slag from coal gasification in China: a review - Shuqin Liu; Chuan Qi; Zhe Jiang; Yanjun Zhang; Maofei Niu; Yuanyuan Li; Shifeng Dai; Robert B. Finkelman (International Geology Review, 2018)

Comparison of Two Air Pollution Episodes over Northeast China in Winter 2016/17 Using Ground-Based Lidar - Yanjun Ma; Hujia Zhao; Yunsheng Dong; Huizheng Che; Xiaoxiao Li; Ye Hong; Xiaolan Li; Hongbin Yang; Yuche Liu; Yangfeng Wang; Ningwei Liu; Cuiyan Sun (Journal of Meteorological Research, 2018)

Characteristics of Boundary Layer Structure during a Persistent Haze Event in the Central Liaoning City Cluster, Northeast China - Xiaolan Li; Yangfeng Wang; Lidu Shen; Hongsheng Zhang; Hujia Zhao; Yunhai Zhang; Yanjun Ma (Journal of Meteorological Research, 2018)

Parameter optimization for carbon and water fluxes in two global land surface models based on surrogate modelling - Jianduo Li; Qingyun Duan; Ying‐Ping Wang; Wei Gong; Yanjun Gan; Chen Wang (International Journal of Climatology, 2018)
Errors are quite large in the simulated carbon and water fluxes obtained by global models used for the Fifth Assessment Report of the Intergovernmental Panel on Climate Change, and reducing those errors is important for improving our confidence about these models and their projections. Errors in model parameter values are a major cause of those large modelling errors but can be significantly reduced if model parameter values are optimized. While parameter optimizations have been carried out at local sites or regional scales, parameter optimizations have been rarely conducted at the global scale because of the high computing costs required to optimize a large (>100) number of model parameters. In this study, we used an adaptive surrogate modelling based optimization (ASMO) method to maximize the match between simulated monthly global gross primary production (GPP) and latent heat flux (LE) derived by two global land surface models (LSMs) and the model‐data products for global GPP and LE from the 1982–2008 period generated by the Max Plank Institute. The ASMO method only required a few hundred model runs to find the optimal values of all optimized parameters for the two global LSMs [the Australian Community Atmosphere‐Biosphere‐Land Exchange (CABLE) and joint UK land environment simulator (JULES)]. Our results show that up to 65% of the model errors can be reduced by parameter optimization for most of the plant functional types (PFTs) and that the model performances of CABLE and JULES are significantly improved at 72 and 93% of the land points, respectively. At last, we discuss the limitations of this work and recommend that parameter optimization based on surrogate modelling using various observational data sets and acceptable prior information of uncertainties in model structure and observations should be considered as a key step in improving the performance of global LSMs or model intercomparisons.

Changes in Extreme Maximum Temperature Events and Population Exposure in China under Global Warming Scenarios of 1.5 and 2.0°C: Analysis Using the Regional Climate Model COSMO-CLM - Mingjin Zhan; Xiucang Li; Hemin Sun; Jianqing Zhai; Tong Jiang; Yanjun Wang (Journal of Meteorological Research, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

Analysis of future drought characteristics in China using the regional climate model CCLM - Jinlong Huang; Jianqing Zhai; Tong Jiang; Yanjun Wang; Xiucang Li; Run Wang; Ming Xiong; Buda Su; Thomas Fischer (Climate Dynamics, 2018)

Modification of rock mass strength assessment methods and their application in geotechnical engineering - Daming Lin; Kaiyang Wang; Kun Li; Wantong He; Weixing Bao; Renmao Yuan; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2017)

Ectopic expression of cucumber (Cucumis sativus L.) CsTIR/AFB genes enhance salt tolerance in transgenic Arabidopsis - Zhehao Chen; Mengting Li; Ye Yuan; Jiangqin Hu; Yanjun Yang; Jiliang Pang; Lilin Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Regulatory roles of introns in fungicide sensitivity of Fusarium graminearum - Yanjun Li; Shunwen Luo; Xiaojing Jia; Yuanye Zhu; Dongming Chen; Yabing Duan; Yiping Hou; Mingguo Zhou (Environmental Microbiology, 2017)
Summary Although the roles of introns have been much debated in eukaryotic organisms, none of them have been functionally characterized in Fusarium graminearum . In this study, we characterized the roles of introns in regulation of fungicide‐sensitivity of F. graminearum . β 2 tub , cyp51A and myosin‐5 are important target genes of benzimidazoles, triazoles and cyanoacrylates respectively. To explore the sensitivity regulation functions of introns in target genes, several detailed deletion studies were completed on the intronic regions of β 2 tub , cyp51A and myosin‐5 . Phenotypic analyses showed that deletion of the fourth intron from β 2 tub gene (designated β 2 Δ i4 ), the sole intron from cyp51A gene ( cyp51A‐ Δ i ) and the second intron from myosin‐5 gene ( myo5‐ Δ i2 ) exhibited an increased sensitivity to corresponding fungicides. In contrast, deletion of the first or second intron from β 2 tub gene exhibited a decreased sensitivity to carbendazim. qRT‐PCR showed that the mRNA transcript levels of target genes were significantly downregulated in β 2 Δ i4 , cyp51A‐ Δ i and myo5‐ Δ i2 respectively. Meanwhile, Western blot assays revealed that the protein expression levels of β 2 tub was also dramatically reduced in β 2 Δ i4 , but accumulated in β 2 Δ i1 and β 2 Δ i2 . Overall, our results indicate that introns in target genes significantly regulate the fungicide‐sensitivity by influencing expression of the corresponding resident genes in F. graminearum .

Pharmacokinetics and immunogenicity of T0001, a newly developed anti-TNFα fusion protein, in healthy volunteers - Yitong Wang; Chang Liu; Shi Chen; Wei Wang; Lihou Dong; Qian Wang; Yan Wang; Libo Zhao; Yannan Zang; Zhenwei Xie; Yang Liu; Yanjun Liu; et al. (European Journal of Clinical Pharmacology, 2017)

Analysis of the spatial-temporal variation characteristics of vegetative drought and its relationship with meteorological factors in China from 1982 to 2010 - Qiu Shen; Liang Liang; Xiang Luo; Yanjun Li; Lianpeng Zhang (Environmental Monitoring and Assessment, 2017)

miR-138 promotes migration and tube formation of human cytomegalovirus-infected endothelial cells through the SIRT1/p-STAT3 pathway - Shanchao Zhang; Lei Liu; Ruijin Wang; Houzhen Tuo; Yanjun Guo; Li Yi; Dexin Wang; Jiawei Wang (Archives of Virology, 2017)

Identification of Methicillin-Resistant Staphylococcus aureus (MRSA) Using Simultaneous Detection of mecA, nuc, and femB by Loop-Mediated Isothermal Amplification (LAMP) - Changguo Chen; Qiangyuan Zhao; Jianwei Guo; Yanjun Li; Qiuyuan Chen (Current Microbiology, 2017)

Influential intensity of urban agglomeration on evolution of eco-environmental pressure: a case study of Changchun, China - Yanjun Liu; Jing Zhang; Chenggu Li; Guolei Zhou; Zhanhui Fu; Degang Liu (Chinese Geographical Science, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

An integrated UAV-borne lidar system for 3D habitat mapping in three forest ecosystems across China - Qinghua Guo; Yanjun Su; Tianyu Hu; Xiaoqian Zhao; Fangfang Wu; Yumei Li; Jin Liu; Linhai Chen; Guangcai Xu; Guanghui Lin; Yi Zheng; Yiqiong Lin; et al. (International Journal of Remote Sensing, 2017)

Two new coumarins from the bark of Streblus indicus (Bur.) Corner - Ruijie He; Shengping Deng; Hui Nie; Yan Huang; Buming Liu; Ruiyun Yang; Shuai Huang; Dexiong Zhou; Huangcan Chen; Jun Li; Yanjun Zhang (Natural Product Research, 2017)

Simulation and projection of climatic changes in the Indus River Basin, using the regional climate model COSMO‐CLM - Jinlong Huang; Yanjun Wang; Thomas Fischer; Buda Su; Xiucang Li; Tong Jiang (International Journal of Climatology, 2017)
In this article, the analysis of simulated and projected climatic changes in the Indus River Basin ( IRB ) is presented. The performance of the regional climate model COSMO‐CLM ( CCLM ) driven by the global circulation model MPI‐ESM‐LR is evaluated on the ability of reproducing temperature, precipitation, and wind pattern for the period 1961–2005. There exist quantitative biases, especially in precipitation pattern, which are associated to the diverse reproduction of the atmospheric circulation by the global circulation model. The overall results show that CCLM is able to satisfyingly capture the dominant spatial characteristics in annual temperature and precipitation time series, including the warming trend, and the seasonal variations. The changes in precipitation and temperature over the IRB are projected for the mid‐ (2046–2065) and late‐21st century (2081–2100). Relative to the baseline period (1986–2005), the average annual temperature will increase during the mid‐ and late‐21st century over the whole basin. Extreme temperature events, i.e. heat waves, are more likely to occur. An increase in summer temperature is also projected especially in the upper IRB , where the persistent increase is likely to cause further melting of glaciers. The annual precipitation will decrease in both the mid‐ and late‐21st century with significant spatial changes. A decrease in the monsoon precipitation is also projected, particularly in the central and southern plains of lower altitudes, which might be highly related to the reduction of wet air from the Indian Ocean and the increment in outflow to the east of the IRB . For winter and spring precipitation, except for the late‐21st century under the representative climate pathway (RCP) 2.6, a decreasing trend is projected, which might be caused by the reduction of water vapour from the west. This will further weaken the availability of water resources in these seasons, especially in the upper IRB of higher altitudes.

Physiological and anatomical responses of Phyllostachys vivax and Arundinaria fortunei (Gramineae) under salt stress - Wei Ge; Ying Zhang; Zhongyuan Sun; Juan Li; Guohua Liu; Yanjun Ma; Jian Gao (Brazilian Journal of Botany, 2017)

Deformation and failure of a tunnel in the restraining bend of a strike–slip fault zone: an example from Hengshan Mountain, Shanxi Province, China - Daming Lin; Renmao Yuan; Yanjun Shang; Weixing Bao; Kaiyang Wang; Zhongjian Zhang; Kun Li; Wantong He (Bulletin of Engineering Geology and the Environment, 2017)

Connectivity of Three-Dimensional Fracture Networks: A Case Study from a Dam Site in Southwest China - Yanyan Li; Jianping Chen; Yanjun Shang (Rock Mechanics and Rock Engineering, 2017)

Soaking in H2O2 regulates ABA biosynthesis and GA catabolism in germinating cotton seeds under salt stress - Xiangqiang Kong; Zhen Luo; Yanjun Zhang; Weijiang Li; Hezhong Dong (Acta Physiologiae Plantarum, 2017)

Expression Profiles of Pathogenesis-Related Gene, TaLr35PR1, as it Relate to Lr35-Mediated Adult Plant Leaf Rust Resistance - Xiaoying Li; Yanjun Zhang; Weihong Zhang; Jiarui Zhang; Haiyan Wang; Daqun Liu (Plant Molecular Biology Reporter, 2016)

Spatiotemporal distributions of influential tropical cyclones and associated economic losses in China in 1984–2015 - Yanjun Wang; Shanshan Wen; Xiucang Li; Fischer Thomas; Buda Su; Run Wang; Tong Jiang (Natural Hazards, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Structural block division for further deep research in coalbed methane development in the Gujiao area, Xishan coalfield, North China - Peng Xia; Fangui Zeng; Xiaoxia Song; Yanjun Meng; Kunjie Li; Jin Wang; Beilei Sun (Arabian Journal of Geosciences, 2016)

Identification and characterization of a β-1, 3-glucanase gene, TcLr19Glu, involved in wheat resistance against Puccinia triticina - Lin Gao; Shen Wang; Yanjun Zhang; Xiaoying Li; Haiyan Wang; Daqun Liu (Journal of Plant Biochemistry and Biotechnology, 2016)

ZmCCD7/ZpCCD7 encodes a carotenoid cleavage dioxygenase mediating shoot branching - Xiaoying Pan; Hongyan Zheng; Jianyu Zhao; Yanjun Xu; Xuexian Li (Planta, 2016)

The strong El Niño of 2015/16 and its dominant impacts on global and China's climate - Panmao Zhai; Rong Yu; Yanjun Guo; Qingxiang Li; Xuejuan Ren; Yaqiang Wang; Wenhui Xu; Yanju Liu; Yihui Ding (Journal of Meteorological Research, 2016)

Assessment of health-based economic costs linked to fine particulate (PM2.5) pollution: a case study of haze during January 2013 in Beijing, China - Yanjun Du; Tiantian Li (Air Quality, Atmosphere & Health, 2016)

Constitutive Expression of a Tomato Small Heat Shock Protein Gene LeHSP21 Improves Tolerance to High-Temperature Stress by Enhancing Antioxidation Capacity in Tobacco - Jiang Zhang; Haiyan Chen; Haihai Wang; Bei Li; Yanjun Yi; Fanjing Kong; Jiayao Liu; Hongxia Zhang (Plant Molecular Biology Reporter, 2016)

Isolation and functional characterization of seed-specific FAD2-1 promoter from cotton (Gossypium hirsutum L) - Feng Liu; YanPeng Zhao; Xiaodong Wang; Yanjun Li; Jie Sun (Journal of Plant Biochemistry and Biotechnology, 2015)

Seismic response of a four-storey RC school building with masonry-infilled walls - Kok Tong Tan; Hashim Abdul Razak; Dagang Lu; Yanjun Li (Natural Hazards, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Comparative genomic approach reveals novel conserved microRNAs in Inner Mongolia cashmere goat skin and longissimus dorsi - Rui Su; Shaoyin Fu; Yanjun Zhang; Ruijun Wang; Yanhong Zhou; Jinquan Li; Wenguang Zhang (Molecular Biology Reports, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Modeling demand/supply of water resources in the arid region of northwestern China during the late 1980s to 2010 - Xingran Liu; Yanjun Shen; Ying Guo; Shuo Li; Bin Guo (Journal of Geographical Sciences, 2015)

GIS-based effect assessment of soil erosion before and after gully land consolidation: A case study of Wangjiagou project region, Loess Plateau - Yansui Liu; Yanjun Guo; Yurui Li; Yuheng Li (Chinese Geographical Science, 2015)

Analysis of Gene Expression Provides Insights into the Mechanism of Cadmium Tolerance in Acidithiobacillus ferrooxidans - Minjie Chen; Yanjun Li; Li Zhang; Jianying Wang; Chunli Zheng; Xuefeng Zhang (Current Microbiology, 2015)

Division of the stages of coalbed methane desorption based on the Langmuir adsorption isotherm - Meng YanJun; Tang DaZhen; Qu YingJie; Xu Hao; Li Yong (Arabian Journal of Geosciences, 2015)

Applying support vector regression analysis on grip force level-related corticomuscular coherence - Yao Rong; Xixuan Han; Dongmei Hao; Liu Cao; Qing Wang; Mingai Li; Lijuan Duan; Yanjun Zeng (Journal of Computational Neuroscience, 2014)

Distribution of stable carbon isotope in coalbed methane from the east margin of Ordos Basin - Yong Li; DaZhen Tang; Yi Fang; Hao Xu; YanJun Meng (Science China Earth Sciences, 2014)

siRNA Combinations Mediate Greater Suppression of Hepatitis B virus Replication in Mice - Guiqiu Li; Lu Fu; Jinghong Jiang; Yuzhuo Ping; Yanjun Huang; Yongchen Wang (Cell Biochemistry and Biophysics, 2014)

Development of novel AllGlo-probe-based one-step multiplex qRT-PCR assay for rapid identification of avian influenza virus H7N9 - Yanjun Zhang; Haiyan Mao; Juying Yan; Xinying Wang; Lei Zhang; Koch Guus; Hui Li; Zhen Li; Yin Chen; Liming Gong; Zhiping Chen; Shichang Xia (Archives of Virology, 2014)

Phosphoinositide 3-Kinase Pathway Mediates Early Aldosterone Action on Morphology and Epithelial Sodium Channel in Mammalian Renal Epithelia - Yuan Zhou; Xuewei Chen; Xiao Liu; Hujie Lu; Ying Li; Hui Zhu; Gaihong An; Na Zhang; Jianning Zhang; Qiang Ma; Yanjun Zhang (The Journal of Membrane Biology, 2014)

Coalbed methane produced water in China: status and environmental issues - Yanjun Meng; Dazhen Tang; Hao Xu; Yong Li; Lijun Gao (Environmental Science and Pollution Research, 2014)

Regulatory function of AMP1 in ABA biosynthesis and drought resistance in arabidopsis - Yanyan Yao; Chun-Hai Dong; Yanjun Yi; Xiang Li; Xiangman Zhang; Jiayao Liu (Journal of Plant Biology, 2014)

In vitro study of nano-HA/PLLA composite scaffold for rabbit BMSC differentiation under TGF-β1 induction - Weimin Zhu; Kang Chen; Wei Lu; Qifeng Sun; Liangquan Peng; Wenzhe Fen; Hao Li; Yangkan Ou; Haifeng Liu; Daping Wang; Yanjun Zeng (In Vitro Cellular & Developmental Biology - Animal, 2014)

Effects of Cow Dung Biochar Amendment on Adsorption and Leaching of Nutrient from an Acid Yellow Soil Irrigated with Biogas Slurry - Yanjun Guo; Hua Tang; Guangdi Li; Deti Xie (Water, Air, & Soil Pollution, 2014)

MiR-199a-5p promotes migration and tube formation of human cytomegalovirus-infected endothelial cells through downregulation of SIRT1 and eNOS - Shanchao Zhang; Lei Liu; Ruijin Wang; Houzhen Tuo; Yanjun Guo; Li Yi; Jiawei Wang; Dexin Wang (Archives of Virology, 2013)

Genome-wide transcriptional analysis of apoptosis-related genes and pathways regulated by H2AX in lung cancer A549 cells - Chengrong Lu; Min Xiong; Yuan Luo; Jing Li; Yanjun Zhang; Yaqiong Dong; Yanjun Zhu; Tianhui Niu; Zhe Wang; Lianning Duan (Apoptosis, 2013)

Exploiting the Role of Resveratrol in Rat Mitochondrial Permeability Transition - Yue Zhang; Fangfang Tian; Qi Xiao; Yanjun Hu; Jiahan Li; Fenglei Jiang; Yi Liu (The Journal of Membrane Biology, 2013)

Lower limits of evaluation parameters for the lower Paleozoic Longmaxi shale gas in southern Sichuan Province - YanJun Li; Huan Liu; LieHui Zhang; ZongGang Lu; QiRong Li; YongBin Huang (Science China Earth Sciences, 2013)

Antisense MMP-9 RNA inhibits malignant glioma cell growth in vitro and in vivo - Cuiyun Sun; Qian Wang; Hongxu Zhou; Shizhu Yu; Alain R. Simard; Chunsheng Kang; Yanyan Li; Yanling Kong; Tongling An; Yanjun Wen; Fudong Shi; Junwei Hao (Neuroscience Bulletin, 2013)

Spatially explicit estimation of domestic water use in the arid region of northwestern China: 1985–2009 - Bin Guo; Yaning Chen; Yanjun Shen; Weihong Li; Chengben Wu (Hydrological Sciences Journal, 2013)

Characterization of Two Mammalian Cortical Collecting Duct Cell Lines with Hopping Probe Ion Conductance Microscopy - Xuewei Chen; Hui Zhu; Xiao Liu; Hujie Lu; Ying Li; Jing Wang; Hongtao Liu; Jianning Zhang; Qiang Ma; Yanjun Zhang (The Journal of Membrane Biology, 2013)

β-Arrestin prevents cell apoptosis through pro-apoptotic ERK1/2 and p38 MAPKs and anti-apoptotic Akt pathways - Xiaohua Yang; Gengyin Zhou; Tao Ren; Hui Li; Yanjun Zhang; Deling Yin; Haixin Qian; Qinchuan Li (Apoptosis, 2012)

Transcriptional and Functional Studies of a Cd(II)/Pb(II)-Responsive Transcriptional Regulator(CmtR) from Acidithiobacillus ferrooxidans ATCC 23270 - Chunli Zheng; Yanjun Li; Li Nie; Lin Qian; Lu Cai; Jianshe Liu (Current Microbiology, 2012)

Nitrogen leaching and phosphorus accumulation in a perennial pasture after composted goat manure was topdressed and incorporated in the Three Gorges region - Yanjun Guo; Guangdi Li (Journal of Soils and Sediments, 2012)

A comparison study of the simulation accuracy between WRF and MM5 in simulating local atmospheric circulations over Greater Beijing - ZhenXin Liu; ShuHua Liu; Fei Hu; Ju Li; YanJun Ma; HePing Liu (Science China Earth Sciences, 2012)

Clinical implications for BRCA gene mutation in breast cancer - Jin Xu; Baosheng Wang; Yanjun Zhang; Ruihui Li; Yuehua Wang; Shaokun Zhang (Molecular Biology Reports, 2012)

Spatial and temporal trends of climate change in Xinjiang, China - Qihu Li; Yaning Chen; Yanjun Shen; Xingong Li; Jianhua Xu (Journal of Geographical Sciences, 2011)

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)

Wheat vacuolar H+-ATPase subunit B cloning and its involvement in salt tolerance - Li Wang; Xiaoliang He; Yanjun Zhao; Yinzhu Shen; Zhanjing Huang (Planta, 2011)

Identification and characterization of a novel l-arabinose isomerase from Anoxybacillus flavithermus useful in d-tagatose production - Yanjun Li; Yueming Zhu; Anjun Liu; Yuanxia Sun (Extremophiles, 2011)

Geochronologies of the Huaixi copper-gold deposit and the Caomen alkaline granite, SE China: implications for tectonic evolution - Yanjun Li; Junhao Wei; Jun Tan; Chunliang Yao; Lina Peng; Guangling Xiao; Yunfei Yan; Zefu Ye (International Geology Review, 2011)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)

Identification of genes contributing to quantitative disease resistance in rice - YanJun Kou; XiangHua Li; JingHua Xiao; ShiPing Wang (Science China Life Sciences, 2010)

Effect of NaCl on leaf H+-ATPase and the relevance to salt tolerance in two contrasting poplar species - Xiuying Ma; Lin Deng; Jinke Li; Xiaoyang Zhou; Niya Li; Decai Zhang; Yanjun Lu; Ruigang Wang; Jian Sun; Cunfu Lu; Xiaojiang Zheng; Eberhard Fritz; et al. (Trees, 2010)

Application of enzyme-linked immunosorbent assay for quantification of the insecticides imidacloprid and thiamethoxam in honey samples - Huixin Ma; Yanjun Xu; Qing X. Li; Ting Xu; Xintong Wang; Ji Li (Food Additives & Contaminants: Part A, 2009)

Molecular analyses of the rice tubby-like protein gene family and their response to bacterial infection - Yanjun Kou; Deyun Qiu; Lei Wang; Xianghua Li; Shiping Wang (Plant Cell Reports, 2009)

Study of hypoxia-induced expression of HIF-1α in retina pigment epithelium - Zeng Yanjun; Li Guangyu; Fan Bin; Wang Qing; Jie Ying; Liu Aizhen (Bulletin of Experimental Biology and Medicine, 2007)

Microdialysis as a tool in local pharmacodynamics - Yanjun Li; Joanna Peris; Li Zhong; Hartmut Derendorf (The AAPS Journal, 2006)

Genome-wide analysis of cyclin family in rice (Oryza Sativa L.) - Honggui La; Jun Li; Zhendong Ji; Yanjun Cheng; Xiuli Li; Shuye Jiang; Prasanna Nori Venkatesh; Srinivasan Ramachandran (Molecular Genetics and Genomics, 2006)

Comparative study on Chinese urban agglomeration districts - Chenggu Li; Yanjun Huang; Qichun Wang (Chinese Geographical Science, 1998)

A study on recession mechanism and rejuvenation ways of the Northeast old industrial base - Chenggu Li; Yanjun Huang; Qichun Wang (Chinese Geographical Science, 1997)